Zein-β-cyclodextrin composite particles for clove essential oil-loaded high internal phase Pickering emulsions: Preparation, characterization and functional fat mimicry of meat products - Lanxin Zhang; Lu Yang; Meihan Wang; Jun-Hua Shao; Yanwei Zhang; Chunqiang Li (Food Hydrocolloids, 2027)

Nitrogen-doped porous carbon from sucrose-polyaniline precursor co-processing: high CO2 adsorption performance and cyclic stability - Li Zhao; Run Zhang; Yong-sheng Ma; Zhong-hao Wu; Qi Niu; Xin-hua Yuan; Xin-yue Zhou; Kai Li; Qiang Lu (Biomass and Bioenergy, 2027)

High-resolution carbon isotope chemostratigraphy of the upper Cambrian from the East Tarim Basin and implications for global correlation and paleoenvironment reconstruction - Xiao-Jun Zuo; Bo Chen; Hong-Xing Wei; Zhi-Xin Sun; Xin-Sheng Luo; Guo-Xiang Li; Zhi-Bin Huang; Miao Lu; Yong-Quan Chen; Ai-Hua Yang; Fang-Chen Zhao; Mao-Yan Zhu (Palaeoworld, 2026)

Mitogenomes of three Sinoxylon species and phylogenetic analysis of Bostrichoidea (Coleoptera) - Hua-Min Fan; Xiao-Yun Wang; Kai Lin; Qian Lu; Qiu-Hong Tao; Jun Li; Xia-Lin Zheng (Molecular Genetics and Genomics, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Inverse design of multi-frequency bandgaps for multi-modal vibration control in long-span bridge cables - Chun-Sheng Lu; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li (Engineering Structures, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Efficient purification of bio-oil-derived levoglucosenone via a multi-stage synergistic separation strategy - Kai Li; Yong-sheng Ma; Bo Wang; Ding-wang Qiao; Qi Niu; Cheng-long Ruan; Bi-heng Bao; Xin-hua Yuan; Qiang Lu (Biomass and Bioenergy, 2026)

Urbanization facilitates colonization and reshapes strangler-host networks: the fate of strangler figs in a tropical urban landscape and implications for management - Yu-Xuan Mo; Huang Zou; Hai-Xia Hu; Josep Peñuelas; Zhi-Peng Wang; Bang-Xiao Zheng; Xian-Meng Shi; Su Li; Sujan Balami; Hua-Zheng Lu; Liang Song (Urban Forestry & Urban Greening, 2026)

Thermal effects on aquifer storage and recovery in brackish aquifers - Hongkai Li; Zhilin Guo; Zidong Pan; Yang Zhan; Sichen Wan; Hua Zhong; Chunhui Lu; Chunmiao Zheng (Journal of Hydrology, 2026)

Probabilistic modeling of failure mechanisms of sensitive clay slopes with non-stationary heterogeneity - Shui-Hua Jiang; Jian-Ping Li; Guo-Tao Ma; Lu-Lu Zhang; Mohammad Rezania; Mohaddeseh Mousavi Nezhad (Computers and Geotechnics, 2026)

Deep removal of Cu-EDTA from saline wastewater via an ozonation-adsorption process: Salt-promoting effect and nanocomposite sequestration - Xin Li; Zhiting Li; Lu Lv; Weiming Zhang; Bingcai Pan; Ming Hua (Chemical Engineering Journal, 2026)

Macrocycle-size-modulated Cl− microenvironments in cationic mesoporous polymers for rapid capture of volatile iodine - Zhangjie Huang; Jinkai Qiu; Liang Liu; Qimeng Sun; Xiaoyong Xia; Cheng Lian; Dongyun Chen; Hua Li; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2026)

Unravelling saltmarsh organic carbon sources: biomarker-isotopic integration for credible blue carbon accounting - Jinge Zhou; Hua He; Han Chen; Jingfan Zhang; Zhe Lu; Shuchai Gan; Guoming Qin; Lulu Zhang; Xingyun Huang; Neil Saintilan; Ding He; Yongxia Jia; et al. (CATENA, 2026)

Tracking clinically critical antibiotic-resistant bacteria and resistance genes in biogas slurry-amended soil: occurrence, enrichment and vertical distribution - Jiwei Li; Yi Lu; Xingshuo Wang; Lifeng Ping; Hua Li; Guanyu Zheng; Ming Hung Wong; Shengdao Shan (Bioresource Technology, 2026)

Nitrogen-driven shifts in soil extracellular enzyme systems and stoichiometric indicators in a tropical ecosystem - Odhiambo O. Nicholas; Zhangbing Chen; Qilin Zhu; Xunzhun Li; Chaoqi Liu; Hua Zhao; Nathan Okoth Oduor; Tracy Opande; Jawad Ullah; Qiqian Lu; Xiaoqian Dan; Jinbo Zhang; et al. (Soil Ecology Letters, 2026)

T2T and chromosome-level genome assemblies provide insights into the genetic basis of bioactive compound biosynthesis and environmental adaptation in licorice - Shandang Shi; Fei Wang; Tianxin Lu; Guozhi Li; Mengqian Long; Chao Jiang; Rui Tang; Shiyan Cui; Wei Wang; Hua Yao; Xuechi Li; Meng Meng; et al. (Science China Life Sciences, 2026)

Mechanisms of combined tetracycline and sulfadiazine stress inhibiting nitrogen transformation in aerobic granular sludge: Insights from oxidative stress, energy metabolism and functional genes - Wenhao Liu; Rushu Sun; He Wang; Xiaoxu Lu; Xiaocheng Wei; Yuxiao Zhao; Haipeng Xu; Yan Li; Dongliang Hua; Wenli Huang (Journal of Environmental Management, 2026)

Corrigendum to “Collaboratively optimize of multi-scale spatial form within urban blocks for low-carbon performance: A machine learning-driven design support framework” [Sustainable Cities and Society, 143 (2026), 107342] - Gaomei Li; Hongxin Guo; Jian Kang; Yichen Dong; Hua Zhong; Anting Gao; Wei Lu; Shen Xu (Sustainable Cities and Society, 2026)

Structurally diverse diterpenoids from Euphorbia milii: Discovery and RORγt-binding evaluation - Meng-Yuan Dai; Xue-Li Hu; Wen-Chang Li; Zhi Lu; Bin-Yuan Jiang; Hua-Mei Chen; Ying Zeng; Dong-Hua Cao (Phytochemistry, 2026)

Disruption of OsGONST3 reduces grain cadmium accumulation without yield penalty in field-grown rice - Jing Huang; Qiang Zhang; Fang Wei Yu; Ming Qing Liu; Huai Kang Jing; Shen Yun Wang; Hao Yu Wang; Jia Qi Li; Lu Zheng; Hua Shao; Xiao Lin He; Ren Fang Shen; et al. (Journal of Hazardous Materials, 2026)

Activity-guided discovery of antibiotic-transforming bacteria from environmental microbiomes using D-amino acid–assisted fluorescence-activated cell sorting - Yi Liu; Kai-Li Wang; Yu-Qi Hong; Ye Yuan; Hua Wang; Yi-Qun Chen; Sheng-Song Yu; Zi-Xuan Lu; Yuan Pan; Ting-Ting Zhu (Environmental Pollution, 2026)

Cold exposure induced cognitive impairment: A systematic review - Bing-Yao Liu; Xin-Mei Ma; Si-Wei Wang; Qi-Feng Li; Jun-Hua Chen; Sen Li; Hai-Yan Wang; Xiu-Min Lu; Yong-Tang Wang (Cryobiology, 2026)

Enhanced Gaussian Splatting SLAM for lunar exploration using landmark-centric re-localization - Meng Yu; Chenxi Lu; Yin Wang; Hua Li (Advances in Space Research, 2026)

Neddylation E2 enzyme UBE2M inhibits inflammatory lung tumor microenvironment by blocking the cGAS-STING signal upon KrasG12D activation - Yawen Zheng; Cantong Chen; Xufan Li; Zhouyang Li; Hua Li; Mingjia Tan; Danyi Zhai; Fengwu Zhang; Wenjing Lu; Zhihua Chen; Yongchao Zhao; Pengyuan Liu; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Type selection and parameter optimization of FRP-steel-concrete composite columns based on machine learning interpretability analysis - Hai-yang Gao; Wen-qi Liu; Hui Li; Li-hua Lu; Hong-bing Bao (Ocean Engineering, 2026)

Spatial structure-mediated attenuation of protective LAB–pathogen competition: Quantitative modeling in structured versus liquid matrices - Chun-lei Lu; Jiao Li; Hua-xiang Li; Zhen-quan Yang (International Journal of Food Microbiology, 2026)

Ultrasensitive SERS aptasensor using multilayered hollow Au/Ag alloy nanourchin SERS tags for trace kanamycin detection in food - Qiaoqiao Shi; Li Lu; Tao Liu; Qian Chen; Dezhao Kong; Hua Ye (Food Bioscience, 2026)

Beyond conventional biochar: Sulfur-iron modification unlocks redox control for synergistic cadmium-arsenic sequestration in paddy soils - Zihao Liang; Hua Lin; Honghu Zeng; Sze-Mun Lam; Jin-Chung Sin; Xuehong Zhang; Guo Yu; Mi Feng; Yanpeng Liang; Huawei Li; Yuxi Lu; Gongning Chen (Environmental Research, 2026)

Tuned pile vibration isolation method for near-field rail transit based on the negative effective mass density model for a dual-resonator system - Chun-Sheng Lu; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li (Engineering Structures, 2026)

Injectable adhesive hydrogel with self-assembled dual-enzyme nanofibers for spatiotemporal modulation of inflammation and axon regeneration after spinal cord injury - Qi Sha; Yuan Li; Zuomeng Wu; Yankai Wang; Yunxiao Fang; Ao Liu; Shunfeng Liu; Yixiang Dong; Lu Ye; Yue Qin; Shuhui Sun; Junjie Zhao; et al. (Chemical Engineering Journal, 2026)

Fish-gill-inspired hierarchical membranes with charge-repulsion-mediated ion-selective nanostructures for enhanced desalination performance - Yingxue Zhang; Wei Sun; Haoyu Jiang; Qiuxuan Zhou; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2026)

Infection risks associated with b/tsDMARDs in rheumatoid arthritis: a systematic review and network meta-analysis - Xue-Mei Zhang; Li Liu; Yi-Dan Yan; Zai-Li Zhang; Ke-Jia Le; Yang-Xi Liu; Xiao-Jun Ni; Liang-Jing Lu; Guo-Hua Zhou; Zhi-Chun Gu; Jia Li; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2026)

Integrated, in situ gas/steam thermal desorption–chemical oxidation for volatile organic compounds and odorants in deep, contaminated soils - Hongguang Zheng; Yanfei Wang; Yi Shi; Hefeng Lu; Jingqi Zhang; Weiguang Zhao; Tianran Li; Jie Hua; Riming Lu; Wenlu Li; Xiaofei Zhang; Juejun Yao; et al. (Environmental Geochemistry and Health, 2026)

Synthesis and biological evaluation of Phorbazole D analogues identify IO-5a as a promoter of hUC-MSC chondrogenic differentiation - Ai-zhu Wang; Xiao-mei Liu; Li-ming Zhang; Lu-lu Fu; Ping Li; Jie-ping Zhang; Hua Han (Molecular Diversity, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Linking the dietary inflammation index to sarcopenia in diabetes: mediation by body roundness index and evidence from complementary analyses - Yang Yang; Ren-hua Lv; Peng-min Liu; Yan-qiu Sun; Lu-ping Wang; Yu Yu; Li-mei Zhang; Xin-yang Zhang (European Journal of Applied Physiology, 2026)

25-hydroxyvitamin D3 enhances growth and immunity in Litopenaeus vannamei by modulating gut health and hepatopancreatic gene expression: A comparative study with vitamin D3 - Guanda Zhu; Junbo Wang; Kangle Lu; Naifeng Li; Shudao Huang; Yingtiao Lai; Feifei Wang; Ling Wang; Chunxiao Zhang; Hua Gong (Aquaculture, 2026)

Novel non-thermal plasma based strategy to synthesize high-performance multistage mesoporous cobalt-ceria oxides for plasma-catalytic decomposition of environmentally hazardous acetone - Lu Liu; Jian-hua Liu; Zhen-yun Wang; Guang-cai Shao; Yan-gang Hu; Karen Leus; Jian-li Mi; Chuan-long Ma; Rui-tang Guo; Qing-shan Wang; Anton Nikiforov; Pascal Van Der Voort; et al. (Journal of Hazardous Materials, 2026)

Efficient capture of Cs+ ions by two supertetrahedral cluster-based microporous metal chalcogenides in neutral and alkaline environments - Ya-Dong Wu; Lu Yang; Zhi-Hua Chen; Hai-Yan Sun; Chuan Lv; Xiao-Ying Huang; En-Chao Li; Mei-Ling Feng (Journal of Hazardous Materials, 2026)

Bidirectional extracellular electron transfer facilitates cyanobacterial high-light adaptation on rock varnish - Yimei Du; Houze Lu; Yan Li; Qi Li; Yanzhang Li; Fuchen Wang; Xiaoming Xu; Tianci Hua; Tao Li (Geochimica et Cosmochimica Acta, 2026)

Identification of Metabolism-Related Genes with Potential Diagnostic Value in Gestational Diabetes Mellitus - Yan Mo; Yan-Yuan Bai; Xiu-Fang Li; Hua Zhang; Juan Liang; Wen-Juan Zhang; Li Lu; Wan-tao Liang (Indian Journal of Clinical Biochemistry, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

An integrated assessment of water and carbon footprints with energy evaluation in the cinnamon soil region of Northeast China - Yidong Zhao; Baoqing Chen; Yisheng Lou; Na Li; Lu Hua; Hongyan Gao; Qian Cai; Wei Bai; Wenyi Dong; Zhe Zhang (Environment, Development and Sustainability, 2026)

Detection of Storm Surge-Induced Non-Tidal Ocean Loading Deformation in Hong Kong Using Sub-Daily GNSS Observations - Ran Lu; Hua Chen; Zhao Li; Mingyuan Zhang; Yanming Feng; Weiping Jiang (Journal of Earth Science, 2026)

Probiotic Effects of Marichromatium gracile DH-1 on Growth, Stress Resistance, and Water Quality in Juvenile Seahorses: A Potential Strategy for Sustainable Aquaculture - Kai-Hua Geng; Shuai Liang; Yi Zhang; Ya-Juan Wang; Tian-Yu Lu; Yunfeng Liu; Tian Lan; Ya-Nan Lu; Yu-Ting Cong; Yuan Wang; Li Wang; Lian-Shun Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Collaboratively optimize of multi-scale spatial form within urban blocks for low-carbon performance: A machine learning-driven design support framework - Gaomei Li; Hongxin Guo; Jian Kang; Yichen Dong; Hua Zhong; Anting Gao; Wei Lu; Shen Xu (Sustainable Cities and Society, 2026)

Mid-Eocene thrusting and early Pleistocene brittle reactivation of the Lancangjiang fault and their implications for the incision of the Lancang River in the SE Tibetan Plateau - Kui Tong; Jinxi Li; Shugen Liu; I. Tonguç Uysal; Andrew Todd; Zijian Wang; Lu Zeng; Tian Hua; Zhiwu Li (Global and Planetary Change, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

Characterization and biological activity of djulis (Chenopodium formosanum) phytosomes and in vivo cosmeceutical applications - Chien-Shan Chiu; Yung-Jia Chan; Min-Hsuan Wu; Bing-Lun Hua; Wen-Chien Lu; Zeng-Chin Liang; Po-Hsien Li (Food Bioscience, 2026)

Transparent superhydrophobic high-emissivity coatings for synergistic self-cleaning and passive cooling of photovoltaics - Li Wan; Yan Yang; Chao-Hua Xue; Xiao-Jing Guo; Pan Lu; Jing-Jing Peng (Chemical Engineering Journal, 2026)

Al3+/H+ dual-cation synergistic phosphorus-functionalized MXene aerogel for supercapacitor applications - Yan Song; Changrui Hua; Linghong Lu; Shiben Jiang; Guanyu Chu; Jun Li (Chemical Engineering Journal, 2026)

Bioactive electrospun membrane with DHBA/Zn-MOF for enhancing neurovascular coupling in diabetic wound healing - Manjuan Li; Peng Hua; Linsa Zhou; Lexuan Fang; Pingping Ma; Zixuan Wang; Shicui Jiang; Qiang Zhou; Gaowen Li; Xudong Zheng; Chi Zhang; Litai Jin; et al. (Chemical Engineering Journal, 2026)

Magmatic-hydrothermal evolution and Li mineralization recorded by correlated crystal chemical zoning of spodumene and muscovite in Lijiagou pegmatites of the Songpan-Garze fold belt, eastern Tibet - Xue Lu; Guangchun Fei; Julian F Menuge; Tianrui Li; Hu Yun; Huipai Zhu; Hua Tan; Yunhua Cai; Guibing Yang; Wenchun Tang; Xi Chen (Mineralium Deposita, 2026)

Non-ignorable dipeptides as nitrogenous precursors in chlor(am)ination: Tyrosyl-L-phenylalanine generates higher toxicity to mammalian cells than aromatic monomeric amino acids - Yiyi Hu; Yao Lu; Yuen Guo; Hua Li; Ying Chen; Min Liu; Wei Hu; Qianyuan Wu; Ye Du (ENGINEERING Environment, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Performance analysis and experimental study of flexible opening-closing single garlic seed metering device based on DEM-MBD coupling - Zhengzhong Li; Hua Zhou; Yinping Zhang; Fangyuan Lu; Xian Wang; Jiaye Li; Yanjun Li; Yangting Hu; Rui Yu (Computers and Electronics in Agriculture, 2026)

Risk assessment and exposure patterns of hydroxypolycyclic aromatic hydrocarbons in elderly population: Insights from urinary metabolite levels and dietary habits - Yafei Gao; Biwen Wang; Liting Hua; Juanhua Li; Junqi Liu; Yang Peng; Lu Cheng; Hongkai Zhu; Hongwen Sun; Han Li; Hongzhi Zhao (Journal of Environmental Sciences, 2026)

Comparative metabolomic evaluation of Schisandraceae leaves as novel food ingredients: nutritional quality and biofunctional components across genera - Lu Zhang; Huimin Tang; Jie Zheng; Qiuyu Yu; Hua Wang; Dewen Li; Zhonghua Zhang; Zhonghua Tang (Food Research International, 2026)

Impacts of tree species and stand density on canopy rainfall partitioning in N deposition to plantation forests - Shan Lu; Guangyong Li; Zhi-Hua Zhang; Shuailin Tian; Wende Tang; Jinsong Zhang; Yuqiang Sang; Sujuan Tian (Forest Ecology and Management, 2026)

Discovery and screening of thermostable signature peptides for robust quantification of wheat allergens in processed foods - Yingjun Lu; Xiaojing Yu; He Li; Jingwen Sun; Yan Chen; Xiaomei Zhang; Xiaosha Wen; Dixian Luo; Hua Ji; Hongwei Zhang (Food Chemistry, 2026)

Determinants of the variability of PGPB effects on zinc biofortification and crop yield: a meta-analysis - Hua He; Lu Peng; Jinzhi Liu; Fangchi Yang; Xiu Li; Qin Lan; Xiaoyan Tang; Yanyan Zhang; Bing Li; Changquan Wang; Yingjie Wu (Plant and Soil, 2026)

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Iatrogenic plasticizer Di(2-ethylhexyl) phthalate (DEHP) exposure increases Sepsis mortality risk: Machine learning implicates monocyte-driven immune dysregulation - Jun-jie Gao; Li-zhu Huang; Tao Wang; Yun-long Zhang; Kai Ye; Wei-hua Lu; Pu-hong Zhang (Toxicology and Applied Pharmacology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A novel salt-tolerant purple photosynthetic bacterium Afifella marina TC201-1 for sustainable treatment of saline aquaculture wastewater - Shuai Liang; Kai-Hua Geng; Ding-xian Xu; Ya-Juan Wang; Wei-Yu Du; Yun-Feng Liu; Ya-Nan Lu; Li Wang; Yuan Wang; Jing Gu; Yu-Ting Cong; Lian-Shun Wang; et al. (Journal of Water Process Engineering, 2026)

Multi-metal/MOF-derived N-doped carbon electrocatalysts: Synergistic enhancement for practical oxygen reduction - Xuan Yang; Cong Li; Cheng Li; Jinrong Lu; Chenxin Wang; Hua Liu (Journal of Environmental Chemical Engineering, 2026)

Self-assembled D-A type conjugated polymer nanofilms with enhancing π–π stacking ability for efficient phenolic pollutant purification - Lijun Zhu; Xinyue Huang; Chenfan Xie; Hua Li; Jianmei Lu (Journal of Environmental Chemical Engineering, 2026)

Dual real-time fluorescent and colorimetric LAMP assay for rapid and on-site identification of sturgeon (Acipenser and Huso) - Chao Ji; Jiaxiu Yao; Yuxiao Lu; Xiangan Li; Sentao Liu; Marti Z. Hua; Henry K. Rotich; Lara Tinacci; Wenjie Zheng; Liangjuan Zhao; Xiaonan Lu (Food Chemistry, 2026)

Influence of brewing method on the nutritional composition and sensory attributes of coffee by Arabica beans of different roasting degrees - Amna Gulshan; Mst Nushrat Yiasmin; Mustafa Zeb; Anam Mushtaq; Weichao Cao; Rongrong Lu; Xiaoxuan Li; Xiao Hua (Food Chemistry, 2026)

Inhibition of ferroptosis improves mitochondrial function and color stability in postmortem beef: Associations with the NRF2/SLC7A11/PRDX6 pathway - Cai-Yun Li; Fang-Fang Lu; Li-Hua Zhu; Ya-Ning Qu; Yu-Bin Zhang (Food Bioscience, 2026)

High electron storage MXene-based adsorption membrane electrode for rapid remediation of uranium-containing wastewater - Mengfei Gao; Xin Lu; Wenxiang Li; Xin Gao; Shibing Shi; Bin Xing; Hua Zhao; Jian Li; Xuan Guo; Yanbiao Liu; Yi Wang (Chemical Engineering Journal, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Meta-analysis of the preventive effects of phytochemicals on Benzo(a)pyrene-induced lung tumors in animal models - Juan Lu; Wei Wei; Zhixin Tang; Kang Li; Shouyue Zhang; Shuai Wu; Yuyao Yang; Yang Liu; Xiaohui Hua (PharmaNutrition, 2026)

A study on the susceptibility of Helice tientsinensis to infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Meifeng Wang; Xiuhua Wang; Jie Huang; Chen Li; Qingli Zhang; Xinyu Lian; Ruoxuan Lu; Hua Xu; Xinyi Fu; Ziyue Gou; Peng Jia; Bing Yang (Journal of Invertebrate Pathology, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Study on the mechanism evolution of carbon structure during blending coal coking - Hanwen Zhu; Peng Yu; Xinni Zhao; Lu Tian; Hua Li; Xingxing Chen; Jinxiao Dou; Jianglong Yu (Fuel, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Flexible thiol–ene crosslinked reduced graphene oxide-functionalized styrene-butadiene-styrene films with enhanced thermal conductivity and electromagnetic interference shielding efficiency - Xinyu Liu; Xiaohui Lv; Chuang Peng; Linzhe He; Yibo Zhang; Song Lei; Guo-Hua Hu; Zhehong Lu; Tao Ding; Xiaohong Li; Zhijun Zhang (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Validation on cloud fraction products from satellite and reanalysis data over the Tibetan Plateau - Xiaoyang Guo; Shaoqi Gong; Hailong Zhang; Li Li; Lu Han; Li Gu; Hua Li; Hao Zhang; Qinhuo Liu (Advances in Space Research, 2026)

Effects of adding Afifella marina on growth performance, intestinal health, and microbial community of juvenile Hippocampus abdominalis - Shuai Liang; Kai-Hua Geng; Yi Zhang; Ya-Juan Wang; Tian-Yu Lu; Tian Lan; Ya-Nan Lu; Yuan Wang; Jing Gu; Yu-Ting Cong; Li Wang; Lian-Shun Wang; et al. (Aquaculture International, 2026)

Real-time visualization of Nocardia seriolae proliferation and macrophage migration in the Northern snakehead (Channa argus) - Jian Teng; Jian-Ru Liu; Yi-Xiang Zhai; Sheng-Liang Cao; Zhen-Shu Si; Qing-Teng Ren; Xiang-Shan Ji; Mei-Hua Lu; Yu-Bao Li; Yan Zhao (Aquaculture, 2026)

Proanthocyanidin B2 regulates epidermal growth factor receptor (EGFR) and activates the PI3K/AKT pathway to promote the in vitro maturation of sheep oocytes - Yucheng Liu; Jingjing Wang; Zhenliang Zhang; Jiachen Bai; Houru Li; Zhanmin Lv; Lei Gao; Jianhong Ni; Shouliang Lu; Changbin Liu; Guiping Hai; Weijun Liu; et al. (Theriogenology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Experimental study on the resetting of IRSL and IRPL signals induced by frictional heating in rocks at seismic slip velocities - Furong Cui; Huili Yang; Jie Chen; Lu Yao; Jinfeng Liu; Jintang Qin; Myungho Kook; Sheng-Hua Li (Quaternary Geochronology, 2026)

Different expansion events of the actin and tubulin gene families within spirotrichean ciliates (Alveolate, Ciliophora) - Hua Su; Zengyu Song; Guoling Chai; Fangfang He; Yize Li; Yuxuan Qian; Xuefen Lu; Qi Zhang; Zhenzhen Yi (Molecular Phylogenetics and Evolution, 2026)

Organic carbon burial and ocean redox modulated biotic recovery after the latest Ordovician crisis - Wei Tang; Mu Liu; Heng-Ye Wei; Li-Guang Wu; Kai Lu; Jian Wang; Xian-Hua Li (Earth and Planetary Science Letters, 2026)

High-sensitivity, multi-modal triboelectric sensor derived from Kevlar for self-powered Morse code transmission and human-machine interaction - Tao Huang; Zhaoqing Lu; Fengfeng Jia; Ruixue Pang; Huimei Zhao; Pengbo Yang; Chunting Li; Jingfeng Chen; Li Hua (Chemical Engineering Journal, 2026)

Upcycling waste polyphenylene sulfide into microporous carbons with high yields for producing freshwater and electricity - Liang Li; Jie Li; Mengyuan Jiang; Liuyi Lu; Yanyan Shan; Xiaojun Wang; Luoxin Wang; Hua Wang; Qingquan Tang; Jiang Gong (Chemical Engineering Journal, 2026)

Integrating an CNOP analysis into a deep learning model to identify optimal initial errors for 2020–2022 La Niña prediction - Lingjiang Tao; Rong-Hua Zhang; Wansuo Duan; Lu Zhou; Tiaoye Li (Climate Dynamics, 2026)

Regulation of phytoplankton community structure by nitrogen-phosphorus stoichiometry in Apostichopus japonicus culture ponds under summer high-temperature conditions - Kaihua Geng; Sitong Li; Jianlong Liu; Zhijian Yin; Dingxian Xu; Shiwei Wang; Yuting Cong; Li Wang; Yuan Wang; Jing Gu; Yanan Lu; Lianshun Wang; et al. (Aquaculture International, 2026)

Design, synthesis, and biological evaluation of quinoxalinyl and quinolinyl derivatives as ALK5 inhibitors - Chuang Liu; Jun Li; Yu-Qi Lu; Yu-Xin Jiang; Cheng-Hua Jin (Molecular Diversity, 2026)

Efficient decomplexation of Cu(II) complexes and Cu(II) recovery via one-step Fenton-like oxidation/adsorption processes mediated by nanoconfined hydrous Co-Zr oxides - Xin Li; Xuewei Song; Lu Lv; Weiming Zhang; Bingcai Pan; Ming Hua (Water Research, 2026)

Nationwide mapping and characterization of land subsidence in the United States using InSAR - Zhiqiang Xiong; Guangcai Feng; Zefa Yang; Hua Gao; Wenbin Xu; Lei Zhang; Xiaohua Xu; Zhong Lu; Jun Hu; Zhiwei Li; Jianjun Zhu (Remote Sensing of Environment, 2026)

New focus on ecological risks of pesticides: The effect of pesticides on the development of bacterial antibiotic resistance - Yitong Zhao; Jingchen Wu; Chunfeng Wei; Lu Li; Fudong Liang; Yanli Man; Houpu Zhang; Lingxi Han; Hua Fang; Yongquan Zheng; Chao Ju (Journal of Hazardous Materials, 2026)

Insight into electrocatalytic activity of lattice-confined phosphorus in activated carbon fiber for recalcitrant pollutant degradation - Hao Zhang; Hua Zheng; Shaoyan Lv; Jun Lu; Minghao Fu; Li Cai; Quanyuan Chen (Journal of Environmental Management, 2026)

Evaluating blue-green infrastructure for outdoor thermal comfort and energy efficiency in a university campus microclimate: a case study from Xi’an, China - Xuan Ma; Haoyang Chen; Yuyang Lu; Qian Luo; Fangxi Yan; Tongxin Li; Jingyuan Zhao; Hua Ding (Energy and Buildings, 2026)

Construction of bonded CoAl-LDH/COF-316 hybrid photocatalysts with Z-scheme heterojunction for efficient reduction of diluted CO2 - Chao Fan; Rui-Yao Li; Can-Can Yu; Ya Wang; Yu-Xin Xie; Nan-Nan Zhang; Lu-Hua Shao; Gui-Ling Zhang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2026)

Synergistic regulation of S/C dual vacancies in Co3O4@SC for 1O2-dominated peroxymonosulfate activation: Mechanism and herbicide degradation - Jialing Sheng; Lu Liu; Wenxue Li; Jiangyan Xu; Hua Wu; Hongmei Jiang (Chemical Engineering Journal, 2026)

Insight into the synergistic SO2 removal by activated carbon loaded with amino acid based deep eutectic solvents: Mechanism, DFT calculation - Yueying Li; Xinxin Xiao; Hua Li; Guangyue Li; Liangbin Dou; Lu Tian; Jingyang Chen; Xingxing Chen; Jianglong Yu; Jinxiao Dou (Chemical Engineering Journal, 2026)

Multi-omics decoding of Phalloidin hepatotoxicity: network toxicology-guided identification of FoxO/PLD/cAMP signaling targets - Shaofang Lv; Yaozhen Gong; Hua Guo; Chong Zheng; Jianfang Ye; Lu Zou; Kai Zhu; Haichang Li; Lei Li; Yongxi Dong (Chemico-Biological Interactions, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Single-cell mass spectrometry imaging: emerging advancements and future insights - Hua Zhang; Malik Ebbini; Thao Duong; Kendra G. Selby; Kelly H. Lu; Emily Hubecky; Haiyan Lu; Lingjun Li (Analytica Chimica Acta, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Two residue mutations in VP1 of FMDV serotype A cause significant antigenic variation via reorientation of G-H loop revealed by lineage-specific neutralizing antibodies from the natural hosts - Shulun Huang; Jiaxin Yang; Fengjuan Li; Hehe Zhang; Yimei Cao; Jingjing Zha; Huifang Bao; Pinghua Li; Linfeng Liang; Zaixin Liu; Kun Li; Zengjun Lu; et al. (Veterinary Microbiology, 2025)

C-glycosylated and alkylated flavonoids with potent anti-inflammatory activity from the whole plants of Drymaria cordata - Lan-Yi Lu; Yan-Hua Wu; Peng Zhang; Li-Yan Wang (Phytochemistry, 2025)

A large, two-stage, anatectic, post-collisional late Triassic lithium pegmatite province in the Songpan-Garze Fold Belt (SGFB), Eastern Tibet, China: Constraints from geochemistry and multiple mineral U-Pb geochronology - Guangchun Fei; Julian F. Menuge; Xue Lu; Tianrui Li; Xiaolong Luo; Yunhua Cai; Huipai Zhu; Hua Tan; Chunmei Yu; Guibing Yang (Lithos, 2025)

Identifying biomarkers for arsenic exposure-induced nonalcoholic fatty liver disease: An integrated proteomics, metabolomics, and machine learning approach - Yiqiong Sun; Fuping Li; Weizhen Hua; Zhenbin Che; Meiping Tian; Yan-Yang Lu; Qingyu Huang (Journal of Hazardous Materials, 2025)

Tailoring the asymmetric structure of Cu-Co bimetallic catalysts to promote peroxydisulfate activation for pollutant degradation - Li-Ming Sun; Qin-Chen Li; Yong-Sheng Tan; Qi-Nian Wang; Yi-Lin Lu; Yi-Jun Zhang; Dong-Hua Xie; Heng-Heng Guo; Xing Zhang (Journal of Environmental Chemical Engineering, 2025)

Application of ZIF-67-grafted CuMoS in microbial fuel cells: Efficient oxygen reduction catalysis regulated by the d-band center - Cong Li; Xuan Yang; Chaoxing Chen; Chenxin Wang; Jinrong Lu; Hua Liu (Journal of Environmental Chemical Engineering, 2025)

Ampicillin-induced resistant variants of Listeria monocytogenes: effects on growth, survival, and virulence - Lu Sun; Hua Cai; Yufan Wu; Yi Hong; Yun Li; Keer Xia; Jiwei Liang; Zhuosi Li; Qingli Dong; Xiang Wang (Food Research International, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

Antioxidant and xanthine oxidase inhibitory theoretically evaluation of ferulic acid oligomers: Tetramers as outstanding dual-functional candidates - Qing-Hua Lu; Bai-Ze Liu; Jun Lu; Han Gao; Guo-Ze Wang; Jun-Li Lv; Xiao-Jun Li; Hui-Ying Peng (Food Bioscience, 2025)

Associations between PM2.5 components, temperature, and semen quality: Insights from seminal plasma metabolome - Jun-feng Tan; Li-li Huang; Zhong-Hua Lu; Hang-Yu Xiang; Hong Yang; Hai-Xia Zhou; Tian-qing Meng; Cheng-liang Xiong; Yi-Xin Wang; Jie Zhang (Environmental Research, 2025)

Machine learning-aided design of adapted water treatment adsorbents: Advances, challenges, and opportunities - Ling Yuan; Sheng Li; Yujia Ma; Han Zhang; Chen Chen; Weiming Zhang; Yanyang Zhang; Ming Hua; Lu Lv; Bingcai Pan (Chemical Engineering Journal, 2025)

Three-dimensional open structure CuCo2O4@Cu-BDC: Interface electronic coupling and d-band regulation facilitate efficient oxygen reduction - Cong Li; Hua Liu; Jinrong Lu (Chemical Engineering Journal, 2025)

Coupled non-fullerene bridging molecules improve the perovskite/PC61BM interface for high performance inverted perovskite solar cells - Shichao Sun; Mengni Zhou; Kunpeng Li; Fashe Li; Xinlong Zhao; Tao Wang; Zhongming Cai; Xue Lu; Zhishan Li; Dongfang Li; Huicong Zhang; Xing Zhu; et al. (Chemical Engineering Journal, 2025)

Highly efficient and narrow-spectrum near ultraviolet OLED achieved by hot exciton emitters with large and rigid π-conjugation - Huihui Li; Jiayi Qin; Taotao Ma; Dezhi Yang; Dongge Ma; Hua Lu; Zujin Zhao; Xin Jiang Feng (Chemical Engineering Journal, 2025)

Rock and root: Which played more important roles in preferential flow in the rocky mountain area - Jianfei Li; Jinhao Zhang; Yuefeng Shi; Shan Lu; Wu Tang; Jinsong Zhang; Si-Yi Zhang; Zhi-Hua Zhang (CATENA, 2025)

Comparative Evaluation of Spores and Vegetative Forms of Bacillus subtilis and Bacillus licheniformis on Probiotic Functionality In Vitro and In Vivo - Hua Xie; Tianfei Yu; Qiwen Zhou; Kai Na; Shuang Lu; Li Zhang; Xiaohua Guo (Probiotics and Antimicrobial Proteins, 2025)

Syringaldehyde Ameliorates Cognitive Dysfunction in APP/PS1 Mice by Stabilizing the NLRP3 Pathway - Ruidan Chen; Hua Gao; Tianshu Zhu; Ni Zheng; Yan Jin; Ming Li; Zhiming Lu (Molecular Neurobiology, 2025)

Deciphering the three-dimensional biomolecular distribution in the Alzheimer's disease brain: A multiomic approach integrating immunohistochemistry with MALDI MS imaging - Kelly H. Lu; Hua Zhang; Gargey B. Yagnik; Mark J. Lim; Kenneth J. Rothschild; Wei Li; Andrew J. Schneider; Luigi Puglielli; Lingjun Li (Analytica Chimica Acta, 2025)

Research on the Reinforcement Effect of the Elephant-Foot Method in Aeolian Sand Tunnels - Ji-hua Qin; Xi-peng Li; Ya Wang; Xiao-li Cao; Dong Li; Yi-guo Xue; Fan-meng Kong; Hui-min Gong; Bang-xiang Li; Chao Lu; Guang-kun Li (Applied Geophysics, 2025)

Inhibitory Effect of TrxR Inhibitor Ag (Ⅰ) Schiff Base Complex Against Cervical Cancer Via ROS-mediated ASK1/MAPK Signaling and Autophagy - Jian-Jun Liu; Jia-Hua Zou; Bin Dong; Xue-Ping Lu; Li-Feng Chen; San-Mei Ma; Zhong Liu (Biological Trace Element Research, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Mitochondrial dysfunction-associated cellular senescence is partially involved in bleomycin-induced pulmonary fibrosis in mice - Ya-Xin Yao; Xue Lu; Zhao Li; Hao-Yu Liao; Zhi-Bing Liu; Hui Zhao; Hua Wang; De-Xiang Xu; Zhu-Xia Tan (Toxicology and Applied Pharmacology, 2025)

Three-dimensional quantum anomalous Hall effect in Weyl semimetals - Zhi-Qiang Zhang; Yu-Hang Li; Ming Lu; Hongfang Liu; Hailong Li; Hua Jiang; X.C. Xie (Science Bulletin, 2025)

Gestational joint exposure to air pollutants and intrauterine skeletal development: Mediating effect of placental metabolome in a Chinese birth cohort - Zhong-Hua Lu; Chong Liu; Chen Tang; Jun-Feng Tan; Hao Chang; Yu-Jie Chen; Guang-Ming Li; Wen-Qing Lu; Yi-Xin Wang; Jie Zhang (Journal of Hazardous Materials, 2025)

SWAT-based analysis of flood regulation service dynamics in the Pearl River Basin (2006–2018): Mechanisms from hydrological modelling to flood events - Heng Yang; Jun Tao; Jiawei Li; Jingyi Lu; Shuyi Shi; Yaobin Meng; Hua Zhang (Journal of Cleaner Production, 2025)

Encapsulation of essential oils with soy β-conglycinin for strawberry preservation: Influence of oil types - Jiayan Lu; Qiao Zhang; Yunyan Hua; Yan Yan; Yungang Cao; Weiwei Li (Food Chemistry, 2025)

Enhanced infrared radiation of zirconate ceramics via doping engineering for high-efficiency heat transfer - Xin-Yan Li; Hui Zhang; Jun Ma; Guo-Shan Zhang; Bao-Hua Liu; Cheng-Yu He; Zhong-Wei Lu; Xiang-Hu Gao (Chemical Engineering Journal, 2025)

Self-folding enhanced mechanical and self-healing polyurethane elastomer for stretchable electronic devices - Peilong Zhou; Wei Rao; Haiyan Ma; Xiang Li; Hui Liu; Yue Lu; Pufan Wang; Jincheng Wang; Liya Jia; Hua Zhang (Chemical Engineering Journal, 2025)

Liver-targeting exosomes loaded naringenin ameliorate metabolic dysfunction-associated steatotic liver disease through ubiquitin-proteasome system initiated lipophagy - Zhenglai Hua; Xiaoyu Li; Liuchunyang Yu; JinXiu Qian; Meng Tian; Xiuyun Bai; Jue Yang; Rongjun Deng; Qiqiong Liu; Cheng Lu; Zhiwen Cao; Yuanyan Liu (Chemical Engineering Journal, 2025)

Various formation pathways of size-resolved secondary organic aerosols at a coastal site in Eastern China - Meng-Xue Tang; Jia-Yuan Wang; Ke-Jin Tang; Wen-Jie Yu; Li He; Xiao-Feng Huang; Ling-Yan He; Hui Zeng; Si-Hua Lu; Min Hu (Atmospheric Environment, 2025)

Study on the effects of microecological and chemical agents on the water quality of spiny ginseng aquaculture ponds - Chongyu Zhu; Zhijian Yin; Yuwei Zhang; Jianlong Liu; Yuting Cong; Li Wang; Yuan Wang; Jing Gu; Yanan Lu; Lianshun Wang; Guojun Yang; Hua Wang (Aquaculture International, 2025)

Effects of β-hydroxy-β-methylbutyrate inclusion on growth performance and fillet quality of olive flounder Paralichthys olivaceus fed low fishmeal based diets - Chaoqing Wei; Zhenxia Su; Cancan Xia; Lu Li; Zhicheng Song; Hua Mu; Hanliang Cheng; Jianhe Xu; Zhiguo Dong; Binlun Yan; Lu Zhang (Aquaculture, 2025)

Harnessing transposable elements for plant functional genomics and genome engineering - Xiao-Yuan Tao; Shou-Li Feng; Lu Yuan; Yan-Jun Li; Xin-Jia Li; Xue-Ying Guan; Zhong-Hua Chen; Sheng-Chun Xu (Trends in Plant Science, 2025)

A line-spread kernel function for angular anisotropy in row-dominated heterogeneous scenarios - Yifan Lu; Zunjian Bian; Chandrika Pinnepalli; Jean-Louis Roujean; Mark Irvine; Xinguang Sang; Xiaobo Luo; Hua Li; Yongming Du; Biao Cao; Qing Xiao (Remote Sensing of Environment, 2025)

Metal bioaccumulation and lipid response in aquatic ecosystem: Evidence of machine learning from Chaohu Lake, China - Qi Lu; Zhi Yuan; Wei Chang; Shen-dong Xu; Lan-lan Wu; Gang Liu; Li-yan Yang; Si-ting Liu; Meng-xue Gao; Yi-fan Hu; Xu-dong Zhang; Huan Zhou; et al. (Journal of Hazardous Materials, 2025)

3D-printed super-wetting membranes with in situ grown MOF for efficient oil-water separation - Siyuan Chen; Zhiyu Zhao; Cheng Chen; Wei Yu; Xinchun Lu; Yue Wang; Hua Li; Qianqian Zeng; Hongjun Lin; Leihong Zhao; Guanhua Jin; Liguo Shen (Journal of Hazardous Materials, 2025)

Rapid self-assembled electroactive biohybrid cathode-driven electron transfer for enhanced uranium bioremediation - Keng-Qiang Zhong; Le-Yi Chen; Meng Li; Xing Chen; Xing Lu; Yu-Chen Yang; Hao-Wen He; Bao-Hua Jing; Hong-Guo Zhang; Jia Yan; Yi-Feng Zhang (Journal of Hazardous Materials, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Insights into evaluation of infective phage MS2 enrichment method based on plate membrane tangential flow ultrafiltration from reclaimed water - Zhen Wang; Chong-Miao Zhang; Jin-Qi Yong; Qian Wang; Yang Guo; Zhi-Yuan Li; Zhou Lu; Wei-Hua Yu; Jie Zhang (Journal of Environmental Chemical Engineering, 2025)

Simplified synthetic community reveals the enrichment of phthalate-degrading bacteria in maize rhizosphere enhancing phthalate degradation - Jia-Lu Wei; Yu-Hong Huang; Jun-Hua Li; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Yan-Wen Li; Ce-Hui Mo; Quan-Ying Cai; Qing X. Li (Journal of Environmental Chemical Engineering, 2025)

Experimental study on dehumidification and heating performance of CO₂ heat pump system for electric vehicles at low ambient temperatures (5 °C and 15 °C) - Kang Li; Mingfei Tan; Soheil Mohtaram; Ni Liu; Hua Zhang; Zhuohan Lu; Jinjun Yan; Qize He; Chao Li (International Journal of Refrigeration, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Pre-reduction of Goethite by hydroxylamine hydrochloride enhances sulfamethoxazole degradation via accelerated Fe(III)/Fe(II) cycling in Fenton-like systems - Hua Li; Kun Wang; Junge Xu; Tao Li; Yi Lu; Rusen Zou; Guanyu Zheng (Chemical Engineering Journal, 2025)

Mechanically strong heterocyclic aramid nanofiber-based nanopaper via boron nitride nanosheet-incorporated polymerization and assembly of poly(p-phenylene-benzimidazole-terephthalamide) - Nan Li; Zhaoqing Lu; Doudou Ning; Li Hua; Songfeng E (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zhong-Bing Zheng; Yu Yang; Jun Liu; Ming-Cheng Zhou; Ju-Hua Li; Long-Jiang Tang; Hai-Long Nie; Kang-Sheng Chen; Feng Liu; Xiang-Ning He; Zhi-Yuan Lu (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na + -K + -ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.

Effects of age and musical training on resting-state periodic oscillatory brain activity - Sijia Guo; Ning Li; Liju Wang; Chenxi Qiu; Yuxin Chen; Yitian Yin; Hua Yang; Claude Alain; Jing Lu; Dezhong Yao (GeroScience, 2025)

Vibration isolation method based on local resonance mechanism for near-field piling in rail transport - Chun-Sheng Lu; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li (Soil Dynamics and Earthquake Engineering, 2025)

Sustainable extraction of Lycium barbarum leaf Phenolics using deep eutectic solvents: Optimization, bioactivity, and functional food potential - Yi-Long Ma; Qian-Lan Wu; Lu Jian; Xin Guo; Jing Li; Tian-Le Mao; Zhi Li; Ya-Fang Shang; Kiran Thakur; Shao-Hua Yang; Zhao-Jun Wei (Food Chemistry, 2025)

Design of 2D/2D Pt SA-MoS2/ZnIn2S4 photocatalysts for boosting hydrogen production - Xue-Lu Chen; Miao Ni; Yan-Ru Li; Yi-An Pan; Chen Chi; Yi Yang; Si-Meng Li; Sudip Biswas; Yi-Bai Sun; Xing-Hua Xia (Chemical Engineering Journal, 2025)

Thiazolyl-conjugated porous polymer-coated CdZnS for synergistic adsorption and photocatalytic degradation of bisphenol A and with enhanced H2O2 production - Wanjun Xu; Yingxue Zhang; Shihong Dong; A.S. Gubin; I.N. Pugacheva; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2025)

Herbicide clomazone induced hematotoxicity and hepatic compensatory responses in the invasive turtle, Trachemys scripta elegans - Huo-Bin Tang; Hua-Dong Li; Yu-Xin Si; Jian-Fang Gao; Hong-Liang Lu (Aquatic Toxicology, 2025)

Emergence of ceftazidime-avibactam resistance in clinical Klebsiella pneumoniae during therapy - Siquan Shen; Xiren Deng; Lu Guo; Li Yang; Hua Yu; Fupin Hu; Xiangning Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

New anti-inflammatory limonoids from the fruits of Melia azedarach - Fan Cao; Jin-Huang Shen; Zhi-Jun Li; Wen-Lu Wang; Zhen-Wei Chen; Yong-Hong Zhang; Xin-Hua Ma (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Improved satellite-scale land surface temperature components retrieval with hotspot effect correction and temperature difference constraints - Yifan Lu; Zunjian Bian; Jean-Louis Roujean; Hua Li; Frank M. Göttsche; Yajun Huang; Tengyuan Fan; Biao Cao; Yongming Du; Qing Xiao (Remote Sensing of Environment, 2025)

Assessing the performance of convection-permitting climate model in reproducing basin-scale hydrological extremes: A western Norway case study - Kun Xie; Lu Li; Hua Chen; Chong-Yu Xu (Journal of Hydrology, 2025)

Pipeline misconnections in separated sewer systems worsen urban river ecological status through stormwater discharge - Tian Ouyang; Jianchao Liu; Guanghua Lu; Hua Wang; Yiping Li; Feifei Zheng; Peng Gao (Journal of Environmental Management, 2025)

Effects of aging years on taste attributes of Huangjiu and their correlation with non-volatile compounds: A study based on E-tongue, UPLC-MS untargeted metabolomics, and WGCNA - Dianhui Wu; Ziqiang Chen; Mingtao Ma; Wenzhe Li; Zhengcong Peng; Zhenbao Shi; Jinglong Zhang; Hua Liu; Guangfa Xie; Jian Lu (Food Chemistry, 2025)

Highly boosting performance of glucose-fed microbial fuel cells by adding L-aspartic acid combined with constructing and in-situ observing electroactive biofilms - Yi Lu; Xinyuan He; Huahua Li; Hua Chen; Longxin Li; Jianlei Zhu; Ke Chen; Zongying Ding; Shiye Sun; Shaoan Cheng (Chemical Engineering Journal, 2025)

SGLT2i continuously prevents cardiac hypertrophy by reducing ferroptosis via AMPK up-regulation - Bing-bing Zhao; Jiao Wang; Lu-lu Zhang; Chao Li; Hong-hong Xue; Li Zhao; Qing-hua Han; Hong-tao Shi (Molecular and Cellular Biochemistry, 2025)

Antibiotic-induced multi-trophic effects and their cascades in a sub-tropical freshwater ecosystem - Kai-Sheng Yao; Pei-Liang Zhou; Li-Juan Tan; Hua-Qiao Yang; Lu-Kai Qiao; Fang-Zhou Gao; You-Sheng Liu; Feng-Jiao Peng; Guang-Guo Ying; Paul J. Van den Brink (Journal of Hazardous Materials, 2025)

Risk prioritization and experimental validation of per- and polyfluoroalkyl substances (PFAS) in Chaohu Lake: Based on nontarget and target analyses - Wei Chang; Shen-Dong Xu; Ting Liu; Lan-Lan Wu; Si-Ting Liu; Gang Liu; Jian Sun; Ye-Xin Luo; Lei Gao; Hao Li; Qi Lu; Zhi Yuan; et al. (Journal of Hazardous Materials, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Development of a novel chemosensor for photodynamic antimicrobial and fluorescence-colorimetric dual-mode sensing in food preservation and spoilage process monitoring - Nan Wang; Hua-Feng Mao; Lu Wang; Yi-Miao Zhang; Jun Li; Hou-Qi Ning; Shan Qian; Xiang-Gui Chen; Xiao-Qi Yu (Food Chemistry, 2025)

Explore the synergistic effects of Lactobacillus plantarum fermentation and tea polyphenols on the deodorization of egg white powder from the perspective of protein site competition - Ru-yi Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

Encapsulation of cinnamaldehyde with protein-based nanoemulsions for strawberry preservation: Influence of protein types - Jiayan Lu; Yunyan Hua; Mengjia Guo; Laixue Ni; Yuling Cai; Yungang Cao; Longfeng Wang; Weiwei Li (Food Packaging and Shelf Life, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

A hydrogel-based composite facilitates efficient and recyclable tetracycline biodegradation in aquatic environments - Ze-Hua Cui; Qian He; Zhi-Peng Li; Yao Deng; Xiao-Ping Liao; Chaoqun Zhang; Jian Sun; Hao Ren; Lu Han (Environmental Research, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

A Rock Strength Prediction Model Utilizing Real-Time Data from Percussion–Rotary Drilling Measurements - Guo-Hua Zhang; Jia-Cheng Yu; Zhao-Yang Han; Sheng-Lian Li; Lu-Zhao Dan; Dong-Jie Hua; Feng Xiong; Yu-Yong Jiao (Rock Mechanics and Rock Engineering, 2025)

Tropical cyclone probability estimation in data-sparse regions: a subtropical high based approach - Jingyi Lu; Jiazi Li; Zhenguo Wang; Xiaochao Li; Chenlu Wang; Xiaopeng Yang; Zhiguo Gao; Shaohua Wang; Hua Zhang (Natural Hazards, 2025)

Deep Hypothermic Low Flow Results in Multiple Aspects of Neurological Deficits in Mice by eEF2 Hyperphosphorylation - Yumei Liao; Dongyang Che; Peng Liu; Xinyu Wang; Yanlin Zhang; Lingling Guo; Jinlin Hu; Tianyao Li; Mei Fong Lam; Nan Ma; Shiqing Zhang; Hua Lu; et al. (Molecular Neurobiology, 2025)

Transcriptomic Response Pathways of Yeast to Crucial Polyphenolic Acids in Rosmarinus Acid Biosynthesis - Tao Xu; Jun-lu Duan; Samuel Ntakirutimana; Li Wang; Zhi-Hua Liu; Chun Li; Bing-Zhi Li (Current Microbiology, 2025)

Low-coverage whole-genome sequencing for differentiating cervical cancer from cervical intraepithelial neoplasia and benign diseases - Tingting Zhang; Fang Gu; Jia yi He; Weihua Li; Ruxue Han; Xinyu Liu; Chan Dai; Zhendong Qin; Di Zhang; Jun Lu; Hua Li (Chromosome Research, 2025)

Using deep learning to understand flood variability across the last millennium from GCM atmospheric variables in two contrasting catchments - Ran Huo; Lu Li; Kailin Huang; Hua Chen; Chuncheng Guo; Øyvind Paasche; Chong-Yu Xu (Journal of Hydrology, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Enhancing alcohol metabolism and hepatoprotection by a plant-based functional beverage in acute alcoholism and liver injury - Xinxin Zhuo; Kaizheng Zhang; Qisheng Zhang; Wei Zou; Zaixin Li; Yujie Lu; Hua Tang; Hongmei Li (Food Bioscience, 2025)

Synthesis of an autochthonous microbiota responsible for the prepared process improving, flavor profile and brewing attributes of high-temperature Daqu - Hongmei Li; Yaochuan Hou; Wei Zou; Qingsong Liu; Yujie Lu; Hua Tang; Mindan Zhang; Xinxin Zhuo; Kaizheng Zhang (Food Bioscience, 2025)

Boosting the selective hydrogenation of renewable unsaturated aldehydes to alcohols over CeO2 with different morphology - Zhendong Yu; Hongyuan Liu; Renjie Huang; Binglin Chen; Zheng Li; Xinyu Huang; Hua Zhang; Aiyong He; Lu Lin; Xianhai Zeng (Chemical Engineering Journal, 2025)

SlDCD and SlLCD increased the salt tolerance in tomato seedlings by enhancing antioxidant and photosynthesis capacity - Xinfang Chen; Dengjing Huang; Xiaoling Man; Ailing Li; Hua Fang; Siting Lu; Di Yang; Weibiao Liao (Plant Cell Reports, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Modulating JAK2/STAT3 signaling by quercetin in Qiling Baitouweng Tang: a potential therapeutic approach for diffuse large B-cell lymphoma - Xin-Zhuo Zhan; Tian-Hua Wei; Chen Huang; Hui Yu; Xiao-Li Chen; Xiang-Tu Kong; Zhi-Hao Shang; Shan-Liang Sun; Meng-Yi Lu; Hai-Wen Ni (Molecular Diversity, 2025)

Design, synthesis, and antifungal activity of novel pyrazole carboxamide derivatives containing benzimidazole moiety as potential SDH inhibitors - Fei Jin; Feng Peng; Xiang-Yi Kong; Wen-Rui Li; Jian-Qi Chai; Min Chen; Ai-Min Lu; Chun-Long Yang; Guo-Hua Li (Molecular Diversity, 2025)

Proteome profiling of the lung tissues of the mice co-infected with H9N2 influenza A virus and Pseudomonas aeruginosa - Sun Ying-Li; Fan Hua; Li Wen-qian; Li Dan; Bai Ke-fei; Dong Lu-jiao; Zhang Hui-ning; Li Jian-liang; Xie Zhi-jing (Veterinary Microbiology, 2025)

Experimental demonstration of reconstructing quantum states with generative models - Xuegang Li; Wenjie Jiang; Ziyue Hua; Weiting Wang; Xiaoxuan Pan; Weizhou Cai; Zhide Lu; Jiaxiu Han; Rebing Wu; Chang-Ling Zou; Dong-Ling Deng; Luyan Sun (Science Bulletin, 2025)

Carnivorous fishes can possess higher mercury levels than omnivorous fishes: A selective detection and efficient removal strategy for mercury using magnetic melamine-platinum composites fabricated by supermolecular self-assembly - Huilan Chen; Yunyan Li; Lily Chen Wang; Ziyi Wang; Di Wang; Luping Feng; Shuai Li; Jizhen Shang; Limin Lu; Guojiang Mao; Hua Wang (Journal of Hazardous Materials, 2025)

Metabolomic profiles of the infection pathways of Calcarisporium cordycipiticola on the cultivated and medicinal mushroom, Cordyceps militaris - Li Lu; Mahesh C.A. Galappaththi; Nimesha M. Patabendige; Yu-Zhe Feng; Tian Yang; Samantha C. Karunarathna; Jiang-Tao Xie; Eleni Gentekaki; Sylvie Rapior; Esteban Charria-Girón; Marc Stadler; Wei-Feng Ding; et al. (Fungal Biology, 2025)

Dynamics of chemical profile and microbial community in 3 consecutive years reveal Rhodococcus and Apiotrichum are potential microbes contributing to quality formation of Guang Chenpi - Fang Li; Kaiying Ge; Yi Lu; Hui Lin; Enwei Tian; Hua Li; Zhiye Yang; Zhi Chao (Food Chemistry, 2025)

Diphasic integrated 3D-bioprinting strategy using framework-enhanced porous cartilage-specific matrix hydrogels for augmentation rhinoplasty - Bohui Li; Chunlei Miao; Xujie Lu; Zhanyu Chang; Yajie Wang; Di Wang; Yingying Huo; Yilin Cao; Guangdong Zhou; Yujie Hua; Yu Liu (Chemical Engineering Journal, 2025)

Toluene-induced framework expansion in carbazole-based porous organic polymers anchored with Cu-ZnIn2S4 for ultrafast azeotropic wastewater recovery - Yingxue Zhang; Xunxun Li; Wanjun Xu; Yuxin Cheng; Shihong Dong; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2025)

SIRT5: a potential target for discovering bioactive natural products - Yuwei Xie; Nali Cai; Xiaohua Liu; Liangliang He; Yiming Ma; Changyu Yan; Juan Liang; Shu-Hua Ouyang; Ao Luo; Yingzhi He; Jun Lu; Dang Ao; et al. (Journal of Natural Medicines, 2025)
Silent information regulator 5 (SIRT5) is the fifth member of the sirtuin family, which is mainly expressed in mitochondrial matrix. SIRT5 plays a key role in metabolism and antioxidant responses, and is an important regulator for maintaining intracellular homeostasis. Given its involvement in multiple cellular processes, dysregulation of SIRT5 activity is associated with a variety of diseases. This review explores the structural characteristics of SIRT5 that influence its substrate specificity, highlights recent research advances, and summarizes its four key enzymatic activities along with their corresponding substrates in disease contexts. We also discuss the natural products that modulate SIRT5 activity and identify potential targets of SIRT5 through virtual docking, which may provide new therapeutic avenues. Although the mechanism of SIRT5 in diseases needs to be further elucidated and deglutathionylation activities are still at an early stage, targeting SIRT5 and its substrates holds significant promise for the development of novel therapeutics. Graphical abstract

Multi-omics and biochemical analyses provide insights into hepatic glucolipid metabolism in red tilapia (Oreochromis spp.) under salinity stress - Bingjie Jiang; Renshan Huang; Yifan Tao; Siqi Lu; Jixiang Hua; Yan Li; Yalun Dong; Pao Xu; Jun Qiang (Aquaculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Synergistic generation of ROS via covalent organic frameworks with excellent energy transfer and charge transfer characteristics for phenolic pollutants treatment - Long Zhang; Liujun Yang; Wanyu Wei; Shaoshuo Wang; Yicheng Pan; Yuhan Gu; Liren Gu; Chen Yu; Hua Li; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Encapsulation of Lacticaseibacillus rhamnosus and Staphylococcus xylosus using sodium alginate improves flavour and the nutritional value of pork broth - Chun-lei Lu; Hua-xiang Li; Fedrick C. Mgomi; Zhen-quan Yang (Food Bioscience, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Plasma-enhanced low-temperature SCO of NH3 over Cu-Mn/SAPO-34 catalyst under oxygen-rich conditions - Kai Li; Yuxuan Ding; Fada Feng; Weiqiang Shen; Yuzhen Jin; Liancheng Zhang; Zhiqiang Lu; Dandan Wang; Hua Pan; Xuming Zhang (Chemical Engineering Journal, 2025)

Simple and robust method for the quantification of nine organic acids in beer using 3-chloropropyl bonded C18 materials with HPLC-UV analysis - Yu Shi; Huifan Li; Yuqi Lu; Ming Chen; Hua Yang; Dongmei Fu (Systems Microbiology and Biomanufacturing, 2025)

Determination of 70 liquid crystal monomers in indoor gas-particle-dust multi-medium based on ultrasonic extraction coupled with comprehensive two-dimensional gas chromatography with time-of-flight mass spectrometry - Kai Hua; Jiahao He; Xingtong Li; Congyi Zheng; Lingrui Ji; Qingyan Wu; Xi Chen; Ke Gao; Wei Wei; Liping Lu (Analytica Chimica Acta, 2025)

Colorectal carcinoma organoid and cancer-associated fibroblasts co-culture system for drug evaluation - Yan Wang; Zilin Zhang; Xiaoran Li; Xiaobing Lu; Xuemei Zhuansun; Qiwei Li; Jing Zhang; Xi Xu; Xueqiang Liu; Yuan Wei; Feng Hua; Runda Wu; et al. (In vitro models, 2025)

Mink enteritis virus infection induced cell cycle arrest and autophagy for its replication - Dong Lu-jiao; Li Zhi-juan; Sun Ying-Li; Fan Hua; Li Wen-qian; Zhang Hui-ning; Peng Jun; Xie Zhi-jing (Veterinary Microbiology, 2025)

Pathogenic Aeromonas veronii with the cheZ-mshK-aerA triple-gene mutant is attenuated and exhibits a potential candidate as a live attenuated vaccine - Jiahui Lu; Jinming Wei; Kemei Liu; Detao Li; Ziyang Li; Yongyao Yu; Hua Ye; Yun Li; Hao Xu; Xiaoyi Pan; Ronghua Wu (Fish & Shellfish Immunology, 2025)

Experimental behaviour of concrete-filled double-skin corrugated steel tubes under combined compression and cyclic lateral loads - Bo Lu; Yong Fang; Yuyin Wang; Hua Yang; Hao Li (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Strengthening the anaerobic bioelectrochemical oxidation of ammonium by adding anthraquinone-2,6-disulfonate - Huahua Li; Yi Lu; Hua Chen; Xinyuan He; Haichun Gao; Shaoan Cheng (Chemical Engineering Journal, 2025)

Dietary bamboo vinegar powder improves growth performance, immunity, antioxidant capacity and lipid metabolism of largemouth bass (Micropterus salmoides) - Weibin Lai; Shuwen Xu; Ran Yu; Linyi Li; Yuanyi Zuo; Manqi Yang; Liangliang Zhang; Liming Lu; Yong Xu; Yiwen Liu; Hua Wang; Jianchun Jiang (Animal Feed Science and Technology, 2025)

Integration of transcriptome, histopathology, and physiological indicators reveals regulatory mechanisms of largemouth bass (Micropterus salmoides) in response to carbonate alkalinity stress - Jixiang Hua; Yifan Tao; Siqi Lu; Yan Li; Yalun Dong; Bingjie Jiang; Bingwen Xi; Jun Qiang (Aquaculture, 2025)

Typical pollutants in secondary water supply systems: Source, spread, and elimination - Gaolei Liu; Zhenghao Yan; Rongrong Mao; Lu Yu; Tao Hua; Fengxiang Li (Journal of Water Process Engineering, 2025)

A plant growth-promoting bacterium supports cadmium detoxification of rice by inducing phenylpropanoid and flavonoid biosynthesis - Yingjie Wu; Haiyang Zhao; Meijuan Xiao; Huimin Liu; Hua He; Lu Peng; Qi Tao; Xiaoyan Tang; Yanyan Zhang; Rong Huang; Bing Li; Changquan Wang (Journal of Hazardous Materials, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Regional disparities in PPCPs contamination of urban wastewater treatment plants: Unveiling influential factors and ecological effects - Xing Chen; Xiaofei Lu; Jiahua Peng; Guijin Su; Jing Meng; Qianqian Li; Yukang Hua; Ming Hu; Bin Shi (Environmental Pollution, 2025)

Highly electrostatic cellulose acetate materials assisted by copper ion coordination for air filtration - Ning Yan; Ting Gao; Li Hua; Fan Xie; Rui-Xin Liu; Ding-Gen Hu; Zhao-Qing Lu (Chemical Engineering Journal, 2025)

Construction and evaluation of PSMA and integrin α2β1 targeted hetero-bivalent agents for the PET imaging and internal irradiation therapy of prostate cancer - Xinmiao Lu; Wenbo Li; Chuang Xi; Fei Kong; Quanyong Luo; Hua Pang (Chemical Engineering Journal, 2025)

Epidemiology of liver diseases: global disease burden and forecasted research trends - Jia Xiao; Fei Wang; Yuan Yuan; Jinhang Gao; Lu Xiao; Chao Yan; Feifei Guo; Jiajun Zhong; Zhaodi Che; Wei Li; Tian Lan; Frank Tacke; et al. (Science China Life Sciences, 2025)

Application of 18β-glycyrrhetinic acid in the structural modification of natural products: a review - Wan-Xin Li; Ye-Fang Lu; Fei Wang; Bing Ai; Sheng-Bo Jin; Siqi Li; Guang-Hua Xu; Cheng-Hua Jin (Molecular Diversity, 2025)

AMPK activation by dietary acadesine improves fillet texture in large yellow croaker (Larimichthys crocea) fed a linseed oil-based diet - Shengdi Chen; Zihan Sun; Ningning Liu; Chenbin Yang; Na Li; Lu Li; Chaoqing Wei; Binlun Yan; Huan Gao; Peng Tan; Hua Mu (Aquaculture, 2025)

Purinergic signaling by TCRαβ+ double-negative T regulatory cells ameliorates liver ischemia–reperfusion injury - Hua Jin; Mingyang Li; Xiyu Wang; Lu Yang; Xinjie Zhong; Zihan Zhang; Xiaotong Han; Jingjing Zhu; Mengyi Li; Songlin Wang; Simon C. Robson; Guangyong Sun; et al. (Science Bulletin, 2025)

Simultaneous effects of nanoscale zero-valent iron on wastewater decontamination and energy generation: Mechanisms of sulfamethoxazole degradation and methanogenesis - Lingyun Zhou; Jibin Li; Xingcheng Lu; Weiming Zhang; Bingcai Pan; Ming Hua (Journal of Hazardous Materials, 2025)

Influencing factors analysis of infectious SARS-CoV-2 aerosols sampling - Yunfeng Chen; Jia Lu; Qingni Li; Wanlu Hua; Wenjin Zhang; Chunyang Li; Yuanlang Liu; Zejun Wang (Journal of Aerosol Science, 2025)

Rapid determination of total phenolic content and antioxidant capacity of maple syrup using Raman spectroscopy and deep learning - Li Xiao; Jinxin Liu; Marti Z. Hua; Xiaonan Lu (Food Chemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Conductive hydrogels with HPC additions for humidity sensing and temperature response - Lizhi Song; Wei‐Jing Chen; Jiarui Huang; Dinggen Hu; Xingxiang Ji; Li Hua; Zhaoqing Lu (Chemical Engineering Journal, 2025)

Thermal-responsive microgels incorporated PVA composite hydrogels: Integration of two-stage drug release and enhanced self-healing ability for chronic wound treatment - Zeying Liu; Huixia Li; Yalin Huang; Jie Li; Ruiying Dong; Xue Yun; Yuqian Ren; Xiaonan Liu; Hui Hui; Lei Wu; Ziwei Lu; Yali Cui; et al. (Chemical Engineering Journal, 2025)

Waxberry-liked micro-nanostructured, superhydrophobic surfaces with enhanced photothermal de-icing and passive anti-icing properties - Siyu Liu; Zhongzheng Zhu; Qitan Zheng; Kaifeng Wang; Feng Zhou; Qiuming Yang; Xinyi Wang; Lu Ye; Yujie Chen; Hezhou Liu; Hua Li (Chemical Engineering Journal, 2025)

Acute hypoxia causes glycolysis and lipid metabolism alterations with HSPs’ persistent activation in Leiocassis longirostris - Mengdan Hou; Zhenlin Ke; Mengbin Xiang; Lu Zhang; Yuejing Yang; Zhe Li; Wenbo Sun; Zhengshi Zhang; Jian Zhou; Hua Ye; Hui Luo (Ichthyological Research, 2025)

Dietary Probiotic Rhodopseudomonas palustris Formulation Improves Growth Performance, Muscle Composition, Digestive Enzyme Activity, Non-Specific Immunity and Disease Resistance of Juvenile Ivory Shell (Babylonia areolata) - Xiao Wang; Yao-Peng Lu; Ze-Long Zhang; Pei-Hua Zheng; Jun-Tao Li; Xiu-Xia Zhang; Jia-Jun Li; Heng-Mei Wu; Jian-An Xian (Fishes, 2024)
Rhodopseudomonas palustris (RP) are known anaerobic bacteria with probiotic properties containing several bioactive compounds and enzymes that benefit aquatic animals. However, studies on the use of RP on aquatic animal species are limited. This study investigated the effects of dietary supplementation with RP formulation on the growth, non-specific immunity, and disease resistance of juvenile ivory shells (Babylonia areolata). The experiment was conducted for 8 weeks, with B. areolata fed a control diet (RP0) and four diets containing four different RP formulations, with doses of 1 (RP1), 5 (RP2), 10 (RP3), and 20 (RP4) g/kg, respectively. Higher levels of R. palustris in the formulation led to increased final weight, weight gain, and specific growth rate in B. areolata. The crude protein content was significantly higher in the RP4 group compared to the RP0 group. However, there was no significant difference in the crude lipid content. Higher levels of R. palustris in the RP4 formulation group increased the trypsin and lipase activities. Dietary supplementation with RP significantly increased the total antioxidant capacity, superoxide dismutase, and catalase activities and decreased the malondialdehyde content in B. areolata. Acid phosphatase and alkaline phosphatase activities were significantly increased in the RP4 group compared to the RP0 group. Dietary RP significantly increased the expression levels of antioxidant-related (superoxide dismutase, Cu/Zn-superoxide dismutase, glutathione S-transferase A-like, ferritin) and immune-related (acid phosphatase, cytochrome c) genes. Higher levels of R. palustris in the formulations RP3 and RP4 increased the survival rate of B. areolata challenged with Vibrio parahaemolyticus. These findings indicate that R. palustris preparation could improve growth performance, muscle composition, and digestive capacity and may act as an immune booster for preventing disease in B. areolata.

Application of atomic force microscopy in the characterization of fruits and vegetables and associated substances toward improvement in quality, preservation, and processing: nanoscale structure and mechanics perspectives - Weinan Huang; Marti Z. Hua; Shenmiao Li; Kunsong Chen; Xiaonan Lu; Di Wu (Critical Reviews in Food Science and Nutrition, 2024)

MshK mutation reduces pathogenicity of Aeromonas veronii by modulating swimming ability, biofilm formation capacity, pili structure and virulence gene expression - Jiahui Lu; Jinming Wei; Kemei Liu; Bei Wang; Liping Zhang; Yongyao Yu; Yun Li; Hua Ye; Hong Li; Ronghua Wu (Aquaculture, 2024)

Inhibition of ATP1V6G3 prompts hepatic stellate cell senescence with reducing ECM by activating Notch1 pathway to alleviate hepatic fibrosis - Xiao-Pei Xue; Yu Sheng; Qi-Qi Ren; Shi-Meng Xu; Min Li; Zhao-Xiu Liu; Cui-Hua Lu (Tissue and Cell, 2024)

Blue carbon storage of tidal flats and salt marshes: A comparative assessment in two Chinese coastal areas - Jinge Zhou; Lulu Zhang; Jingfan Zhang; Shuchai Gan; Zhe Lu; Guoming Qin; Xingyun Huang; Han Chen; Hua He; Yongxing Li; Yingwen Li; Hui Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

A novel high-throughput quantitative method for the determination of per- and poly-fluoroalkyl substances in human plasma based on UHPLC-Q/Orbitrap HRMS coupled with isotope internal standard - Wenting Zhang; Qiuyan Lu; Huafeng Chen; Yuxiang Li; Yongyou Hua; Jing Wang; Fa Chen; Renjin Zheng (Journal of Hazardous Materials, 2024)

AmTPS6 promotes trehalose biosynthesis to enhance the Cd tolerance in mangrove Avicennia marina - Ling-Yu Song; Jing Li; Lu-Dan Zhang; Zhao-Yu Guo; Chao-Qun Xu; Li-Wei Jiang; Jin-Yu Liu; Ji-Cheng Wang; Qing-Hua Li; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2024)

Responses of depth-dependence of C:N:P stoichiometry to check dam in mangrove wetlands - Xingyun Huang; Fangyuan Guan; Yi Zhong; Yu Ni; Ruyi Ding; Guoming Qin; Jinge Zhou; Jingfan Zhang; Han Chen; Hua He; Yingwen Li; Yongxing Li; et al. (Journal of Environmental Management, 2024)

Rapid and sensitive detection of haloxyfop-P-methyl by competitive and noncompetitive immunoassays using phage-displayed peptides - Jiao Li; Panpan Cui; Zhijia Wang; Yang Lu; Yuan Ding; Xiude Hua (Food Bioscience, 2024)

Preparation and characterization of Chitosan based edible coating containing vanillin/HPβCD inclusion complex and its application in chicken preservation - Chen Peiyao; Hua Shuhao; Liu Yinxin; Li Cheng; Zhang Xinyi; Lu Xingmeng; Sun Cui; Sun Chongde; Lingxia Huang (Food Control, 2024)

Carboxymethyl chitosan/peach gum polysaccharide packaging film incorporating Citrus sinensis essential oil effectively enhances the quality preservation of strawberries - Maolin Liu; Chunjie He; Wendan Chen; Yushu Li; Ningwei Yang; Xuqing Chen; Jing Xue; Xian Wang; Anxiang Lu; Zongda Xu; Xiuhai Zhang; Lei Sun; et al. (Food Packaging and Shelf Life, 2024)

Fast preparing bioelectrode with conductive bioink for nitrite detection in high sensitivity and stability - Shaoan Cheng; Hua Chen; Huahua Li; Longxin Li; Yi Lu; Beichen Jin; Xinyuan He (Environmental Research, 2024)

A robust COF membrane on polyethylene support via ethanol-assisted self-assembly of COF nanosheets for efficient desalination - Xianjuan Zhang; Yu Zheng; Runnan Zhang; Hua Jin; Peng Lu; Hui Wang; Zhongyi Jiang; Yanshuo Li (Desalination, 2024)

Comparative Analysis of Seven Endogenous Hormones in a Novel Dual-axillary Bud Mutant Genotype of Sugarcane - Kamal Priyananda Wickramasinghe; Jun Mao; Chao-hua Xu; Xiu-qin Lin; Xu-juan Li; Wei Qin; Hong-bo Liu; Xin-long Liu; Faisal Mehdi; Pei-fang Zhao; Xin Lu (Sugar Tech, 2024)
The sugarcane genotype YZ 07-86 is a distinct natural mutant with dual-axillary buds. Exploitation of this valuable trait in sugarcane breeding requires an understanding of the physiological mechanism of dual-axillary bud formation. This experiment determined the contents of indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins (GA 3 and GA 4 ), and three cytokinins (CKs), namely isopentenyl adenosine (iPA), zeatin riboside (ZR), and dihydrozeatin riboside (DHZR), in the shoot apical meristem tissues of YZ 07-86 and its sister line YZ 07-87, which served as the control genotype. The field experiment followed a completely randomized design with three replications for each genotype. Sampling was done at 5-day intervals, starting 106 days after planting. The ELISA technique was used to measure the contents of endogenous hormones. The study revealed that the mean contents of IAA, GA 3 , GA 4 , DHZR, and iPA were not significantly different ( P > 0.05) among the genotypes. Conversely, in YZ 07-86, the mean ZR content was significantly higher ( P < 0.05), and the mean ABA content was significantly lower than in the control genotype. Moreover, the mean content ratios of ZR/IAA, ZR/ABA, ZR/GA 3 , and ZR/GA 4 were also significantly higher in YZ 07-86. The study concludes that elevated ZR content and an increased ZR/ABA ratio directly contributes to dual-axillary bud formation in YZ 07-86, offering valuable insights for the advancement of sugarcane genotypes.

Molecular cloning and gene expression of acc2 from grass carp (Ctenopharyngodon idella) and the regulation of glucose metabolism by ACCs inhibitor - Manxia Cao; Xinyuan Li; Lixue Dong; Hua Wen; Ming Jiang; Xing Lu; Feng Huang; Juan Tian (Molecular Biology Reports, 2024)

Peroxynitrite-Triggered Carbon Monoxide Donor Improves Ischemic Stroke Outcome by Inhibiting Neuronal Apoptosis and Ferroptosis - Xin-Jian Guo; Lin-Yan Huang; Shi-Tong Gong; Ming Li; Wan Wang; Jie Chen; Yi-De Zhang; Xicun Lu; Xiaohua Chen; Lan Luo; Youjun Yang; Xiao Luo; et al. (Molecular Neurobiology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Numerical Simulation of the Horizontal Water-Entry Process of High-Speed Vehicles - Jin-Long Ju; Na-Na Yang; Yi-Fei Zhang; Lei Yu; Zhe Zhang; Liang-Chao Li; Guo-Lu Ma; Wen-Hua Wu (Journal of Marine Science and Engineering, 2024)
Based on the RNG k-ε turbulence model and VOF multiphase flow model, a numerical model of horizontal water-entry of the vehicle was established, and the numerical method was verified by experimental results. The cavitation characteristics, fluid resistance, and motion of the vehicle under different conditions were studied during the vehicle’s water-entry process. The results show that the cavitation process can be divided into the cavity development stage, saturation stage, and collapse stage. With the increase in initial velocity and mass of the vehicle, more water vapor will be generated during the water-entry process. The initial velocity of the vehicle had a limited effect on the resistance coefficient. The resistance coefficient in the stable stage remained almost unchanged for vehicles with different masses. Nevertheless, the time interval of the stable stage was shortened, and the resistance coefficient was greater in the gradually increasing stage for the vehicle with a smaller mass. For vehicles with higher initial velocity or smaller mass, the instantaneous velocity decreased faster after it entered the water. The vehicle with a streamlined design was able to reduce the generation of water vapor and decrease fluid resistance and its coefficient, and the vehicle can run farther during the water-entry process.

Occurrence and risks of PPCPs of a typical mountainous region: Implications for sustainable urban water systems - Xing Chen; Xiaofei Lu; Renxin Zhao; Guijin Su; Jing Meng; Qianqian Li; Yukang Hua; Bin Shi (Science of The Total Environment, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Response of soil gross nitrogen mineralization to fertilization practices in China's uplands - Jun Wang; Yinghua Duan; Guanmo Li; Lu Zhang; Dejin Li; Kailou Liu; Xi'an Cui; Boku Zhou; Hongjun Gao; Xiaori Han; Junyong Ma; Shutang Liu; et al. (Journal of Cleaner Production, 2024)

Oral administration of recombinant Lactococcus lactis expressing largemouth bass (Micropterus salmoides) IFNa3 protein enhances immune response against largemouth bass virus (LMBV) infection - Xiaojing Hua; Chen Li; Yuncai Xiao; Yuanan Lu; Xueqin Liu (Fish & Shellfish Immunology, 2024)

Programmed DNA tile response system enabled accurate detection of ATP for clinical diagnosis - Dongxia Li; Yanan Peng; Liangqing Lu; Delun Chen; Bingrong Wang; Qiumei Pu; Qionglin Zhou; Xinxin Xiao; Mingpeng Fu; Xiaohong Wang; Jinchun Tu; Hua Pei; et al. (Chemical Engineering Journal, 2024)

Enhanced removal of nanoplastics from freshwater using in-situ synthesized and anchored nano-Fe3O4 via two-step ferrous oxidation - Jiarong Li; Yan Zhang; Cuiyun Zeng; Qiang Xiong; Hua Zhang; Qiaohui Guo; Lu Wang; Jun Ma; Shuiliang Chen (Chemical Engineering Journal, 2024)

High-performance circularly polarized electroluminescence UV-OLED based on hot exciton molecules with preferred horizontal dipole orientation - Sinuo Geng; Min Wang; Huihui Li; Hua Lu; Zujin Zhao; Xin Jiang Feng (Chemical Engineering Journal, 2024)

Fate of soil organic carbon in estuarine mangroves: Evidences from stable isotopes and lignin biomarkers - Guoming Qin; Zhe Lu; Shuchai Gan; Lulu Zhang; Jingfan Zhang; Jinge Zhou; Ruyi Ding; Xingyun Huang; Han Chen; Hua He; Mengxiao Yu; Hui Li; et al. (CATENA, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

Hohaiivirga grylli gen. nov., sp. nov., a New Member of the Family Methylobacteriaceae, Isolated from Cricket (Gryllus chinensis) - Hong-Chuan Wang; Meng-Han Huang; Dan-Yuan Guo; Wei He; Lu Wang; Zi-Yue Fu; Wen-Jun Li; Ai Hua Zhang; Dao-Feng Zhang (Current Microbiology, 2024)

Strap-on Buoyant Device to Enhance Gastrointestinal Tract Retention of Felodipine Osmotic Pump Tablets - Qijia Ni; Zeru Li; Libumo Baqing; Tianfu Li; Huipeng Xu; Falan Li; Ningning Peng; Caifen Wang; Jianhua Lu; Zhigang Wang; Kai Wang; Chao Jiang; et al. (AAPS PharmSciTech, 2024)

SESN2 Ameliorates Dihydrotestosterone-induced Human Ovarian Granulosa Cell Damage by Activating AMPK/ULK1-mediated Mitophagy - Xiaojing Hua; Qing Lu; Li Zeng (Cell Biochemistry and Biophysics, 2024)

Enhancing the nitrogen removal of anammox sludge by setting up novel redox mediators-mediated anammox process - Huahua Li; Hua Chen; Xinyuan He; Yi Lu; Haichun Gao; Hao Song; Shaoan Cheng (Chemosphere, 2024)

The role and function mechanism of tapP in modulating the virulence of Aeromonas hydrophila - Rui Long; Jinming Wei; Caijiang Xiong; Bei Wang; Jiahui Lu; Hua Ye; Yun Li; Yongyao Yu; Lingyun Lin; Ronghua Wu (Aquaculture, 2024)

Particle-ozone complex pollution under diverse synoptic weather patterns in the Yangtze River Delta region: Synergistic relationships and the effects of meteorology and chemical compositions - Yangzhihao Zhan; Min Xie; Bingliang Zhuang; Da Gao; Kuanguang Zhu; Hua Lu; Tijian Wang; Shu Li; Mengmeng Li; Yi Luo; Runqi Zhao (Science of The Total Environment, 2024)

BrARR10 contributes to 6-BA-delayed leaf senescence in Chinese flowering cabbage by activating genes related to CTK, GA and ABA metabolism - Ci-mei Wang; Ze-xiang Zeng; Zong-li Liu; Jian-hua Zhu; Xin-guo Su; Ri-ming Huang; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Ying-ying Yang (Postharvest Biology and Technology, 2024)

A combined experimental and theoretical study on the mechanism of catalytic oxidation of lignite to carboxylic acids by iron - Jiao-Xuan Bai; Cong Xu; Jie-Ping Wang; Rui Guo; Wei-Ze Wu; Ting Lu; Guang-Yue Li; Ying-Hua Liang (Fuel, 2024)

The role of aroA and ppk1 in Aeromonas veronii pathogenicity and the efficacy evaluation of mutant strain AV-ΔaroA/ppk1 as a live attenuated vaccine - Jiahui Lu; Wan'e Ding; Jinming Wei; Hua Ye; Hui Luo; Yun Li; Ying Lin; Yongyao Yu; Jiayun Yao; Ronghua Wu (Fish & Shellfish Immunology, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Quantitative analysis of aeolian dust incidence and diagnosis using a dynamic Bayesian network model: A case study of estuary area in central Taiwan - Yung-Chieh Wang; Kao-Hua Chang; Tse-Yang Hsu; Yu-Hsin Lu; Li-Chi Chiang (Atmospheric Environment, 2024)

Effect of Foliar Application of Selenite On Organic Se and Antioxidant Activity in Kiwifruit - Yun-mei Lu; Mao Mu; Li-ai Wang; Ren-hua Huang (Applied Fruit Science, 2024)

Encapsulation of lycopene in Pickering emulsion stabilized by complexes of whey protein isolate fibrils and sodium alginate: Physicochemical property, structural characterization and in vitro digestion property - Qiaomei Zhu; Yihua Qiu; Lujia Zhang; Wenjing Lu; Yijun Pan; Xuanbo Liu; Zhenjing Li; Hua Yang (Food Research International, 2024)

Protective layer constructed by liquid phase quenching for long lifespan potassium ion batteries - Shedong Li; Lu-Kang Zhao; Yu-Hua Bian; Hong Chen; Xuan-Wen Gao; Yingying Song; Zhaomeng Liu; Wen-Bin Luo (Chemical Engineering Journal, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Ultrastructure of the larval rectum of the scorpionfly Panorpa liui (Mecoptera: Panorpidae) - Wan-Ruo Ma; Lu Liu; Ge Wang; Jia-Li Bai; Bao-Zhen Hua (Arthropod Structure & Development, 2024)

Dietary chitosan reversed the toxic effects of polystyrene microplastics on Nile tilapia (Oreochromis niloticus) liver by inhibiting mitochondrial damage - Di Wu; Xing Lu; Li-Xue Dong; Juan Tian; Hua Wen; Shan Zhong; Yun-feng Li; Ming Jiang (Reviews in Fish Biology and Fisheries, 2024)

Overexpression of the MiAGL1 gene from mango promoted flowering in transgenic Arabidopsis - Xue-mei Zeng; Xin-hua He; Wen-jing Mo; Hai-xia Yu; Ting-ting Lu; Li-ming Xia; Yi-li Zhang; Jia-wei Zhu; Cong Luo (Journal of Plant Biochemistry and Biotechnology, 2024)

Replacing soybean meal with fermented rapeseed meal in diets: potential effects on growth performance, antioxidant capacity, and liver and intestinal health of juvenile tilapia (Oreochromis niloticus) - Yaxue Li; Xing Lu; Lixue Dong; Di Peng; Jianmin Zhang; Zongbin Cui; Hua Wen; Juan Tian; Ming Jiang (Fish Physiology and Biochemistry, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Fiddler crab bioturbation stimulates methane emissions in mangroves: Insights into microbial mechanisms - Guoming Qin; Zhe Lu; Shuchai Gan; Lulu Zhang; Jingtao Wu; Christian J. Sanders; Zhili He; Xiaoli Yu; Jingfan Zhang; Jinge Zhou; Ruyi Ding; Xingyun Huang; et al. (Soil Biology and Biochemistry, 2024)

Rapid and sensitive quantitation of amitraz in orange, tomato, and eggplant samples using immunochromatographic assay - Qianqian Lu; Liqiang Liu; Jinyan Li; Shanshan Song; Hua Kuang; Chuanlai Xu; Lingling Guo (Food Chemistry, 2024)

Dietary cholesterol intervention could alleviate the intestinal injury of Oreochromis niloticus induced by plant-based diet via the intestinal barriers - Jiayuan Jiang; Xing Lu; Li-Xue Dong; Di Peng; Jian-Min Zhang; Juan Tian; Hua Wen; Ming Jiang (Fish & Shellfish Immunology, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Comparative transcriptomics and metabolomics reveal specific biochemical responses in cultured largemouth bass (Micropterus salmoides) juveniles with sexual dimorphism - Yan Li; Jixiang Hua; Yifan Tao; Siqi Lu; Yalun Dong; Bingjie Jiang; Qingchun Wang; Jun Qiang; Pao Xu (Aquaculture, 2024)

Dynamics of antibiotic resistance genes in the sediments of a water-diversion lake and its human exposure risk behaviour - Yuanyuan Liu; Kejian Chu; Zulin Hua; Qiming Li; Ying Lu; Fuzhu Ye; Yueyang Dong; Xiaoqing Li (Science of The Total Environment, 2024)

Neoarchean clockwise P-T trajectories with evolution sequence from HP to UHT metamorphism during decompression: Evidence from petrology, mineralogy, and phase equilibria modeling of mafic granulites in the Sittampundi Complex, southern India - Xu Kong; Jun-Sheng Lu; Ming-Guo Zhai; Cheng-Li Zhang; M.P. George; Long-Long Gou; Yan Zhao; Wen-Hao Ao; Yu-Hua Hu; Qiang Feng; Gang Liu (Precambrian Research, 2024)

Anti-inflammatory activity of organic acids from the seeds of Phaseolus lunatus L. - Kun Li; Jin-hui Bian; Heng Wu; Ya-lan Wang; Yun-jia Feng; Jia Nie; Na Chen; Han Yu; Wan Li; Yu-zhu Tan; Guang-hua Lu (Phytochemistry Letters, 2024)

Turbulent transports in the flow around a rectangular cylinder with different aspect ratios - Jiang-hua Li; Bo-fu Wang; Xiang Qiu; Quan Zhou; Shi-xiao Fu; Yu-lu Liu (Ocean Engineering, 2024)

Comparative steroidogenic effects of hexafluoropropylene oxide trimer acid (HFPO-TA) and perfluorooctanoic acid (PFOA): Regulation of histone modifications - Fuping Li; Rui Yang; Lu Lu; Weizhen Hua; Yan Sun; Meiping Tian; Yanyang Lu; Qingyu Huang (Environmental Pollution, 2024)

Chitosan-based injectable hydrogel with multifunction for wound healing: A critical review - Aiqin Li; Bin Ma; Shiyao Hua; Rui Ping; Lu Ding; Bingren Tian; Xu Zhang (Carbohydrate Polymers, 2024)

Characterization of the complete mitochondrial genome of Ergasilus anchoratus Markevich, 1946 (Ergasilidae) and phylogeny of Copepoda - Cong-jie Hua; Yan Huang; Hui-quan Li; Jin-mei Feng; Jia-lu Qiao; Song Hu; Wei Liu; Xi-ji Shu (Systematic Parasitology, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Pivotal role of intracellular oxidation by HOCl in simultaneously removing antibiotic resistance genes and enhancing dewaterability during conditioning of sewage sludge using Fe2+/Ca(ClO)2 - Xinxin Wang; Yu Lu; Yiwen Yan; Ru Wang; Yuhang Wang; Hua Li; Lixiang Zhou; Guanyu Zheng; Yifeng Zhang (Water Research, 2024)

Integration of transcriptome, gut microbiota, and physiology reveals toxic responses of the red claw crayfish (Cherax quadricarinatus) to imidacloprid - Yao-Peng Lu; Jia-Han Liu; Xiu-Xia Zhang; Chi Xu; Pei-Hua Zheng; Jun-Tao Li; Jia-Jun Li; Dong-Mei Wang; Jian-An Xian; Ze-Long Zhang (Journal of Hazardous Materials, 2024)

Environmental cadmium inhibits testicular testosterone synthesis via Parkin-dependent MFN1 degradation - Tian-Tian Wang; Hua-Long Zhu; Kong-Wen Ouyang; Hua Wang; Ye-Xin Luo; Xin-Mei Zheng; Qing Ling; Kai-Wen Wang; Jin Zhang; Wei Chang; Qi Lu; Yu-Feng Zhang; et al. (Journal of Hazardous Materials, 2024)

E-eye and FT-NIR combined with multivariate algorithms to rapidly evaluate the dynamic changes in the quality of Gastrodia elata during steaming process - Jiu-ba Zhang; Bin Wang; Yun-fei Zhang; Yi Wu; Ming-xuan Li; Ting Gao; Tu-lin Lu; Zhen-hua Bian; Lian-lin Su (Food Chemistry, 2024)

Emergence of blaNDM-5–bearing IncHI2/ST2 and p0111 multidrug-resistance plasmids and widespread distribution of IncHI2/ST3–blaNDM-5 plasmids across foods, animals, and humans - Lu-Chao Lv; Cheng-Zhen Wang; Jing-Jing Yu; Yan-Xiang Jiao; Li-Min Deng; Wan-Yun He; Guo-Long Gao; Xiao-Yu Zhang; Li-Tao Lu; Xun Gao; Yi-Yun Liu; Jian-Hua Liu (Food Control, 2024)

Grafting small organic molecules on donor-acceptor polymers to regulate electron push-pull interactions for efficient H2O2 production - Shuang Zhao; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu; Dongyun Chen (Chemical Engineering Journal, 2024)

A quaternary ammonium cyclodextrin polymer for efficient photocatalytic production of hydrogen peroxide from pure water - Bingshu Jiang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2024)

Population pharmacokinetics of rivaroxaban in Chinese deep vein thrombosis patients and the exposure simulation for dosing recommendation - Ze Li; Siyu Yang; Zixin Hua; Yanxia Lu; Xingang Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Emergence of a clinical Salmonella enterica serovar 1,4,[5], 12: i:-isolate, ST3606, in China with susceptibility decrease to ceftazidime-avibactam carrying a novel blaCTX-M-261 variant and a blaNDM-5 - Jie Wei; Shimei Shen; Qinghuan Zhang; Jinping Lu; Shenglan Mao; Chunhong Zou; Hua Zhou; YeLin Wei; Xingyi Ou; Jinyu Huang; Deqiang Wang; Xiaobin Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The detection rate of Salmonella enterica serovar 1,4,[5], 12: i: - (S. 1,4,[5], 12: i: -) has increased as the most common serotype globally. A S . 1,4,[5], 12: i: - strain named ST3606 (sequence type 34), isolated from a fecal specimen of a child with acute diarrhea hospitalized in a tertiary hospital in China, was firstly reported to be resistant to carbapenem and ceftazidime-avibactam. The aim of this study was to characterize the whole-genome sequence of S. 1,4,[5], 12: i: - isolate, ST3606, and explore its antibiotic resistance genes and their genetic environments. Methods The genomic DNA of S. 1,4,[5], 12: i: - ST3606 was extracted and performed with single-molecule real-time sequencing. Resistance genes, plasmid replicon type, mobile elements, and multilocus sequence types (STs) of ST3606 were identified by ResFinder 3.2, PlasmidFinder, OriTfinder database, ISfinder database, and MLST 2.0, respectively. The conjugation experiment was utilized to evaluate the conjugation frequency of pST3606-2. Protein expression and enzyme kinetics experiments of CTX-M were performed to analyze hydrolytic activity of a novel CTX-M-261 enzyme toward several antibiotics. Results Single-molecule real-time sequencing revealed the coexistence of a 109-kb IncI1-Iα plasmid pST3606-1 and a 70.5-kb IncFII plasmid pST3606-2. The isolate carried resistance genes, including bla NDM-5 , sul1 , qacE , aadA2 , and dfrA12 in pST3606-1, bla TEM-1B , aac (3)- lld , and bla CTX-M-261 , a novel bla CTX-M-1 family member, in pST3606-2, and aac (6')- Iaa in chromosome. The bla CTX-M-261 was derived from bla CTX-M-55 by a single-nucleotide mutation 751G>A leading to amino acid substitution of Val for Met at position 251 (Val251Met), which conferred CTX-M increasing resistance to ceftazidime verified by antibiotics susceptibility testing of transconjugants carrying pST3606-2 and steady-state kinetic parameters of CTX-M-261. pST3606-1 is an IncI1-α incompatibility type that shares homology with plasmids of pC-F-164_A-OXA140, pE-T654-NDM-5, p_dm760b_NDM-5, and p_dmcr749c_NDM-5. The conjugation experiment demonstrated that pST3606-2 was successfully transferred to the Escherichia coli recipient C600 with four modules of OriTfinder. Conclusion Plasmid-mediated horizontal transfer plays an important role in bla NDM-5 and bla CTX-M-261 dissemination, which increases the threat to public health due to the resistance to most β-lactam antibiotics. This is the first report of bla CTX-M-261 and bla NDM-5 in S. 1,4,[5], 12: i: -. The work provides insights into the enzymatic function and demonstrates the ongoing evolution of CTX-M enzymes and confirms urgency to control resistance of S . 1,4,[5], 12: i: -.

Methylated derivatives of polycyclic aromatic hydrocarbons in road dust, green belt soil and parking lot dust: occurrence, spatial distribution and emission sources - Jin-Nong Li; Ye Zhang; Jian-Xin Wang; Jie Hu; Xi-Mei Lu; Wen-Xi Xie; Zi-Feng Zhang; Zhong-Hua Tang (Environmental Geochemistry and Health, 2024)

A novel method for identifying aerobic granular sludge state using sorting, densification and clarification dynamics during the settling process - Zhi-Hua Li; Ruo-Lan Wang; Meng Lu; Xin Wang; Yong-Peng Huang; Jia-Wei Yang; Tian-Yu Zhang (Water Research, 2024)

Emergence of tet(X4)-positive Enterobacterales in retail eggs and the widespread of IncFIA(HI1)-HI1A-HI1B(R27) plasmids carrying tet(X4) - Chao Yue; Yuman Bai; Tong Li; Haotian Deng; Litao Lu; Wannan Lin; Xiaoxiao Cui; Luchao Lv; Guolong Gao; Jian-Hua Liu; Yi-Yun Liu (International Journal of Food Microbiology, 2024)

Coculturing of non-Saccharomyces cerevisiae and Saccharomyces cerevisiae for improving the aroma quality and antioxidant characteristics of beer with Yuan'an yellow tea - Dianhui Wu; Ziqiang Chen; Yongxuan Lv; Lixia Yang; Hua Liu; Ran Qiu; Hengde Xu; Jianbo Li; Jian Lu; Guolin Cai (Food Bioscience, 2024)

Effects of antimicrobial peptides from dietary Hermetia illucens larvae on the growth, immunity, gene expression, intestinal microbiota and resistance to Aeromonas hydrophila of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yong-Qi Meng; Jia-Jun Li; Xiu-Xia Zhang; Jun-Tao Li; Jia-Rui Xu; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Spatiotemporal evolution of county level ecological security based on an emergy ecological footprint model: The case of Dingxi, China - Yanhua Lu; Lijuan Yan; Jie Li; Yunliang Liang; Chuanjie Yang; Guang Li; Jiangqi Wu; Hua Xu (Ecological Modelling, 2024)

Hazardous potential assessment of airborne and foodborne polyvinyl alcohol and polyhydroxyalkanoates nanoplastics: Comparison with polyvinyl chloride nanoplastics - Hua Zha; Qian Li; Qiangqiang Wang; Yaqi Zhang; Haifeng Lu; Lanjuan Li (Chemical Engineering Journal, 2024)

A refined full-spectrum temperature-induced subsurface thermal expansion model and its contribution to the vertical displacement of global GNSS reference stations - Zhao Li; Ran Lu; Weiping Jiang; Danan Dong; Jintao Lei; Yang Lu; Xin Ding; Kaichun Yang; Hua Chen; Qusen Chen (Journal of Geodesy, 2024)

On the contributions of refined thermal expansion model to nonlinear variations in different GNSS height time series products - Ran Lu; Zhao Li; Qusen Chen; Xin Ding; Kaichun Yang; Mingyuan Zhang; Yang Lu; Wenlan Fan; Hua Chen; Weiping Jiang (GPS Solutions, 2024)

Effects of Dietary Fish Meal Replaced by Cottonseed Protein Concentrate on Growth Performance, Antioxidant Capacity, and Liver and Intestinal Health of Juvenile Hybrid Culter - Guangming Xu; Huijie Wei; Di Peng; Lang Zhang; Xing Lu; Qing Li; Lixue Dong; Juan Tian; Hua Wen; Guiying Wang; Ming Jiang (Fishes, 2024)
The objective of this study was to assess the impact of concentrated cottonseed protein (CPC) as a substitute for fishmeal (FM) in juvenile hybrid culter (Erythroculter ilishaeformis ♀ × Ancherythroculter nigrocauda ♂). A total of 360 fish with an initial body weight of 10.0 ± 0.5 g were randomly allocated into 12 indoor culture tanks, with each tank containing 30 fish. Four diets were formulated in which fish meal (FM) was replaced by CPC at different inclusion levels: 0% (T0), 15% (T15), 30% (T30), and 45% (T45). The corresponding amounts of CPC included were 0, 61, 122, and 182 g/kg, respectively. At the end of the 10-week feeding trial, the findings revealed an inverse correlation between the proportion of CPC replacing FM and both final body weight (FBW) and weight growth rate (WG) in hybrid culter. Specifically, the T30 and T45 groups exhibited significantly lower FBW and WG compared to the T0 group (p 0.05). However, the crude lipid content was highest in hybrid culter fed the T45 diet and lowest in the T0 group (p 0.05). The contents of total protein (TP) and albumin (ALB) declined slightly as the proportion of FM substituted by CPC increased, yet this decline did not reach statistical significance (p > 0.05). Serum alanine aminotransferase (ALT) activity elevated with increasing dietary CPC, and the T45 group exhibited significantly higher ALT activity compared to the T0 group (p

Chang’e-5 basalt-like non-KREEP young lunar meteorite - Jing-Yao Xu; Qiu-Li Li; Kai Lu; Xian-Hua Li (Science Bulletin, 2024)

Nano polystyrene microplastics could accumulate in Nile tilapia (Oreochromis niloticus): Negatively impacts on the intestinal and liver health through water exposure - Di Wu; Xing Lu; Li-Xue Dong; Juan Tian; Jin Deng; Lei Wei; Hua Wen; Shan Zhong; Ming Jiang (Journal of Environmental Sciences, 2024)

Nanoparticle encapsulation using self-assembly abietic acid to improve oral bioavailability of curcumin - Ying Han; Hua Zhang; Haitian Zhao; Shiyao Fu; Ruiling Li; Zhili Wang; Yangxin Wang; Weihong Lu; Xin Yang (Food Chemistry, 2024)

Multi-comparted microgels delivering human derived probiotics and deferoxamine for multidrug-resistant infection and healing - Chao Hua; Fengbo Yang; Xiaoli Jia; Yichi Lu; Xiaoxiao Li; Peng Zhao; Malcolm Xing; Guozhong Lyu (Chemical Engineering Journal, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Synergistic mechanisms between chlorine-mediated electrochemical advanced oxidation and ultraviolet light for ammonia removal - Qiangang Li; Guo-hua Liu; Hongbiao Du; Guang Xian; Lu Qi; Hongchen Wang (Journal of Environmental Management, 2024)

Emergence of plasmid-mediated high-level tigecycline resistance gene tet(X4) in Enterobacterales from retail aquatic products - Yi-Yun Liu; Litao Lu; Chao Yue; Xun Gao; Jiakuo Chen; Guolong Gao; Kexin Li; Haotian Deng; Jian-Hua Liu (Food Research International, 2024)

Microbiota-accessible carbohydrates enhance the biological properties and promote colonization of Lactiplantibacillus plantarum ZDY2013 in the intestinal tract of weaned rats - Jinmei Li; Kaisheng Shao; Na Zhang; Jinlin Lu; Zhihong Zhang; Hua Wei (Food Bioscience, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Effects of dietary chitosan oligosaccharide on the growth, intestinal microbiota and immunity of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yan-Lei Cao; Jia-Rui Xu; Xiu-Xia Zhang; Jia-Jun Li; Jun-Tao Li; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Environmental-friendly enzyme nanoreactors with high adsorption capacity for long-time and efficient treatment of pollutants under visible light irradiation - Shuting Huang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2024)

Effect of exposures to multiple metals on blood pressure and hypertension in the elderly: a community-based study - Wen-lei Hu; Wei Xiao; Wen-bin Shen; Yue-yang Wu; Xue Li; Qi Zhong; Guo-ao Li; Huan-huan Lu; Jian-jun Liu; Zhi-hua Zhang; Fen Huang (BioMetals, 2024)

Human milk oligosaccharides and the association with microbiota in colostrum: a pilot study - Wen Sun; Lin Tao; Chen Qian; Peipei Xue; Xiankun Tong; Li Yang; Fang Lu; Hua Wan; Yingna Tao (Archives of Microbiology, 2024)
HMOs (Human milk oligosaccharide) has an impact on maternal and infant health. Colostrum samples of 70 breastfeeding women in China were collected and recorded clinical characteristics. The major oligosaccharides and microbiota were quantitated in colostrum. The concentration of fucosylated HMOs in primipara was higher than that of multipara ( p = 0.030). The concentration of N-acetylated HMOs in vaginal delivery milk was less than that of cesarean ( p = 0.038). Non-fucosylated HMOs of breastfeeding women were less than that of breast pump ( p = 0.038). Meanwhile, the concentration of LNT was positively correlated with Lactobacillus ( r = 0.250, p = 0.037). DS-LNT was negatively correlated with Staphylococcus ( r = – 0.240, p = 0.045). There was a positive correlation of Streptococcus with LNFP II ( r = 0.314, p = 0.011) and 3-SL ( r = 0.322, p = 0.009). In addition, there was a negative correlation between 2'-FL and 3-FL ( r = – 0.465, p = 0.001). There was a positive correlation between LNT and LNnT ( r = 0.778, p = 0.001). Therefore, the concentration of HMOs is related to number of deliveries, delivery mode, lactation mode and perinatal antibiotic. The concentration of HMOs is related to Lactobacillus , Streptococcus and Streptococcus in colostrum. In addition, there are connections between different oligosaccharides in content. The study protocol was also registered in the ClinicalTrails.gov (ChiCTR2200064454) (Oct. 2022).

Laccase-evoked removal of antibiotics: Reaction kinetics, conversion mechanisms, and ecotoxicity assessment - Kai Sun; Mei-Hua Chen; Xue-Min Qi; Dan Hong; Ling-Zhi Dai; Shun-Yao Li; Yi-Chen Lu; Han-Qing Yu (Critical Reviews in Environmental Science and Technology, 2024)

Synergistic removal performance and mechanism of Cd(II) and As(III) from irrigation water by iron sulfide-based porous biochar - Yuxi Lu; Honghu Zeng; Hua Lin; Yanpeng Liang; Mi Feng; Zijian Zhou; Zihao Liang; Huawei Li; Gongning Chen (Environmental Science and Pollution Research, 2024)

Sirtuin 3-mediated deacetylation of superoxide dismutase 2 ameliorates sodium fluoride-induced mitochondrial dysfunction in porcine oocytes - Xin-Yue Qi; Jin-Dong Yuan; Zi-Yu Liu; Xi-Qing Jiang; Qi Zhang; Shan-Long Zhang; Lu Zhao; Ling-Yan Ke; Chen-Yuan Zhang; Yan Li; Lu-Yan Zhang; Qian-Qian Xu; et al. (Science of The Total Environment, 2024)

Modulating the microenvironment of catalytic interface with functional groups for efficient photocatalytic degradation of persistent organic pollutants - Yujun Ju; Ze Wang; Hailong Lin; Ruien Hou; Hua Li; Zhe Wang; Ruitong Zhi; Xiaoquan Lu; Yu Tang; Fengjuan Chen (Chemical Engineering Journal, 2024)

Home environment exposure and sick building syndrome (SBS) symptoms among adults in southern China: Health associations in 2010 and 2019 - Hong Cheng; Dan Norbäck; Huilin Zhang; Liu Yang; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; et al. (Building and Environment, 2024)

Prediction Model of the Sound Speed of Seafloor Sediments on the Continental Shelf of the East China Sea Based on Empirical Equations - Guangming Kan; Junjie Lu; Xiangmei Meng; Jingqiang Wang; Linqing Zhang; Guanbao Li; Baohua Liu; Qingfeng Hua; Mujun Chen (Journal of Marine Science and Engineering, 2023)
Based on the data of the acoustic and physical properties of seafloor sediments obtained on the continental shelf area of the East China Sea (ECS), prediction equations of the sediment sound speed based on single and dual parameters were established, and the correlation of the sound speed with physical parameters was discussed. The results show that the sediment sound speed (c) is strongly correlated with water content (w), density (ρ), void ratio (e), mean grain size (Mz) and median grain size (Md), and the coefficient of determination R2 of the empirical regression equation is generally greater than 0.80, while the empirical regression equation coefficient of determination R2 of the compression coefficient (a) and compression modulus (E) are slightly lower, with 0.79 and 0.73, respectively. The coefficients of determination of the dual parameter regression equations between sediment sound speed with physical property parameters are generally higher than those of the single parameter equations, which are all higher than 0.90 indicating better prediction performance. The sensitivity of the physical parameters to the sound speed was analyzed, and the result shows that the sequence of sensitivity from high to low influence on sediment sound speed is void ratio, density, compressibility coefficient, median grain size and mean grain size. The prediction equations established in this study are a good extension and supplement to marine geoacoustic models and is of great significance for obtaining the acoustic properties of the seafloor sediments on the shelf of the East China Sea.

A systematic review on the recent advances of wheat allergen detection by mass spectrometry: future prospects - Yingjun Lu; Hua Ji; Yan Chen; Zhenxing Li; Vaileth Timira (Critical Reviews in Food Science and Nutrition, 2023)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

The effects of Spinosad on zebrafish larvae and THP-1 cells: Associated with immune cell damage and NF-kappa B signaling pathway activation - Wei-Guo Wang; Shou-Qian Xiong; Jin Lu; Lian-Hua Zhu; Cheng Zhang; Jia-Gao Cheng; Zhong Li; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Chemosphere, 2023)

Collagen hydrolyzed extract derived from leather waste as a multifunctional additive for the preparation of granular fertilizer - Hua Chen; Yi Li; Hanzheng Dai; Lu Chen; Xiaoliang Ding; Zhijun Hu (Sustainable Chemistry and Pharmacy, 2023)

Graphene aerogel-doped CoFe2O4/MoS2 sheets for magnetic oil absorption and the degradation of contaminants - Xin Xiang; Wenxuan Deng; Zhiyi He; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Journal of Environmental Chemical Engineering, 2023)

Metagenomic analysis of the relationship between microorganisms and flavor development during soy sauce fermentation - Hua Liu; Ziqiang Chen; Mingtao Ma; Yongxin Zhang; Dingding Li; Jian Lu; Xingguang Chen (Food Bioscience, 2023)

Hydrogen production and CO2 capture from Linz-Donawitz converter gas via a chemical looping concept - Huicong Zuo; Chunqiang Lu; Lei Jiang; Xianming Cheng; Zhiqiang Li; Yuelun Li; Danyang Li; Hua Wang; Kongzhai Li (Chemical Engineering Journal, 2023)

Insights into the adsorptive separation of iron from pickling waste acid: The overlooked role of FeCl3 species - Ling Yuan; Mujian Xu; Rongming Xu; Chenghan Ji; Hailun Yang; Hang Yu; Xiaoyang Li; Ming Hua; Lu Lv; Weiming Zhang (Chemical Engineering Journal, 2023)

Simultaneous mitigating the bioavailability of cadmium and arsenic in paddy soil by two carbon-iron composites: A field-scale evaluation - Gongning Chen; Yuxi Lu; Mi Feng; Hua Lin; Yanpeng Liang; Zijian Zhou; Zihao Liang; Huawei Li; Honghu Zeng (Bioresource Technology Reports, 2023)

Analyzing the cellular and molecular atlas of ovarian mesenchymal cells provides a strategy against female reproductive aging - Longzhong Jia; Wenji Wang; Jing Liang; Shudong Niu; Yibo Wang; Jian Yang; Lingyu Li; Ge Wang; Xueqiang Xu; Lu Mu; Kaixin Cheng; Xuebing Yang; et al. (Science China Life Sciences, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Numerical simulation of flow instability induced by a fixed cylinder placed near a plane wall in oscillating flow - Zi-Fang Li; Jiang-Hua Li; Jian-Zhao Wu; Kai-Leong Chong; Bo-Fu Wang; Quan Zhou; Yu-Lu Liu (Ocean Engineering, 2023)

The hidden indirect environmental effect undercuts the contribution of crop nitrogen fertilizer application to the net ecosystem economic benefit - Quanfeng Yang; Junhua Ma; Fei Yang; Hua Zheng; Zengbin Lu; Fei Qiao; Kening Zhang; Huarui Gong; Xingyuan Men; Jing Li; Fang Ouyang; Feng Ge (Journal of Cleaner Production, 2023)

Occurrence and exposure assessment of chlorate and perchlorate in food and drinking water from Fujian, China - Wenting Zhang; Qiuyan Lu; Yuxiang Li; Yongyou Hua; Renjin Zheng (Food Control, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Tuning MXene electrical conductivity towards multifunctionality - Lu Jia; Suqin Zhou; Abbas Ahmed; Zhichao Yang; Shuqiang Liu; Hua Wang; Fu Li; Man Zhang; Yujing Zhang; Luyi Sun (Chemical Engineering Journal, 2023)

Enhanced VOCs adsorption and oxidation by hydrophobic-layer-modified YMn2O5 mullite catalyst with ultralow single-atom Pt loading - Jiaqin He; Yaru Wang; Xunxun Li; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

Dampness and mould in Chinese homes and sick building syndrome (SBS) symptoms – Associations with climate, family size, cleaning and ventilation - Bin Zhang; Dan Norbäck; Hong Cheng; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; Tingting Wang; et al. (Building and Environment, 2023)

m6A mRNA modification potentiates Th17 functions to inflame autoimmunity - Xuefei Wang; Chen Chen; Hongwei Sun; Kaiqiong Mao; Jiameng Yao; Weiqiao Zhang; Meixiao Zhan; Hua-Bing Li; Zhiren Zhang; Shu Zhu; Ligong Lu (Science China Life Sciences, 2023)

Association between meteorological factors and varicella incidence: a multicity study in Yunnan Province, China - Hao Wang; Shanjun Huang; Zhaohan Wang; Hua Zhen; Zhuo Li; Wenqi Fan; Menghan Lu; Xin Han; Lanping Du; Meifang Zhao; Yuke Yan; Xinyao Zhang; et al. (Environmental Science and Pollution Research, 2023)

Like father, like daughter:Paternal cadmium exposure causes hepatic glucose metabolic disorder and phospholipids accumulation in adult female offspring - Lu-Lu Tan; Yong-Wei Xiong; Jin Zhang; Dai-Xin Li; Yichao Huang; Hua Wang (Chemosphere, 2023)

Quantifying cooling benefits of cool roofs and walls applied in building clusters by scaled outdoor experiments - Mengrong Lu; Liyue Zeng; Qingman Li; Jian Hang; Jiajia Hua; Xuemei Wang; Weiwen Wang (Sustainable Cities and Society, 2023)

Chlorine-mediated electrochemical advanced oxidation process for ammonia removal: Mechanisms, characteristics and expectation - Qiangang Li; Guo-hua Liu; Lu Qi; Hongchen Wang; Guang Xian (Science of The Total Environment, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Heavy silicon and oxygen isotope signatures of TTGs formed in distinct tectonic settings - Kai Lei; Qing Zhang; Yu Liu; Kai Lu; Li-Guang Wu; Sheng He; Xian-Hua Li (Precambrian Research, 2023)

Attenuation effects of ZVI/PDS pretreatment on propagation of antibiotic resistance genes in bioreactors: Driven by antibiotic residues and sulfate assimilation - Qi Zhao; Qing-Lian Wu; Hua-Zhe Wang; Qi-Shi Si; Lu-Shi Sun; De-Nian Li; Nan-Qi Ren; Wan-Qian Guo (Journal of Hazardous Materials, 2023)

Dual-supported nanoscale zero-valent iron for As(III) contaminated groundwater remediation - Ying Liang; Lu Tang; Jun Jiang; Meng-li Li; Hua-gang Lv; Yong He; Hong-yu Liu; Sheng-guo Xue (Journal of Environmental Chemical Engineering, 2023)

E-eye, flash GC E-nose and HS-GC-MS combined with chemometrics to identify the adulterants and geographical origins of Ziziphi Spinosae Semen - Jiu-ba Zhang; Ming-xuan Li; Yun-fei Zhang; Yu-wen Qin; Yu Li; Lian-lin Su; Lin Li; Zhen-hua Bian; Tu-lin Lu (Food Chemistry, 2023)

New insights into the regulation mechanism of Pacific white shrimp (Litopenaeus vannamei) hepatopancreas under 4-nonylphenol exposure using transcriptome analysis - Pei-Hua Zheng; Yao-Peng Lu; Xiu-Xia Zhang; Ke-Er Luan; Ze-Long Zhang; Jia-Jun Li; Tong Xu; Jun-Tao Li; Jian-An Xian; Hui Guo; An-Li Wang (Fish & Shellfish Immunology, 2023)

Removal of antibiotic-resistant bacteria and genes by Solar-activated Ferrate/ Peroxymonosulfate: Efficiency in aquaculture wastewater and mechanism - Ruixue Li; Xudai Wu; Zhenfei Han; Lijie Xu; Lu Gan; Yanqiong Zhang; Fengru Lu; Hua Lin; Xue Yang; Muting Yan; Wei Chu; Han Gong (Chemical Engineering Journal, 2023)

Clarifying the contributor of ammonia oxidation in chlorine-mediated electrochemical process - Qiangang Li; Guo-hua Liu; Sizhe Chen; Lu Qi; Hongchen Wang (Chemical Engineering Journal, 2023)

Microbiological Characteristics and Risk Factors Involved in Progression from Fungal Keratitis with Hypopyon to Keratitis-Related Endophthalmitis - Yu Sun; Fanxing Zeng; Jingjing Zhang; Xiaolin Qi; Xiuhai Lu; Na Ning; Suxia Li; Ting Zhang; Gongqiang Yuan; Weiyun Shi; Hua Gao (Mycopathologia, 2023)

Development and validation of a machine learning model to predict prognosis in HIV-negative cryptococcal meningitis patients: a multicenter study - Junyu Liu; Yaxin Lu; Jia Liu; Jiayin Liang; Qilong Zhang; Hua Li; Xiufeng Zhong; Hui Bu; Zhanhang Wang; Liuxu Fan; Panpan Liang; Jia Xie; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Serum exosomal hsa_circRNA_0001842 is the potential biomarker for diagnosing lower limb vascular disease in type 2 diabetes mellitus - Qian-Qian Liu; Xing-Hui Liu; Hai-Ming Wang; Li-Min Xu; Xiao-Jing Zhao; Shu-Guang Han; Zuo-Hua Lu (Journal of Genetics, 2023)

Silica mitigated calcium mineral scaling in brackish water reverse osmosis - Kai-Ge Lu; Shuanglong Ma; Dangling Hua; Hongen Liu; Chang Li; Jia Song; Haiou Huang; Yuchen Qin (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Hypoxia and panvascular diseases: exploring the role of hypoxia-inducible factors in vascular smooth muscle cells under panvascular pathologies - Yiqing Hu; Yongchao Zhao; Peng Li; Hao Lu; Hua Li; Junbo Ge (Science Bulletin, 2023)

Ridge tillage increased halophyte fine root production and turnover rates by altering soil properties in an abandoned farmland in northwest China - Xu Zheng; Chao-qun Chen; Lu-hua Li; Jia-ping Wang (Rhizosphere, 2023)

Phytochemistry and biological activities of corynanthe alkaloids - Jun Li; Jia-Xing Li; Hua Jiang; Min Li; Lin Chen; Yue-Yue Wang; Lu Wang; Ning Zhang; He-Zhe Guo; Kai-Long Ma (Phytochemistry, 2023)

Selective degradation of antibiotic in a novel Cu7S4/peroxydisulfate system via heterogeneous Cu(III) formation: Performance, mechanism and toxicity evaluation - Xieping He; Yining Lu; Tao Cai; Xijun Fu; Lu Song; Minjie Wang; Qingyi Zeng; Qingming Zeng; Mi Li; Yilong Hua; Xiaoyan Wu; Longlu Wang (Journal of Hazardous Materials, 2023)

Design of effective catalysts for the aftertreatment of CNG-fueled vehicle exhaust by doping 1% Pt/Ce0.4Zr0.5La0.05Y0.05-xO1.95+x with niobium - Yu Chen; Lei Jiang; Bing Bao; Chunqiang Lu; Yunkun Zhao; Shiying Chang; Dongxia Yang; Depeng Zhao; Xianming Cheng; Hua Wang; Kongzhai Li (Fuel, 2023)

Loss of Atg5 in Sertoli cells enhances the susceptibility of cadmium-impaired testicular spermatogenesis in mice - Yong-Wei Xiong; Dai-Xin Li; Zheng-Jia Ling; Lu-Lu Tan; Yu-Feng Zhang; Jin Zhang; Hao Li; Wei Chang; Hua-Long Zhu; Jun Zhang; Lan Gao; De-Xiang Xu; et al. (Food and Chemical Toxicology, 2023)

Alteration of the migration trajectory of antibiotic resistance genes by microplastics in a leachate activated sludge system - Hongyuan Liu; Hong Li; Libo Qiu; Qiaona Xie; Yingying Lu; Binhui Chen; Hua Wang; Yuyang Long; Lifang Hu; Chengran Fang (Environmental Pollution, 2023)

Boosted photogenerated charge carrier separation by synergy of oxygen and phosphorus co-doping of graphitic carbon nitride for efficient 2-chlorophenol photocatalytic degradation - Zhuzhu Zhang; Qimeng Sun; Rui Ji; Dongyun Chen; Najun Li; Hua Li; Qingfeng Xu; Huilong Dong; Jianmei Lu (Chemical Engineering Journal, 2023)

Neuroprotective effect of salidroside on hippocampal neurons in diabetic mice via PI3K/Akt/GSK-3β signaling pathway - Xue-Hua Wang; Zhong-Fu Zuo; Lu Meng; Qi Yang; Pan Lv; Li-Pan Zhao; Xiao-Bai Wang; Yu-Fei Wang; Ying Huang; Cong Fu; Wen-Qiang Liu; Xue-Zheng Liu; et al. (Psychopharmacology, 2023)

Cordythiazole A, the first member of thiazole alkaloids from Chinese cordyceps, with α-glucosidase inhibitory activity - Xue Han; Li-Hua Liu; Xiao-Ying Fang; Shu-Tai Jiang; Huan Zhao; Zheng-Ming Qian; Zhi-Nan Yin; Li-Gong Lu; Chuan-Xi Wang; Xin-Sheng Yao; Hao Gao (Journal of Natural Medicines, 2023)

Distribution, sources, and risk assessment of polycyclic aromatic hydrocarbons (PAHs) in Kaokaowusu river sediments near a coal industrial zone - Zhu Wang; Yong Jun Liu; Lu Yang; Zhuang Zhuang Yang; Ai Ning Zhang; Zhi Hua Li; Zhe Liu (Environmental Geochemistry and Health, 2023)

An integrated method to quantify human appropriation of net primary production in grasslands of the Qinghai-Tibet Plateau - Xuhuan Dai; Yanzheng Yang; Hua Zheng; Nan Meng; Jingyi Zhu; Ruonan Li; Jinfeng Ma; Zijian Lu; Zuzheng Li (Applied Geography, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

Biomimetic porphyrin-modified 3D porous composite material adsorption enhances photocatalytic CO2 reduction and tetracycline oxidative degradation - Mengmeng Wang; Yingxue Zhang; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

Increased risk of respiratory and allergic diseases in preschoolers from building envelope dampness exposure: Repeated cross-sectional surveys in multicity China - Wei Yu; Yan Zhang; Baizhan Li; Yinping Zhang; Chenqiu Du; Zhuohui Zhao; Dan Norback; Jiao Cai; Qihong Deng; Chan Lu; Hua Qian; Xiaohong Zheng; et al. (Building and Environment, 2023)

Modeling the effects of realistic land cover changes on land surface temperatures over China - Xing Li; Haishan Chen; Wenjian Hua; Hedi Ma; Xiao Li; Shanlei Sun; Yiwen Lu; Xueqi Pang; Xuanwen Zhang; Qian Zhang (Climate Dynamics, 2023)

Nanobubble technology applications in environmental and agricultural systems: Opportunities and challenges - Kyle Rafael Marcelino; Li Ling; Sumeth Wongkiew; Hua Thai Nhan; K. C. Surendra; Ty Shitanaka; Hui Lu; Samir Kumar Khanal (Critical Reviews in Environmental Science and Technology, 2023)

Evaluating the ecological vulnerability of Chongqing using deep learning - Jun-Yi Wu; Hong Liu; Tong Li; Yuan Ou-Yang; Jing-Hua Zhang; Teng-Jiao Zhang; Yong Huang; Wen-Long Gao; Lu Shao (Environmental Science and Pollution Research, 2023)

Extraction optimization and identification of four advanced glycation-end products inhibitors from lotus leaves and interaction mechanism analysis - Lu Zhang; Qi-ming Zhou; Liang Xu; Xing Xie; Pei-xin Wang; Zuo-hua Xie; Jin-lin Li; Zong-cai Tu (Food Chemistry, 2023)

Punching shear behavior and strength prediction of UHTCC-enhanced RC slab-column joints - Xiao-Ning Huang; Qing-Hua Li; Jing-Zhong Tong; Shi-Lang Xu; Yu-Chen Lu (Engineering Structures, 2023)

Amorphous biomineral-reinforced hydrogels with dramatically enhanced toughness for strain sensing - Jia-hua Liu; Zhengyi Mao; Yuhan Chen; Yunchen Long; Haikun Wu; Junda Shen; Rong Zhang; Oscar W.H. Yeung; Binbin Zhou; Chunyi Zhi; Jian Lu; Yang Yang Li (Chemical Engineering Journal, 2023)

Plasmon driven super-high HER activity of electronic structure and lattice strain engineered single atomic layer Pd@Au nanorods - Yi-Bai Sun; Miao Ni; Chen Chi; Dong-Rui Yang; Xue-Lu Chen; Qi Qi; Jian Li; Xing-Hua Xia (Chemical Engineering Journal, 2023)

Performance and mechanism of phosphorus adsorption removal from wastewater by a Ce-Zr-Al composite adsorbent - Yijin Wang; Guo-hua Liu; Junli Yuan; Qiangang Li; Lu Qi; Hongchen Wang (Environmental Science and Pollution Research, 2023)

Long-term cadmium exposure induces chronic obstructive pulmonary disease-like lung lesions in a mouse model - Wen-Jing Wang; Kun Peng; Xue Lu; Yan-Yan Zhu; Zhao Li; Qing-Hua Qian; Ya-Xin Yao; Lin Fu; Yan Wang; Yi-Chao Huang; Hui Zhao; Hua Wang; et al. (Science of The Total Environment, 2023)

Exploring the continuous cleavage-oxidation mechanism of the catalytic oxidation of cellulose to formic acid: A combined experimental and theoretical study - Gui-Hua Wei; Ting Lu; Hai-Yan Liu; Jiao-Xuan Bai; Qian Wang; Guang-Yue Li; Ying-Hua Liang (Fuel, 2023)

Construction of a dynamic model to predict the growth of Staphylococcus aureus and the formation of enterotoxins during Kazak cheese maturation - Huixue Cai; Sijie Pei; Yan Zhang; Rongrong Liu; Shiling Lu; Baokun Li; Juan Dong; Qingling Wang; Xinrong Zhu; Hua Ji (Food Microbiology, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Barium(II)-based semiconductive coordination polymers for high-performance direct X-ray detection and imaging: Reducing the exciton binding energy via enhancing π-π interactions - Mei-Juan Xie; Jian Lu; Bao-Yi Li; Wen-Fei Wang; Shuai-Hua Wang; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2023)

Runx2 overexpression promotes bone repair of osteonecrosis of the femoral head (ONFH) - Hai-Jia Xu; Xiang-Zhong Liu; Lu Yang; Yu Ning; Liang-Liang Xu; Da-Ming Sun; Wen Liao; Yi Yang; Zhang-Hua Li (Molecular Biology Reports, 2023)
Background Runt-related transcription factor-2 (Runx2) has been considered an inducer to improve bone repair ability of mesenchymal stem cells (MSCs). Methods and results Twenty-four rabbits were used to establish Osteonecrosis of the femoral head (ONFH) and randomly devided into four groups: Adenovirus Runx2 (Ad-Runx2) group, Runx2-siRNA group, MSCs group and Model group. At 1 week after model establishment, the Ad-Runx2 group was treated with 5 × 107 MSCs transfected through Ad-Runx2, the Runx2-siRNA group was treated with 5 × 107 MSCs transfected through Runx2-siRNA, the MSCs group was injected with 5 × 107 untreated MSCs, and the Model group was treated with saline. The injection was administered at 1 week and 3 weeks after model establishment. The expression of bone morphogenetic protein 2 (BMP-2), Runx2 and Osterix from the femoral head was detected at 3 and 6 weeks after MSCs being injected, and Masson Trichrome Staining, Gross Morphology, X-ray and CT images observation were used to evaluate the repair effect of ONFH. The data revealed that the expression of BMP-2, Runx2 and Osterix in the Runx2-siRNA group was reduced at 3 weeks compared with the MSCs group, and then the expression further reduced at 6 weeks, but was still higher than the Model group besides Osterix; The expression of these three genes in the Ad-Runx2 group was higher than in the MSCs group. Masson Trichrome Staining, Gross Morphology and X-ray and CT images observation revealed that necrotic femoral head of the MSCs group was more regular and smooth than the Runx2-siRNA group, which has a collapsed and irregular femoral head. In the Ad-Runx2 group, necrotic femoral head was basically completely repaired and covered by rich cartilage and bone tissue. Conclusions Overexpression of Runx2 can improve osteoblastic phenotype maintenance of MSCs and promote necrotic bone repair of ONFH.

Multi-channel GCN ensembled machine learning model for molecular aqueous solubility prediction on a clean dataset - Chenglong Deng; Li Liang; Guomeng Xing; Yi Hua; Tao Lu; Yanmin Zhang; Yadong Chen; Haichun Liu (Molecular Diversity, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Effects of different dietary lipid sources (perilla, fish, and soybean oils) on growth, lipid metabolism, antioxidant, and immune status in Chinese giant salamander (Andrias davidianus) - Yi-Hua Guo; Jun-Kang Ma; Hang-zhong Xu; Wei-long Li; Chang-Jiang Liu; Hua Lu; Hong Li; Xu-liang Zhai; Yang Xue; Li Luo (Frontiers in Marine Science, 2023)
Introduction Perilla oil is a natural vegetable oil rich in alpha-linolenic acid extracted from Perilla seeds. Fish oil is a commonly used animal fat containing a large amount of n-3 polyunsaturated fatty acids. Soybean oil is a commonly used vegetable oil rich in linoleic acid. This study aimed to determine whether perilla, fish, or soybean oil can be used as a lipid source in the diet of the Chinese giant salamander ( Andrias davidianus ). Methods Three isonitrogenous and isolipidic diets were created by adding 3.0% each of soybean oil (SO), fish oil (FO), and perilla seed oil (PSO). Eight adolescent giant salamanders were fed in rectangular tanks for 98 days with a total of 96 giant salamanders (mean body weight = 75.20g) and were fed an experimental diet until satiation. Results and Discussion The viscerosomatic index and crude lipid content of muscle were found to be considerably lower and the muscle crude protein was substantially higher in the PSO group than in the other groups (P<0.05). Linoleic acid levels were highest in SO, eicosapentaenoic acid and docosahexaenoic acid levels were highest in FO, and α-linolenic acid levels were highest in PSO in A. davidianus muscle tissue (P<0.05). The results of study indicate that the PSO diet can significantly increase the total antioxidative capabilities in the liver and intestine, by elevating the activities of total superoxide dismutase, carnitine transferase-1, and acetyl-CoA carboxylase in the liver. Meanwhile, the immunoglobulin M and high-density lipoprotein cholesterol levels were higher in the blood (P<0.05). Furthermore, it significantly reduced hepatic malondialdehyde, plasma endotoxin, D-lactic acid, and total cholesterol levels, and plasma alkaline phosphatase, diamine oxidase, aspartate transaminase, and alanine transaminase activities (P<0.05). Therefore, perilla, fish, and soybean oils can be used as single lipid sources for A. davidianus with respect to growth performance. On the other hand, perilla oil can enhance crude protein content of muscle, increase Immunoglobulin M(IgM) content and Alkaline phosphatase(AKP) enzyme activity, promote lipid metabolism, and maintain the health of the liver and intestine in A. davidianus .

Two new compounds from edible mushroom Sarcomyxa edulis - Lan Yao; Jian-Hua Lv; Mei-Chen Pan; Lei Xing; Lu-Peng Wang; Chang-Tian Li; Shu-Yan Liu; Yu Li (Natural Product Research, 2023)

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

Colonic mechanism of serum NAD+ depletion induced by DEHP during pregnancy - Yun Hong; Xia Ning; Yue-yue Liang; Xiao-lu Li; Ya Cui; Wei Wu; Yang Cai; Shuai Zhao; Meng Zhu; Tian-xiao Zhong; Hua Wang; De-xiang Xu; et al. (Science of The Total Environment, 2023)

Effects of tetrasodium pyrophosphate coupled with soy protein isolate on the emulsion gel properties of oxidative myofibrillar protein - Jun Liu; Ze Yu; Wenru Xie; Lu Yang; Mingyun Zhang; Chunqiang Li; Jun-hua Shao (Food Chemistry, 2023)

Clonal fragmentation drives performance deterioration of epiphytic and lithophytic ferns in a karst forest - Qian Dai; Yu-Xuan Mo; Quan Chen; Liang Song; Li-Min Zhang; Gbadamassi G.O. Dossa; Hua-Zheng Lu (Flora, 2023)

Under-loaded operation of an anaerobic-anoxic-aerobic system in dry and wet weather dynamics to prevent overflow pollution: Impacts on process performance and microbial community - Lu-Man Jiang; Zhenjian Zhang; Yunhui Li; Jialei Xu; Kun Wang; Xinya Ding; Junli He; Zhan Qiu; Hua Zhou; Zhen Zhou (Bioresource Technology, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

WITHDRAWN: Construction and evaluation of risk prediction model for kidney injury in patients treated with PD-1 inhibitors - Peiyu Lu; Li Tian; Aihua Wu; Hua Zhou; Min Yang (Toxicology and Applied Pharmacology, 2023)

Enhanced remediation of phenanthrene in water and soil by novel biochar-immobilized bacterial microspheres - Kai Wang; Yang Sun; Dongyun Chen; Qingfeng Xu; Najun Li; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

How the Wild Sugarcane Resource Miscanthus floridulus Responds to Low-Temperature Stress: A Physiological and Transcriptomic Analysis - Hong-Li Yang; Zhi-Jun Guo; Lu Jiang; Jun-Jun He; Qing Liu; Mo Chen; Xing-Hua Yu; Xian-Hong Wang; Qing-Hui Yang (Sugar Tech, 2023)

Regional differences in gully network connectivity based on graph theory: a case study on the Loess Plateau, China - Jian-hua Cheng; Lan-hua Luo; Fa-yuan Li; Lu-lu Liu; Ling-zhou Cui (Journal of Mountain Science, 2023)

Dietary lysine facilitates muscle growth and mediates flesh quality of Pacific white shrimp (Litopenaeus vannamei) reared in low-salinity water - Meili Wu; Meifeng Li; Hua Wen; Lijuan Yu; Ming Jiang; Xing Lu; Juan Tian; Feng Huang (Aquaculture International, 2023)

The development and layout of China's cruise industry in the post-epidemic era: Conference report - Hua Li; Jing Lu; Shanqi Hu; Shengjun Gan (Marine Policy, 2023)

Variations in the concentration, source and flux of polycyclic aromatic hydrocarbons in sediments of the Pearl River Estuary: Implications for anthropogenic impacts - Yali Li; Nairong Guo; Ke Yuan; Baowei Chen; Junjie Wang; Maofeng Hua; Jing Yu; Jingyan Hu; Run Lu; Shichun Zou; Ying Yang (Science of The Total Environment, 2023)

A rapid selection strategy for umami peptide screening based on machine learning and molecular docking - Chen Li; Ying Hua; Daodong Pan; Lulu Qi; Chaogeng Xiao; Yongzhao Xiong; Wenjing Lu; Yali Dang; Xinchang Gao; Yufen Zhao (Food Chemistry, 2023)

A reverse distribution between synergistic effect and economic development: An analysis from industrial SO2 decoupling and CO2 decoupling - Feng Dong; Jingyun Li; Jianheng Huang; Yang Lu; Chang Qin; Xiaoyun Zhang; Bin Lu; Yajie Liu; Yifei Hua (Environmental Impact Assessment Review, 2023)

Fine mapping and candidate gene analysis of qFL-A12-5: a fiber length-related QTL introgressed from Gossypium barbadense into Gossypium hirsutum - Xianghui Xiao; Ruixian Liu; Juwu Gong; Pengtao Li; Ziyin Li; Wankui Gong; Aiying Liu; Qun Ge; Xiaoying Deng; Shaoqi Li; Quanjia Chen; Hua Zhang; et al. (Theoretical and Applied Genetics, 2023)

Flood variability in the upper Yangtze River over the last millennium—Insights from a comparison of climate-hydrological model simulated and reconstruction - Ran Huo; Hua Chen; Lu Li; Chong-Yu Xu; Jingjing Li; Si Hong; Chesheng Zhan; Jun Xia (Science China Earth Sciences, 2023)

Comprehensive performance evaluation of plasma vitrification for detoxification and valorization of residual wastes - Yao-Jian Li; Si-Lu Pei; Zhong-Hua Sun; Lei Zhong; Cheng-Chun He; Shu-Yuan Pan (Critical Reviews in Environmental Science and Technology, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Solvent-free oxidation of toluene to benzaldehyde using electron-rich Au clusters confined in Silicalite-1 - He Huang; Huahua Fan; Yuzhen Ge; Wanyue Ye; Yingcen Liu; Caicheng Song; Hua Lin; Xiaotong Zhang; Bing Li; Xiaowa Nie; Shufen Zhang; Rongwen Lu (Chemical Engineering Journal, 2023)

Ni-Mn spinel aerogel catalysts with adsorption induced superior activity for Low-Temperature toluene oxidation - Jiaqin He; Xunxun Li; Yaru Wang; Jun Xiao; Yunchong Liu; Hua Li; Najun Li; Qingfeng Xu; Jinghui He; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2023)

8-O-acetyl shanzhiside methylester protects against sleep deprivation-induced cognitive deficits and anxiety-like behaviors by regulating NLRP3 and Nrf2 pathways in mice - Yu-Jiao Li; Xiao-Lu He; Jie-Yu Zhang; Xue-Jiao Liu; Jia-Long Liang; Qing Zhou; Guo-Hua Zhou (Metabolic Brain Disease, 2023)

Effects of urban particulate matter on gut microbiome and partial schizophrenia-like symptoms in mice: Evidence from shotgun metagenomic and metabolomic profiling - Weizhuo Yi; Yifu Ji; Hua Gao; Shengyong Luo; Rubing Pan; Jian Song; Yangyang He; Yuxuan Li; Yudong Wu; Shuangshuang Yan; Yunfeng Liang; Xiaoni Sun; et al. (Science of The Total Environment, 2023)

Phylogeny, character evolution, and biogeography of the fern genus Bolbitis (Dryopteridaceae) - Li-Yun Nie; Liang Zhang; Zhen-Long Liang; Rossarin Pollawatn; Yue-Hong Yan; Ngan Thi Lu; Ralf Knapp; Xia Wan; Daniele Cicuzza; Xin-Xin Cheng; Hong-Feng Chen; Ai-Hua Wang; et al. (Molecular Phylogenetics and Evolution, 2023)

Low quantity of Pt loaded onto CeCoOx nanoboxes: Surface–rich reactive oxygen species for catalytic oxidation of toluene - Yunchong Liu; Xunxun Li; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Alterations of gut and oral microbiota in the individuals consuming take-away food in disposable plastic containers - Hua Zha; Jiawen Lv; Yiqing Lou; Wanlong Wo; Jiafeng Xia; Shengjie Li; Aoxiang Zhuge; Ruiqi Tang; Nian Si; Zhihao Hu; Haifeng Lu; Kevin Chang; et al. (Journal of Hazardous Materials, 2023)

Sulfonate-modified calixarene-based porous organic polymers for electrostatic enhancement and efficient rapid removal of cationic dyes in water - Lechen Tian; Shiyuan Zhou; Jiaojiao Zhao; Qingfeng Xu; Najun Li; Dongyun Chen; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Covalent organic framework-immobilized wood membrane for efficient, durable, and high-flux nanofiltration - Zhidong Zhang; Hua Li; Jianguo Cui; Zhouli Yang; Ruien Hou; Yujun Ju; Xiaoquan Lu; Fengjuan Chen (Journal of Cleaner Production, 2023)

Aggravation of nitrogen losses driven by agriculture and livestock farming development on the Qinghai-Tibet Plateau - Fangfang Wang; Shiliang Liu; Hua Liu; Yixuan Liu; Lu Yu; Qingbo Wang; Yuhong Dong; Jian Sun; Lam-Son Phan Tran; Weiqiang Li (Journal of Environmental Management, 2023)

Discrimination of the harvesting season of green tea by alcohol/salt-based aqueous two-phase systems combined with chemometric analysis - Xiao-Hua Zhang; Hui-Na Cui; Jing-Jing Zheng; Xiang-Dong Qing; Kai-Long Yang; Ya-Qian Zhang; Lu-Meng Ren; Le-Yuan Pan; Xiao-Li Yin (Food Research International, 2023)

Traceability and identification of fish gelatin from seven cyprinid fishes by high performance liquid chromatography and high-resolution mass spectrometry - Xiao-Mei Sha; Wen-Li Jiang; Zi-Zi Hu; Li-Jun Zhang; Zuo-Hua Xie; Ling Lu; Tao Yuan; Zong-Cai Tu (Food Chemistry, 2023)

New insights into the regulation mechanism of red claw crayfish (Cherax quadricarinatus) hepatopancreas under air exposure using transcriptome analysis - Yao-Peng Lu; Pei-Hua Zheng; Xiu-Xia Zhang; Jun-Tao Li; Ze-Long Zhang; Jia-Rui Xu; Yong-Qi Meng; Jia-Jun Li; Jian-An Xian; An-Li Wang (Fish & Shellfish Immunology, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Design of hybrid La1-Ce CoO3- catalysts for lean methane combustion via creating active Co and Ce species - Lei Jiang; Danyang Li; Guixian Deng; Chunqiang Lu; Linan Huang; Zhiqiang Li; Haiwen Xu; Xing Zhu; Hua Wang; Kongzhai Li (Chemical Engineering Journal, 2023)

Lead-Free Cs3Bi2Br9 perovskite In-situ growth on 3D Flower-like g-C3N4 microspheres to improve photocatalytic performance - Bingke Xie; Dongyun Chen; Najun Li; Qingfeng Xu; Hua Li; Jianmei Lu (Chemical Engineering Journal, 2023)

Effects of mold, water damage and window pane condensation on adult rhinitis and asthma partly mediated by different odors - Juan Wang; Yinping Zhang; Baizhan Li; Zhuohui Zhao; Chen Huang; Xin Zhang; Qihong Deng; Chan Lu; Hua Qian; Xu Yang; Yuexia Sun; Dan Norbäck (Building and Environment, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Increasing soil heterogeneity strengthens the inhibition of a native woody plant by an invasive congener - Yi Hu; Zhen-Wei Xu; Ming-Yan Li; Jordan R. Croy; Zhong-Yi Zhang; Hai-Mei Li; Wei-Hua Guo; Xiao-Lei Jiang; Hui-Cui Lu; Xiao Guo (Plant and Soil, 2022)

Idiomarina rhizosphaerae sp. nov. isolated from rhizosphere soil of Kalidium cuspidatum, and reclassification of Idiomarina andamanensis as Pseudidiomarina andamanensis comb. nov., and Idiomarina mangrovi as Pseudidiomarina mangrovi comb. nov - Lu-Fan Li; Lian Xu; Hua-Mei Wei; Ji-Quan Sun (Archives of Microbiology, 2022)

Has substantial sea ice loss along the Siberian coast contributed to the 2020/2021 winter cold wave in China? - Shaoyin Wang; Jiping Liu; Xiao Cheng; Tobias Kerzenmacher; Hua Li; Riyu Lu; Yongyun Hu; Zhuoqi Chen; Peter Braesicke (International Journal of Climatology, 2022)
In winter 2020/2021, several episodes of cold air outbreaks have wreaked havoc across much of China, resulting in exceptionally low temperatures over northern‐to‐southeastern China. Our analysis shows that the anomalous circulation leading to the cold wave in China was characterized as: (a) a strengthening of the Siberian high, (b) a deepening of the East Asian trough, and (c) a weakening of the stratospheric polar vortex. Prior to the winter, in summer and autumn, the largest sea ice loss along the Siberian coast was observed. We therefore address the question whether the substantial sea ice loss has contributed to the cold wave. First, applying singular value decomposition (SVD) analysis, we find strong coherence between the autumn Arctic sea ice coverage and temperatures over the central‐to‐east Asian region with the sea ice component (SVD1_SIC) reaching a record high in 2020 and displaying a decadal shift around 2005. Associated with both the interannual and decadal variations of the SVD1_SIC, there are similar circulation anomalies as described in (a), (b) and (c) above. Second, applying self‐organizing maps, wintertime daily air temperatures are clustered into nine nodes with Node‐1 mostly resembling “warm Arctic, cold Eurasia” pattern. The frequency of Node‐1 shows a similar decadal shift as observed in SVD_SIC1 above, with a correlation of about 0.56. Associated with Node‐1, the circulation anomalies are consistent with features highlighted in (a), (b) and (c) above. Thus, taking all the evidence into account, we conclude that the substantial sea ice loss along the Siberian coast contributed significantly to the 2020/2021 winter cold wave in China. The mechanism behind the contribution in this study highlights that the Arctic sea ice loss is favourable for certain circulation patterns on climate timescale, reinforcing disruptive chain of reactions on weather timescale, and leading to severe cold events.

Shallow groundwater enhances water productivity of maize in arid area - Jialu Dai; Ruiping Li; Qingfeng Miao; Congcong Li; Yaoze Lu; Zhimin Hua (Irrigation Science, 2022)

Genetic variations in the bitter taste receptor gene TAS2R38 are related to cigarette smoking behavior in Han Chinese smokers - Fei-Yan Qi; Zhou-Hai Zhu; Meng Li; Ying Guan; Qi-Yuan Peng; She-Ming Lu; Zhi-Hua Liu; Ming-Feng Wang; Ming-Ming Miao; Zhang-Yu Chen; Xue-Mei Li; Jie Bai; et al. (Genes & Genomics, 2022)

Activated sludge process enabling highly efficient removal of heavy metal in wastewater - Guo-hua Liu; Xiangnan Tang; Junli Yuan; Qiangang Li; Lu Qi; Hongchen Wang; Zhengfang Ye; Quanlin Zhao (Environmental Science and Pollution Research, 2022)

Correction to: Protective effects of fowl‑origin cadmium‑tolerant lactobacillus against sub‑chronic cadmium‑induced toxicity in chickens - Da‑Wei Chen; Hui‑Jia Li; YinYin Liu; Li‑Na Ma; Jun‑Hua Pu; JunXian Lu; Xiu‑Jun Tang; Yu‑shi Gao (Environmental Science and Pollution Research, 2022)

Protective effects of fowl-origin cadmium-tolerant lactobacillus against sub-chronic cadmium-induced toxicity in chickens - Da-Wei Chen; Hui-Jia Li; YinYin Liu; Li-Na Ma; Jun-Hua Pu; JunXian Lu; Xiu-Jun Tang; Yu-shi Gao (Environmental Science and Pollution Research, 2022)

Hyphomonas sediminis sp. nov., isolated from marine sediment - Lu Wang; Wei He; Zeng-Yu Gao; Dao-Feng Zhang; Jian-Ke Huang; Chuang Liu; Wen-Jun Li; Ai Hua Zhang (Antonie van Leeuwenhoek, 2022)

Prediction of Water Inflow into Tunnel Crossing Intersecting Faults Based on IDB Seepage Model - Jing Wu; Li Wu; Ya-ni Lu; Yan-hua Han; Jun-jie Jiang (Geotechnical and Geological Engineering, 2022)

The relationship between short-term PM2.5 exposure and outpatient visits for acne vulgaris in Chongqing, China: a time-series study - Xiang Li; Lai-Xin Zhou; Li-Li Yang; Xiao-Long Huang; Nan Wang; Yue-Gu Hu; En-Jie Tang; Hua Xiao; Yu-Meng Zhou; Ya-Fei Li; Yuan-Gang Lu; Tong-Jian Cai (Environmental Science and Pollution Research, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

TRIM36 suppresses cell growth and promotes apoptosis in human esophageal squamous cell carcinoma cells by inhibiting Wnt/β-catenin signaling pathway - Bin Zhao; Gaofeng Qiao; Jianhua Li; Yukun Wang; XiaoDong Li; Hua Zhang; Lu Zhang (Human Cell, 2022)

Effects of Late Pleistocene Climatic Fluctuations on the Phylogeographic and Demographic History of Japanese Scad (Decapterus maruadsi) - Qing-Hua Wang; Ren-Xie Wu; Zhong-Lu Li; Su-Fang Niu; Yun Zhai; Min Huang; Biao Li (Frontiers in Marine Science, 2022)
The Late Pleistocene-Holocene climate fluctuations have greatly influenced the phylogeographic structure and historical dynamics of many marine organisms in the western Pacific marginal seas. Here, we investigated the impact of Pleistocene glacial-interglacial cycles on the phylogeographic structure and demographic dynamics of Decapterus maruadsi , an economically important fish along the coast of the East China Sea (ECS) and northern South China Sea (NSCS). We obtained 430 concatenated sequences (Cyt b + control region, 1548–1554 bp) of D. maruadsi , including 246 newly sampled from the ECS and 184 previously determined from the NSCS. Genetic structure and phylogenetic analysis demonstrated a lack of significant population structure among 16 populations. Moreover, there was no significant differentiation among populations from Chinese coastal waters and northern Vietnam. Neutrality tests, unimodal mismatch distributions, Bayesian skyline plots, and the star-like haplotype networks all indicated a recent demographic expansion for D. maruadsi population during the Late Pleistocene-Holocene, explaining the low genetic diversity in D. maruadsi along the southeast coast of China. Notably, phylogenetic analyses and net genetic distances based on Cyt b jointly confirmed that 57 Cyt b haplotypes identified as D. maruadsi from the previously defined Sundaland-Rosario-Ranong clade actually represented D. russelli . These results not only reveal the complex effects of Pleistocene-Holocene climate fluctuations on the phylogeographic structure and demographic history of D. maruadsi but also provide useful genetic information for the management of genetic resources.

LncDACH1 promotes mitochondrial oxidative stress of cardiomyocytes by interacting with sirtuin3 and aggravates diabetic cardiomyopathy - Qi Zhang; Danyang Li; Xue Dong; Xiaowen Zhang; Junwu Liu; Lili Peng; Bo Meng; Qi Hua; Xinyu Pei; Lu Zhao; Xiaoxi Hu; Yang Zhang; et al. (Science China Life Sciences, 2022)

Combined System of Organic Substrate and Straw-Degrading Microbial Agents Improved Soil Organic Matter Levels and Microbial Abundance in a Rice–Wheat Rotation - Shi-Li Song; Xue Luo; Hao Wu; Xiao-Lin Lu; Fang-Ji Xu; Zhen-Hua Zhang; Yong-Xiang Guan; Chuan-Chao Dai (Current Microbiology, 2022)

FLO8 deletion leads to decreased adhesion and virulence with downregulated expression of EPA1, EPA6, and EPA7 in Candida glabrata - Jun-Tao Zhao; Ke-Zhi Chen; Jin-Yan Liu; Wei-Hua Li; Yu-Zhu Wang; Lu-Ling Wang; Ming-Jie Xiang (Brazilian Journal of Microbiology, 2022)

Anti-hyperglycaemic effect of labdane diterpenes isolated from the rhizome of Amomum maximum Roxb., an edible plant in Southwest China - Chuan-Li Lu; Li-Ning Wang; Ya-Jun Li; Qing-Fei Fan; Qing-Hua Huang; Jun-Jia Chen (Natural Product Research, 2022)

Forensic analysis and numerical simulation of a catastrophic landslide of dissolved and fractured rock slope subject to underground mining - Xiaoming Wang; Yuanjie Xiao; Wenbing Shi; Juanjuan Ren; Feng Liang; Jiaqi Lu; Hua Li; Xiaoxiao Yu (Landslides, 2022)

Dominant Fungal Epiphytes Promote Growth of the Invasive Plant Ipomoea cairica Through Hormone Interactions - Hua Xu; Ping Chang; Shaoshan Li; Jianguo Lu; Xuejun Lin; Can Xie (Journal of Plant Growth Regulation, 2022)

Fine mapping of powdery mildew resistance gene MlWE74 derived from wild emmer wheat (Triticum turgidum ssp. dicoccoides) in an NBS-LRR gene cluster - Keyu Zhu; Miaomiao Li; Haibin Wu; Deyun Zhang; Lingli Dong; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Guanghao Guo; Huaizhi Zhang; Panpan Zhang; et al. (Theoretical and Applied Genetics, 2022)

Effective connectivity decreases in specific brain networks with postparalysis facial synkinesis: a dynamic causal modeling study - Zhen-Zhen Ma; Ye-Chen Lu; Jia-Jia Wu; Xu-Yun Hua; Si-Si Li; Wei Ding; Jian-Guang Xu (Brain Imaging and Behavior, 2022)

Analysis and Research on Blasting Network Delay of Deep-Buried Diversion Tunnel Crossing Fault Zone Based on EP-CEEMDAN-INHT - Jing Wu; Li Wu; Miao Sun; Ya-ni Lu; Yan-hua Han (Geotechnical and Geological Engineering, 2022)

Numerical simulation of water inrush in a tunnel crossing faults: impacts of fault width, damage zone width, and fault permeability - Jing Wu; Xintong Wang; Li Wu; Ya-ni Lu; Yan-hua Han (Arabian Journal of Geosciences, 2022)

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

First report of tomato spotted wilt virus in Zinnia elegans in China - Ning Jiang; Yong-lei Jiang; Xiao-tong Gai; Can-hua Lu; Zhe-jin Li; Zhen-yuan Xia (Journal of Plant Pathology, 2022)

Applicability and improvement of different evapotranspiration methods of reference crops in Jiangxi Province - Xianghui Lu; Haina Zhang; Yixiu Han; Hua Bai; Erhui Li (Theoretical and Applied Climatology, 2022)

MiR-615 Agomir Encapsulated in Pluronic F-127 Alleviates Neuron Damage and Facilitates Function Recovery After Brachial Plexus Avulsion - Kangzhen Chen; Lu Ding; Hua Shui; Yinru Liang; Xiaomin Zhang; Tao Wang; Linke Li; Shuxian Liu; Hongfu Wu (Journal of Molecular Neuroscience, 2022)
Brachial plexus avulsion (BPA) is a devastating traumatic peripheral nerve injury complicated with paralysis of the upper extremity. We previously reported that leucine-rich repeat and immunoglobulin-like domain-containing NOGO receptor-interacting protein 1 (LINGO-1) has a potent role in inhibiting neuron survival and axonal regeneration after the central nervous system (CNS) damage and miR-615 is a potential microRNA (miRNA) negatively regulated LINGO-1. However, the effect of miR-615 in BPA remains to be elucidated. Accumulating evidence indicates that pluronic F-127 (PF-127) hydrogel could serve as a promising vehicle for miRNA encapsulation. Thus, to further explore the potential role of hydrogel-miR-615 in BPA-reimplantation, the present study established the BPA rat model and injected miR-615 agomir encapsulated by PF-127 hydrogel into the reimplantation site using a microsyringe. In this study, results indicated that hydrogel-miR-615 agomir effectively alleviated motoneuron loss by LINGO-1 inhibition, promoted musculocutaneous nerve regeneration and myelination, reduced astrocytes activation, promoted angiogenesis and attenuated peripheral amyotrophy, leading to improved motor functional rehabilitation of the upper extremity. In conclusion, our findings demonstrate that miR-615-loaded PF-127 hydrogel may represent a novel therapeutic strategy for BPA treatment.

Two new nor-sesquiterpenoids from Fusarium tricinctum , an endophytic fungus isolated from Ligusticum chuanxiong - Yu-Mei Cao; Da-Le Guo; Meng-Ying Jin; Lu Tan; Tian-Long Yang; Fang Deng; Yu-Cheng Gu; Xiao-Hua Li; Zhi-Xing Cao; Yun Deng (Natural Product Research, 2021)

Effects of temperature on the growth and carbohydrate production of three benthic dinoflagellate species from Hainan Island, South China Sea - Zhen Wu; Hua Zhang; Qun Li; Lei Cui; Heng Chen; Songhui Lu (Ecotoxicology, 2021)

Influence of elevation on bioregionalisation: A case study of the Sino‐Himalayan flora - Yun Liu; Jian‐Fei Ye; Hai‐Hua Hu; Dan‐Xiao Peng; Li‐Na Zhao; Li‐Min Lu; Wajid Zaman; Zhi‐Duan Chen (Journal of Biogeography, 2021)
Aim Elevation is an important factor that influences bioregionalisation in mountainous areas, but its effects are not well known. Taking the Sino‐Himalayan flora as a case, we aimed to test the effect of elevation on bioregionalisation and provide a regionalisation scheme of the Sino‐Himalayan flora. Location The Sino‐Himalaya (East Himalaya, the Hengduan Mountains and the Yunnan Plateau in China). Taxon Angiosperms. Methods We compiled distribution data and elevation ranges of angiosperms in the Sino‐Himalaya and adjacent areas and reconstructed a species‐level phylogenetic tree of 19,313 angiosperm species. The area was divided into 398 grid cells, each 1 × 1°. Nine datasets of different elevation ranges were then used to delineate the flora of the Sino‐Himalaya and adjacent areas using the phylogenetic dissimilarity approach. Results A comparison of nine regionalisation schemes of the Sino‐Himalayan flora based on different elevation range datasets revealed that more than half of grid cells were allocated to more than one subregion. Most of these grid cells were located in areas with a wide range of elevation and/or at the boundaries between subregions. After revising the subregion allocations of eight shifting grid cells, we generated a phylogeny‐ and elevation‐based regionalisation scheme of three regions, comprising eight subregions, for the Sino‐Himalayan flora. Main conclusions By integrating phylogenetic and elevational information, the Sino‐Himalaya can be divided into three floristic regions: the Yunnan Plateau region, the Hengduan Mountains region and the East Himalaya region. Our study provides novel insights into the regionalisation of the flora and highlights the importance of incorporating elevation data in the bioregionalisation of areas with a broad elevational range.

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

Integrative taxonomy of the seasonally polyphenic scorpionfly Panorpa liui Hua, 1997 (Mecoptera: Panorpidae) - Ning Li; Lu Jiang; Ji-Shen Wang; Bao-Zhen Hua (Organisms Diversity & Evolution, 2021)

Exploring the dynamic mechanism of allosteric drug SHP099 inhibiting SHP2E69K - Shan Du; Xin-hua Lu; Wei-Ya Li; Li-Peng Li; Yang-Chun Ma; Liang Zhou; Jing-Wei Wu; Ying Ma; Run-Ling Wang (Molecular Diversity, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Resolvin D1 Attenuates Innate Immune Reactions in Experimental Subarachnoid Hemorrhage Rat Model - Guang-Jie Liu; Tao Tao; Xiang-Sheng Zhang; Yue Lu; Ling-Yun Wu; Yong-Yue Gao; Han Wang; Hai-Bin Dai; Yan Zhou; Zong Zhuang; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2021)

Bjerkandera adusta M1 inhibits the growth of Fusarium oxysporum f. sp. conglutinans and fusarium wilt incidence in Brassica napus L. - Xiao Feng; Su-Ping Li; Yi-Fan Lu; Jing-Jie Zhang; Yun-Yun Zhu; Yong Li; Hong-Jun Yang; Xin-Hua He (Journal of Plant Pathology, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

EPG-recorded Feeding Behaviors Reveal Adaptability and Competitiveness in Two Species of Bemisia tabaci (Hemiptera: Aleyrodidae) - Shao-hua Lu; Jing-jing Li; Run-e Bai; Feng-ming Yan (Journal of Insect Behavior, 2021)

Change detection in SAR images based on superpixel segmentation and image regression - Rui Zhao; Guo-Hua Peng; Wei-dong Yan; Lu-Lu Pan; Li-Ya Wang (Earth Science Informatics, 2021)

Soil amendment in plastic greenhouse using modified biochar: soil bacterial diversity responses and microbial biomass carbon and nitrogen - Bin Hua; Zhouwen Li; Weikai Gao; Huilin Feng; Nan Chen; Jiayi Li; Xiaoming Ji; Lu Zhang; Zhiyong Wu; Shen Yan; Tianbao Ren; Chensheng Xu; et al. (Biotechnology Letters, 2021)

Isolation and characterisation of N-benzyl tadalafil as a novel adulterant in a coffee-based dietary supplement - Pei-Zhi Dong; Xiao-Pu Liu; Lu Zhang; Guo-Hua Shen; Zi-Long Wang; Guo-Wei Yang; Wei Li; Xin-Hua Xiang (Food Additives & Contaminants: Part A, 2020)

Antibody response and therapy in COVID-19 patients: what can be learned for vaccine development? - Ligong Lu; Hui Zhang; Meixiao Zhan; Jun Jiang; Hua Yin; Danielle J. Dauphars; Shi-You Li; Yong Li; You-Wen He (Science China Life Sciences, 2020)

Fucoxanthin Mitigates Subarachnoid Hemorrhage-Induced Oxidative Damage via Sirtuin 1-Dependent Pathway - Xiang-Sheng Zhang; Yue Lu; Tao Tao; Han Wang; Guang-Jie Liu; Xun-Zhi Liu; Cang Liu; Da-Yong Xia; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2020)

The Bre1/Rad6 machinery: writing the central histone ubiquitin mark on H2B and beyond - Zhi-Heng Deng; Hua-Song Ai; Cheng-Piao Lu; Jia-Bin Li (Chromosome Research, 2020)

Spatial and Temporal Evolution Characteristics of PM2.5 in China from 1998 to 2016 - Hua Li; Helong Tong; Xianhua Wu; Xiaoli Lu; Shuhan Meng (Chinese Geographical Science, 2020)

Sphingosylphosphorylcholine alleviates hypoxia-caused apoptosis in cardiac myofibroblasts via CaM/p38/STAT3 pathway - Ying Li; Qi Qi; Wan-cheng Yang; Tian-liang Zhang; Chen-chen Lu; Yu-juan Yao; Wei-hua Kong; Jing Zhao (Apoptosis, 2020)

A pair of new diastereoisomeric phenylpropanoid-substituted flavan from the leaves of Ilex centrochinensis - Hui Long; Yu Chen; Ze-Hua Hu; Shao-Jun Zhang; Lu-Jun Li (Natural Product Research, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Noise does not equal bias in assessing the evolutionary history of the angiosperm flora of China: A response to Qian (2019) - Li‐Min Lu; Hai‐Hua Hu; Dan‐Xiao Peng; Bing Liu; Jian‐Fei Ye; Tuo Yang; Hong‐Lei Li; Miao Sun; Stephen A. Smith; Pamela S. Soltis; Douglas E. Soltis; Zhi‐Duan Chen (Journal of Biogeography, 2020)
In response to our paper on the evolutionary history of the Chinese flora, Qian suggests that certain features of the divergence time estimation employed might have led to biased conclusions in Lu et al (2018). Here, we consider Qian's specific criticisms, explore the extent of uncertainty in the data and demonstrate that (i) no systematic bias toward dates that are too young or too old is detected in Lu et al.; (ii) constraint of the crown age of angiosperms does not bias the generic ages estimated by Lu et al.; and (iii) ages derived from the Chinese regional phylogeny do not bias the conclusions reported by Lu et al. All these analyses confirm that the conclusions reported previously are robust. We argue that, like many large‐scale biodiversity analyses, sources of noise in divergence time estimation are to be expected, but these should not be confused with bias.

Depletion of florfenicol and florfenicol amine in eggs of laying hens and growing pullets after oral administration - Xia Li; Lu Chen; Hui Yue; Hua Feng; Enmin Xu; Xiuli Wei; Xiaoli Han; Ligang Deng; Zengmei Li (Food Additives & Contaminants: Part A, 2020)

Prediction of loess soil-water characteristic curve by mercury intrusion porosimetry - Hua Li; Tong-lu Li; Ping Li; Ya-guo Zhang (Journal of Mountain Science, 2020)

Four pairs of proline-containing cyclic dipeptides from Nocardiopsis sp. HT88, an endophytic bacterium of Mallotus nudiflorus L - Wen-Xin Xiang; Qing Liu; Xiao-Man Li; Chun-Hua Lu; Yue-Mao Shen (Natural Product Research, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

MicroRNA-153-3p enhances the sensitivity of chronic myeloid leukemia cells to imatinib by inhibiting B-cell lymphoma-2-mediated autophagy - Yu-Ling Li; Jia-Ming Tang; Xiao-Yun Chen; Bing Luo; Guo-Hua Liang; Qian Qu; Zi-Yuan Lu (Human Cell, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Genome-wide identification of the NPR1-like gene family in Brassica napus and functional characterization of BnaNPR1 in resistance to Sclerotinia sclerotiorum - Zheng Wang; Lu-Yue Ma; Xiao Li; Feng-Yun Zhao; Rehman Sarwar; Jun Cao; Yu-Long Li; Li-Na Ding; Ke-Ming Zhu; Yan-Hua Yang; Xiao-Li Tan (Plant Cell Reports, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Analysis of an improved workflow of endoscope reprocessing for bedside endoscopic diagnosis and treatment on COVID-19 patients - Qing Gu; Hua-fen Wang; Ying Fang; Ye Lu; Zhe Shen; Yan Wang; Xin Wu; Li Cen; Yi-shu Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Efficacy of internet-based integrated intervention on depression and anxiety symptoms in patients with COVID-19 - Ning Wei; Bo-chao Huang; Shao-jia Lu; Jian-bo Hu; Xiao-yi Zhou; Chan-chan Hu; Jing-kai Chen; Jin-wen Huang; Shu-guang Li; Zheng Wang; Dan-dan Wang; Yi Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Dialectical behavior therapy-based psychological intervention for woman in late pregnancy and early postpartum suffering from COVID-19: a case report - Jin-wen Huang; Xiao-yi Zhou; Shao-jia Lu; Yi Xu; Jian-bo Hu; Man-li Huang; Hua-fen Wang; Chan-chan Hu; Shu-guang Li; Jing-kai Chen; Zhong Wang; Shao-hua Hu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Exogenous salicylic acid alleviates halosulfuron-methyl toxicity by coordinating the antioxidant system and improving photosynthesis in soybean (Glycine max Merr.) - Yuan-Fu Li; Lu-Lu Huang; Xiao-Liang Liu; Xue-Sheng Li; Hui-Hua Tan (Acta Physiologiae Plantarum, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

Lipocalin-2 Predicts Long-Term Outcome of Normotensive Patients with Acute Pulmonary Embolism - Haixu Yu; Zhuohui Liu; Jie Lu; Xinying Yang; Xin-Xin Yan; Yuhong Mi; Lu Hua; Yulin Li; Zhi-Cheng Jing; Jie Du (Cardiovascular Toxicology, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Primary age-related tauopathy in a Chinese cohort - Xin Wang; Lei Zhang; Hui Lu; Juan-li Wu; Hua-zheng Liang; Chong Liu; Qing-qing Tao; Zhi-ying Wu; Ke-qing Zhu (Journal of Zhejiang University-SCIENCE B, 2020)

Quantitative proteomic analysis reveals that the Rap1/MAPK/ERK pathway is inhibited through selenomethionine strengthening antioxidant activity - Zhe Liu; Feng Zhang; Lina Cui; Jihong Wang; Ping Lu; Rui Zhao; Hua Zhang; Jianfa Wang; Chunqiu Li; Rui Wu (BioMetals, 2020)

Review of Chinese atmospheric science research over the past 70 years: Atmospheric physics and atmospheric environment - Tijian Wang; Taichang Gao; Hongsheng Zhang; Maofa Ge; Hengchi Lei; Peichang Zhang; Peng Zhang; Chunsong Lu; Chao Liu; Hua Zhang; Qiang Zhang; Hong Liao; et al. (Science China Earth Sciences, 2019)

Interaction Between Variations in Dopamine D2 and Serotonin 2A Receptor is Associated with Short-Term Response to Antipsychotics in Schizophrenia - Liansheng Zhao; Huijuan Wang; Yamin Zhang; Jinxue Wei; Peiyan Ni; Hongyan Ren; Gang Li; Qiang Wang; Gavin P Reynolds; Weihua Yue; Wei Deng; Hao Yan; et al. (Neuroscience Bulletin, 2019)

FAM20A is essential for amelogenesis, but is dispensable for dentinogenesis - Lili Li; Wuliji Saiyin; Hua Zhang; Suzhen Wang; Qian Xu; Chunlin Qin; Yongbo Lu (Journal of Molecular Histology, 2019)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Artemisinin suppresses hepatocellular carcinoma cell growth, migration and invasion by targeting cellular bioenergetics and Hippo-YAP signaling - Yujie Li; Jing Lu; Qin Chen; Shengnan Han; Hua Shao; Pingyi Chen; Qiumei Jin; Mingyue Yang; Fugen Shangguan; Mingming Fei; Lu Wang; Yongzhang Liu; et al. (Archives of Toxicology, 2019)

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

Traveltime tomography and prestack depth migration for vertical seismic profiling of an angle-domain walkaway on a complex surface - Jian-Guo Li; Xiao-Jie Cui; Jian-Hua Huang; Xiao-Lu Zhang; Yan-Peng Li (Applied Geophysics, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Dorsolateral striatal miR-134 modulates excessive methamphetamine intake in self-administering rats - Jing-Jing Shi; Dan-Ni Cao; Hui-Fen Liu; Zhi-Yuan Wang; Guan-Yi Lu; Ning Wu; Wen-Hua Zhou; Jin Li (Metabolic Brain Disease, 2019)

Selenium-Yeast Alleviated Inflammatory Damage Caused by Lead via Inhibiting Ras/ERK Pathway and Inflammatory Factors in Chicken Skeletal Muscles - Zhe Liu; Feng Zhang; Ping Lu; Rui Zhao; Hua Zhang; Baifen Song; Liyang Li; Zhijun Wu; Rui Wu (Biological Trace Element Research, 2019)

Proteomics analysis of HSV-1-induced alterations in mouse brain microvascular endothelial cells - Hui Liu; Chu-Xin Huang; Qiang He; Dong Li; Min-Hua Luo; Fei Zhao; Wei Lu (Journal of NeuroVirology, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Performance of Post-Processed Methods in Hydrological Predictions Evaluated by Deterministic and Probabilistic Criteria - Xiang-Quan Li; Jie Chen; Chong-Yu Xu; Lu Li; Hua Chen (Water Resources Management, 2019)

An H-ferritin from the hydrothermal vent shrimp Rimicaris exoculata and its potential role in iron metabolism - Xiao-Li Liu; Sen Ye; Hua-Wei Li; Bo Lu; Yan-Qin Yu; Yu-Peng Fan; Wei-Jun Yang; Jin-Shu Yang (BioMetals, 2019)

Bone morphogenetic proteins and inner ear development - Jiao-yao Ma; Dan You; Wen-yan Li; Xiao-ling Lu; Shan Sun; Hua-wei Li (Journal of Zhejiang University-SCIENCE B, 2019)

An Assessment of ENSO Stability in CAMS Climate System Model Simulations - Lijuan Hua; Lin Chen; Xinyao Rong; Jian Li; Guo Zhang; Lu Wang (Journal of Meteorological Research, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

Retraction Note to: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Reconstruction of Y-chromosome phylogeny reveals two neolithic expansions of Tibeto-Burman populations - Ling-Xiang Wang; Yan Lu; Chao Zhang; Lan-Hai Wei; Shi Yan; Yun-Zhi Huang; Chuan-Chao Wang; Swapan Mallick; Shao-Qing Wen; Li Jin; Shu-Hua Xu; Hui Li (Molecular Genetics and Genomics, 2018)

Impact of atmospheric model resolution on simulation of ENSO feedback processes: a coupled model study - Lijuan Hua; Lin Chen; Xinyao Rong; Jingzhi Su; Lu Wang; Tim Li; Yongqiang Yu (Climate Dynamics, 2018)

Identification of Neoscytalidium dimidiatum causing canker disease of pitaya in Hainan, China - Min Xu; Yun Peng; Zhao Qi; Zhen Yan; Lu Yang; Meng-Die He; Qing-Xiu Li; Cheng-Li Liu; Yun-Ze Ruan; Shuang-Shuang Wei; Jun Xie; You-Quan Xia; et al. (Australasian Plant Pathology, 2018)

RETRACTED ARTICLE: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

Neonatal Exposure to Low-Dose (1.2%) Sevoflurane Increases Rats’ Hippocampal Neurogenesis and Synaptic Plasticity in Later Life - Xi Chen; Xue Zhou; Lu Yang; Xu Miao; Di-Han Lu; Xiao-Yu Yang; Zhi-Bin Zhou; Wen-Bin Kang; Ke-Yu Chen; Li-Hua Zhou; Xia Feng (Neurotoxicity Research, 2018)

Organochlorine pesticides in soils from the Issyk-Kul region in the western Tian Shan Mountains, Kyrgyzstan: Implication for spatial distribution, source apportionment and ecological risk assessment - Qian-yu Li; Jing-lu Wu; Zhong-hua Zhao; Kadyrbek Sakiev (Journal of Mountain Science, 2018)

Whole sequence analysis indicates a recent southern origin of Mongolian Y-chromosome C2c1a1a1-M407 - Yun-Zhi Huang; Lan-Hai Wei; Shi Yan; Shao-Qing Wen; Chuan-Chao Wang; Ya-Jun Yang; Ling-Xiang Wang; Yan Lu; Chao Zhang; Shu-Hua Xu; Da-Li Yao; Li Jin; et al. (Molecular Genetics and Genomics, 2018)

The effects of CXCL10 polymorphisms on COPD susceptibility - Yan Wang; Qipeng Zhou; Lian Dong; Mingmei Xiong; Hua Jiang; Meihua Guo; Li Zhao; Liang Yuan; Ziying Li; Hanwei Liu; Jian Wang; Nanshan Zhong; et al. (Molecular Genetics and Genomics, 2018)

Protection of plasma transfusion against lipopolysaccharide/d-galactosamine-induced fulminant hepatic failure through inhibiting apoptosis of hepatic cells in mice - Bing-yu Chen; Lu-xi Jiang; Ke Hao; Lu Wang; Ying Wang; Yi-wei Xie; Jian Shen; Meng-hua Zhu; Xiang-ming Tong; Kai-qiang Li; Zhen Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Isolation and characterization of 33 EST-SNP markers in Schizothorax prenanti - Jian Zhou; Bo Zhou; Qiang Li; Lu Zhang; Jun Du; Hua Ye (Conservation Genetics Resources, 2018)

Genome-wide analysis and expression profiling of the HMA gene family in Brassica napus under cd stress - Nannan Li; Hua Xiao; Juanjuan Sun; Shufeng Wang; Jingchao Wang; Peng Chang; Xinbin Zhou; Bo Lei; Kun Lu; Feng Luo; Xiaojun Shi; Jiana Li (Plant and Soil, 2018)

Selective toxicity of the mesoionic insecticide, triflumezopyrim, to rice planthoppers and beneficial arthropods - Jun Zhu; Yao Li; Hua Jiang; Chen Liu; Weiwei Lu; Wei Dai; Jianxiang Xu; Fang Liu (Ecotoxicology, 2018)

Long non-coding RNA p10247, high expressed in breast cancer (lncRNA-BCHE), is correlated with metastasis - Yu-Xia Yang; Li Wei; Yan-Ju Zhang; Takahide Hayano; María del Pilar Piñeiro Pereda; Hirofumi Nakaoka; Qiang Li; Isabel Barragán Mallofret; Yuan-Zhi Lu; Luca Tamagnone; Ituro Inoue; Xiangdong Li; et al. (Clinical & Experimental Metastasis, 2018)

Complete nucleotide sequence of jasmine virus H, a new member of the family Tombusviridae - Tao Zhuo; Li-Juan Zhu; Cheng-Cong Lu; Chao-Yang Jiang; Zi-Yin Chen; Guangzhi Zhang; Zong-Hua Wang; Juan Jovel; Yan-Hong Han (Archives of Virology, 2018)

Short hairpin RNA interference targeting interleukin 1 receptor type I in the paraventricular nucleus attenuates hypertension in rats - Peng Lu; Shu-jun Jiang; Hong Pan; Ai-li Xu; Gui-hua Wang; Chun-lei Ma; Zhen Shi (Pflügers Archiv - European Journal of Physiology, 2018)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Erratum to: Effects of elicitors on trichothecene accumulation and Tri genes expression in potato tubers inoculated with Fusarium sulphureum - Xue Hua-Li; Bi Yang; Zong Yuan-Yuan; Alejandro Calderón-Urrea; Wang Hu-Jun; Pu Lu-Mei; Wang Yi; Li Yong-Cai (European Journal of Plant Pathology, 2017)

Cytotoxicity of anti-tumor herbal Marsdeniae tenacissimae extract on erythrocytes - Ke Hao; Bing-yu Chen; Kai-qiang Li; Yu Zhang; Cai-xia Li; Ying Wang; Lu-xi Jiang; Jiang Shen; Xiang-chai Guo; Wei Zhang; Meng-hua Zhu; Zhen Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of elicitors on trichothecene accumulation and Tri genes expression in potato tubers inoculated with Fusarium sulphureum - Xue Hua-Li; Bi Yang; Zong Yuan-Yuan; Alejandro Calderón-Urrea; Wang Hu-Jun; Pu Lu-Mei; Wang Yi; Li Yong-Cai (European Journal of Plant Pathology, 2017)

Endogenously generated amyloid-β increases stiffness in human neuroblastoma cells - Zhuoyang Lu; Hua Li; Chen Hou; Yunhua Peng; Jiangang Long; Jiankang Liu (European Biophysics Journal, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Three-dimensional tomography using high-power induced polarization with the similar central gradient array - Jun-Lu Wang; Pin-Rong Lin; Meng Wang; Dang Li; Jian-Hua Li (Applied Geophysics, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Mice lacking myotubularin-related protein 14 show accelerated high-fat diet-induced lipid accumulation and inflammation - Lv Yin; Peng Yong-bo; Yu Meng-Fei; Chen Weiwei; Zhao Ping; Xue Lu; Ma Li-Qun; Cai Congli; Liu Qing-hua; Shen Jinhua (Journal of Physiology and Biochemistry, 2017)

Genetic variation in mitochondrial genes of the tick Haemaphysalis flava collected from wild hedgehogs in China - Zhong-Bo Li; Tian-Yin Cheng; Xing-Li Xu; Lu-Lin Song; Guo-Hua Liu (Experimental and Applied Acarology, 2017)

Two new sesquiterpenoids produced by halophilic Nocardiopsis chromatogenes YIM 90109 - Ming-Wei Sun; Xiao-Mei Zhang; Hui-Li Bi; Wen-Jun Li; Chun-Hua Lu (Natural Product Research, 2017)

RAS Promotes Proliferation and Resistances to Apoptosis in Meningioma - Chunling Jiang; Tao Song; Jingao Li; Fan Ao; Xiaochang Gong; Yicheng Lu; Chenran Zhang; Liangyu Chen; Yunhui Liu; Hua He; Ouping Huang (Molecular Neurobiology, 2017)

Geochemistry of fine-grained clastic rocks in the Mesoproterozoic Kawabulake Group: implications for provenance and the tectonic model of the Eastern Tianshan, Xinjiang, NW China - Deng-Feng Li; Hua-Yong Chen; Li Zhang; Philip Fralick; Pete Hollings; Mei Mi; Wan-Jian Lu; Jin-Sheng Han; Cheng-Ming Wang; Jing Fang (International Journal of Earth Sciences, 2017)

Contamination, Fractionation and Biological Risk Related to Metals in Surface Sediments from the Largest Deep Freshwater Lake in China - Hua-Bing Li; Yang-Guang Gu; Rong Wang; Hui-Bin Lu (Archives of Environmental Contamination and Toxicology, 2017)

Developing a rat model of dilated cardiomyopathy with improved survival - Li-juan Shen; Shu Lu; Yong-hua Zhou; Lan Li; Qing-min Xing; Yong-liang Xu (Journal of Zhejiang University-SCIENCE B, 2016)

Population distribution and urbanization on both sides of the Hu Huanyong Line: Answering the Premier’s question - Mingxing Chen; Yinghua Gong; Yang Li; Dadao Lu; Hua Zhang (Journal of Geographical Sciences, 2016)

Risk factors for death in children with severe hand, foot, and mouth disease in Hunan, China - Lu Long; Li-Dong Gao; Shi-Xiong Hu; Kai-Wei Luo; Zhen-Hua Chen; Carine Ronsmans; Ding-Lun Zhou; Ya-Jia Lan (Infectious Diseases, 2016)

Sonic Hedgehog Signaling Affected by Promoter Hypermethylation Induces Aberrant Gli2 Expression in Spina Bifida - Xiao-Lin Lu; Li Wang; Shao-Yan Chang; Shao-Fang Shangguan; Zhen Wang; Li-Hua Wu; Ji-Zhen Zou; Ping Xiao; Rui Li; Yi-Hua Bao; Z-Y Qiu; Ting Zhang (Molecular Neurobiology, 2016)

Genetic alterations of δ-catenin/NPRAP/Neurojungin (CTNND2): functional implications in complex human diseases - Qun Lu; Byron J. Aguilar; Mingchuan Li; Yongguang Jiang; Yan-Hua Chen (Human Genetics, 2016)

Estimating cropland carbon mitigation potentials in China affected by three improved cropland practices - Fei Lun; Josep G. Canadell; Lu He; Bo Yang; Mou-cheng Liu; Zheng Yuan; Mi Tian; Jun-guo Liu; Wen-hua Li (Journal of Mountain Science, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Optimization of the Expression Conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by Response Surface Methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Effects of resistant and susceptible rubber germplasms on development, reproduction and protective enzyme activities of Eotetranychus sexmaculatus (Acari: Tetranychidae) - Fuping Lu; Zhishui Chen; Hui Lu; Xiao Liang; Huiying Zhang; Qian Li; Qing Chen; Huasun Huang; Yuwei Hua; Weimin Tian (Experimental and Applied Acarology, 2016)

Late Quaternary glacial advances in the eastern Qilianshan, north‐eastern Tibet, as inferred from luminescence dating of fluvioglacial sediments - Gang Hu; Chao‐Lu Yi; Jia‐Fu Zhang; Jin‐Hua Liu; Tao Jiang; Sheng‐Hua Li (Journal of Quaternary Science, 2016)
The Qilianshan [ shan means ‘mountain(s)’ in Chinese] are important for understanding the Quaternary glaciations which occurred along the north‐eastern margins of the Tibetan Plateau (TP). Two sets of moraines identified in the Gangshika Valley on the southern slopes of the Qilianshan, and in the Jindonggou Valley on the northern slopes of the Lenglongling Ridge in the eastern Qilianshan, were dated using optically stimulated luminescence (OSL) dating. The D e values of the sediments were determined using single aliquot regeneration (SAR) and ‘global standardized growth curve’ (gSGC) procedures. The gSGC method was first applied to glacial sediment and proved to be adaptable. Based on D e distribution analysis, and a comparison between the ages of coarse‐grained (90–125 μm) quartz, we concluded that the minimum age model (MAM) OSL age obtained may be closer to the burial age of the sediments. The first set of moraines in the Gangshika Valley was formed at 18.1 ± 1.8 ka. The second set of moraines in both the Gangshika and the Jindonggou valleys was mainly formed at ∼12.5–10.7 ka, consistent with the Younger Drays chronozone, most probably covering the moraines produced at 14.3 ± 1.4 ka. These results indicate that the glaciers along the Lenglongling Ridge were sensitive to abrupt decreases in temperature.

Biogeographical diversification of mainland Asian Dendrobium (Orchidaceae) and its implications for the historical dynamics of evergreen broad‐leaved forests - Xiao‐Guo Xiang; Xiang‐Cheng Mi; Hai‐Lang Zhou; Jian‐Wu Li; Shih‐Wen Chung; De‐Zhu Li; Wei‐Chang Huang; Wei‐Tao Jin; Zhen‐Yu Li; Lu‐Qi Huang; Xiao‐Hua Jin (Journal of Biogeography, 2016)
Aim Evergreen broad‐leaved forests ( EBLF s) occupy most tropical and subtropical regions of mainland Asia and exhibit high species diversity, productivity and richness. Understanding the historical dynamics of EBLF s is important for biodiversity conservation and regional carbon storage and cycling under global climate change. However, little is known about the historical dynamics of EBLF s in mainland Asia. Dendrobium , an epiphytic orchid genus found in EBLF s, was used to gain new insights of the historical establishment and extension of EBLF s in mainland Asia. Location Mainland Asia. Methods We sampled c . 80% of the currently recognized species of Dendrobium found in mainland Asia. A phylogeny was generated using maximum parsimony, maximum likelihood and Bayesian inference methods. A calibrated chronogram was obtained using a Bayesian relaxed‐clock model approach. Biogeographical scenarios were investigated using the statistical dispersal–vicariance analysis and dispersal–extinction–cladogenesis methods. Ancestral states were constructed by mesquite and bayestraits , and diversification of Dendrobium was investigated by APE and LASER packages. Results Our results indicate that Asian Dendrobium was present on mainland Asia since the Oligocene, after which this genus diversified in this region and dispersed into higher elevations. The ancestral habit of Dendrobium was epiphytic and terrestrial and lithophytic habits each have multiple, recently independent origins. Main conclusions Our results support the hypothesis that EBLF s have been established in mainland Asia at least since the Oligocene and further suggest that the EBLF s of mainland Asia expanded into higher elevations prior to the late Cenozoic. The diversification of Asian Dendrobium coincided with a warmer climate during the late Oligocene and middle Miocene and the expansion of key groups (including Fagaceae, Lauraceae, Magnoliaceae and Theaceae) of EBLF s during the early Cenozoic.

The Intra-familial Relationships of Pentaphylacaceae s.l. as Revealed by DNA Sequence Analysis - Chih-hua Tsou; Lu Li; Kunjupillai Vijayan (Biochemical Genetics, 2016)

Calpain-Dependent ErbB4 Cleavage Is Involved in Brain Ischemia-Induced Neuronal Death - Ying-mei Lu; Yin-ping Gao; Rong-rong Tao; Mei-hua Liao; Ji-yun Huang; Gang Wu; Feng Han; Xiao-ming Li (Molecular Neurobiology, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Novel Development of a qPCR Assay Based on the rpoB Gene for Rapid Detection of Cronobacter spp. - Yuanhong Li; Qiming Chen; Hua Jiang; Yang Jiao; Fengxia Lu; Xiaomei Bie; Zhaoxin Lu (Current Microbiology, 2016)

Glucose-Based Mesoporous Carbon Nanospheres as Functional Carriers for Oral Delivery of Amphiphobic Raloxifene: Insights into the Bioavailability Enhancement and Lymphatic Transport - Yanghuan Ye; Tianpeng Zhang; Wan Li; Hua Sun; Danyi Lu; Baojian Wu; Xingwang Zhang (Pharmaceutical Research, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Low temperature destruction of PCDD/Fs by catalysis coupled with activated carbon - Ming-feng Yu; Xiao-dong Li; Tong Chen; Sheng-yong Lu; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

JA, a new type of polyunsaturated fatty acid isolated from Juglans mandshurica Maxim, limits the survival and induces apoptosis of heptocarcinoma cells - Xiu-Li Gao; Hua Lin; Wei Zhao; Ya-Qin Hou; Yong-Li Bao; Zhen-Bo Song; Lu-Guo Sun; Shang-Yi Tian; Biao Liu; Yu-Xin Li (Apoptosis, 2016)

Identification and topographical characterisation of microbial nanowires in Nostoc punctiforme - Sandeep Sure; Angel A. J. Torriero; Aditya Gaur; Lu Hua Li; Ying Chen; Chandrakant Tripathi; Alok Adholeya; M. Leigh Ackland; Mandira Kochar (Antonie van Leeuwenhoek, 2016)

Effects of salinity on activity and expression of enzymes involved in ionic, osmotic, and antioxidant responses in Eurya emarginata - Jia-Lang Zheng; Lu-Yao Zhao; Bin Shen; Li-Hua Jiang; Ai-Yi Zhu (Acta Physiologiae Plantarum, 2016)

Programmed Death Ligand-1 on Microglia Regulates Th1 Differentiation via Nitric Oxide in Experimental Autoimmune Encephalomyelitis - Jingxia Hu; Hao He; Zhengang Yang; Guangming Zhu; Li Kang; Xiuli Jing; Hai Lu; Wengang Song; Bo Bai; Hua Tang (Neuroscience Bulletin, 2016)

Bioinformatics analysis and expression of a novel protein ROP48 in Toxoplasma gondii - Jian Zhou; Lin Wang; Aihua Zhou; Gang Lu; Qihang Li; Zhilin Wang; Meiyan Zhu; Huaiyu Zhou; Hua Cong; Shenyi He (Acta Parasitologica, 2016)
is an obligate intracellular apicomplexan parasite, and can infect warmblooded animals and humans all over the world. In the past years, ROP family genes encoding particular proteins of

Morphology-dependent antimicrobial activity of Cu/CuxO nanoparticles - Lu Xiong; Zhong-Hua Tong; Jie-Jie Chen; Ling-Li Li; Han-Qing Yu (Ecotoxicology, 2015)

Associations of hypoxia inducible factor-1α gene polymorphisms with susceptibility to digestive tract cancers: a case–control study and meta-analysis - Zhi-Hai Ni; Xian-Jun Liang; Jing-Gang Mo; Yi Zhang; Jian-Hua Liang; Yu-Sha Yang; Yong Zhou; Zhao-Hua Li; Jian-Liang Zhang; Yin-Lu Ding; Peng Zhang; Jin-Qing Wang (Genes & Genomics, 2015)

Inquisition of Microcystis aeruginosa and Synechocystis nanowires: characterization and modelling - Sandeep Sure; Angel A. J. Torriero; Aditya Gaur; Lu Hua Li; Ying Chen; Chandrakant Tripathi; Alok Adholeya; M. Leigh Ackland; Mandira Kochar (Antonie van Leeuwenhoek, 2015)

Validation of a practical normalized soil moisture model with in situ measurements in humid and semi-arid regions - Dianjun Zhang; Zhao-Liang Li; Ronglin Tang; Bo-Hui Tang; Hua Wu; Jing Lu; Kun Shao (International Journal of Remote Sensing, 2015)

Integrating two layers of soil moisture parameters into the MOD16 algorithm to improve evapotranspiration estimations - Su-Chuang Di; Zhao-Liang Li; Ronglin Tang; Hua Wu; Bo-Hui Tang; Jing Lu (International Journal of Remote Sensing, 2015)

Antioxidative responses of Pseudomonas fluorescens YZ2 to simultaneous exposure of Zn and Cefradine - Yan-Bin Xu; Jia-Xin Xu; Jin-Liang Chen; Lu Huang; Shao-Qi Zhou; Yan Zhou; Li-Hua Wen (Ecotoxicology, 2015)

Effects of cold acclimation on sugar metabolism and sugar-related gene expression in tea plant during the winter season - Chuan Yue; Hong-Li Cao; Lu Wang; Yan-Hua Zhou; Yu-Ting Huang; Xin-Yuan Hao; Yu-Chun Wang; Bo Wang; Ya-Jun Yang; Xin-Chao Wang (Plant Molecular Biology, 2015)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Effects of glucose, insulin and triiodothyroxine on leptin and leptin receptor expression and the effects of leptin on activities of enzymes related to glucose metabolism in grass carp (Ctenopharyngodon idella) hepatocytes - Rong-Hua Lu; Yi Zhou; Xiao-Chen Yuan; Xu-Fang Liang; Liu Fang; Xiao-Li Bai; Min Wang; Yu-Hua Zhao (Fish Physiology and Biochemistry, 2015)

Loss of Egr-1 sensitizes pancreatic β-cells to palmitate-induced ER stress and apoptosis - Mun-Wai Cheong; Li-Hua Kuo; Yi-Ning Cheng; Pei-Jane Tsai; Li-Chun Ho; Haw-Chih Tai; Wen-Tai Chiu; Shun-Hua Chen; Pei-Jung Lu; Yan-Shen Shan; Lee-Ming Chuang; Yau-Sheng Tsai (Journal of Molecular Medicine, 2015)

Water relations and gas exchange of fan bryophytes and their adaptations to microhabitats in an Asian subtropical montane cloud forest - Liang Song; Yong-Jiang Zhang; Xi Chen; Su Li; Hua-Zheng Lu; Chuan-Sheng Wu; Zheng-Hong Tan; Wen-Yao Liu; Xian-Meng Shi (Journal of Plant Research, 2015)

Relative Bioavailability of Zinc-Methionine Chelate for Broilers Fed a Conventional Corn–Soybean Meal Diet - Haiqing Suo; Lin Lu; Liyang Zhang; Xueyuan Zhang; Hua Li; Yufei Lu; Xugang Luo (Biological Trace Element Research, 2015)

Cytokine production suppression by culture supernatant of B16F10 cells and amelioration by Ganoderma lucidum polysaccharides in activated lymphocytes - Li-Xin Sun; Wei-Dong Li; Zhi-Bin Lin; Xin-Suo Duan; En-Hong Xing; Miao-Miao Jiang; Ning Yang; Hai-Hua Qi; Yu Sun; Min Li; Yan-Dong Niu; Jie Lu (Cell and Tissue Research, 2015)

Two new triterpenoid saponins obtained by microbial hydrolysis with Alternaria alternata AS 3.6872 - Li-Hua Mu; Yong-Jie Gu; Bai-Ping Ma; Li Lu; Ping Liu (Natural Product Research, 2015)

In vivo expression patterns of microRNAs of Gallid herpesvirus 2 (GaHV-2) during the virus life cycle and development of Marek’s disease lymphomas - Pu Zhao; Xiu-Jie Li; Man Teng; Lu Dang; Zu-Hua Yu; Jia-Qi Chi; Jing-Wei Su; Gai-Ping Zhang; Jun Luo (Virus Genes, 2015)

A maize phytochrome-interacting factor 3 improves drought and salt stress tolerance in rice - Yong Gao; Wei Jiang; Yi Dai; Ning Xiao; Changquan Zhang; Hua Li; Yi Lu; Meiqin Wu; Xiaoyi Tao; Dexiang Deng; Jianmin Chen (Plant Molecular Biology, 2015)

Optimization of the expression conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by response surface methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Kidney Transplantation from Pediatric Donors in a Single Chinese Center - Jin-feng Li; Jia Liu; Tao Guo; Xin-lu Pang; Lei Liu; Yong-hua Feng; Zhi-gang Wang; Gui-wen Feng; Wen-jun Shang (Cell Biochemistry and Biophysics, 2014)

Temperature Affects Hg-Induced Antioxidant Responses in Chinese Rare Minnow Gobiocypris rarus Larvae In Vitro - Zhi-Hua Li; Ping Li; Lu Chen (Bulletin of Environmental Contamination and Toxicology, 2014)

A mutation of Aspergillus niger for hyper-production of citric acid from corn meal hydrolysate in a bioreactor - Wei Hu; Jing Liu; Ji-hong Chen; Shu-yang Wang; Dong Lu; Qing-hua Wu; Wen-jian Li (Journal of Zhejiang University-SCIENCE B, 2014)

miR-1246 releases RTKN2-dependent resistance to UVB-induced apoptosis in HaCaT cells - Wei Li; Ya-Fen Wu; Rong-Hua Xu; Hui Lu; Cui Hu; Hua Qian (Molecular and Cellular Biochemistry, 2014)

Fungus Exposed Solenopsis invicta Ants Benefit from Grooming - Hua-long Qiu; Li-hua Lu; Qing-xing Shi; Yu-rong He (Journal of Insect Behavior, 2014)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

Effects of Mercury on Oxidative Stress and Gene Expression of Potential Biomarkers in Larvae of the Chinese Rare Minnow Gobiocypris Rarus - Zhi-Hua Li; Lu Chen; Yan-Hua Wu; Ping Li; Yun-Feng Li; Zhao-Hui Ni (Archives of Environmental Contamination and Toxicology, 2014)

Remotely sensing the ecological influences of ditches in Zoige Peatland, eastern Tibetan Plateau - Wenjiang Zhang; Qifeng Lu; Kechao Song; Guanghua Qin; Yan Wang; Xin Wang; Hongxia Li; Jun Li; Guodong Liu; Hua Li (International Journal of Remote Sensing, 2014)

Cosuppression of RBCS3B in Arabidopsis leads to severe photoinhibition caused by ROS accumulation - Gao-Miao Zhan; Rong-Jun Li; Zhi-Yong Hu; Jing Liu; Lin-Bin Deng; Shi-You Lu; Wei Hua (Plant Cell Reports, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Evaluating the Effects of Silent Discharge Plasma on Remediation of Acid Scarlet GR-Contaminated Soil - Na Lu; Jing Lou; Cui Hua Wang; Jie Li; Yan Wu (Water, Air, & Soil Pollution, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Residential energy consumption and associated carbon emission in forest rural area in China: A case study in Weichang County - Fei Lun; Josep G. Canadell; Zhong-qi Xu; Lu He; Zheng Yuan; Dan Zhang; Wen-hua Li; Mou-cheng Liu (Journal of Mountain Science, 2014)

Application of T-DNA activation tagging to identify glutamate receptor-like genes that enhance drought tolerance in plants - Guihua Lu; Xiping Wang; Junhua Liu; Kun Yu; Yang Gao; Haiyan Liu; Changgui Wang; Wei Wang; Guokui Wang; Min Liu; Guanfan Mao; Binfeng Li; et al. (Plant Cell Reports, 2014)

Multi-mode PolInSAR experiments using an airborne X-band SAR system in China - Li-Jun Lu; Ji-Xian Zhang; Fen-Fen Hua; Guo-Man Huang (International Journal of Remote Sensing, 2014)

Neuroprotective Effects of Bis(7)-tacrine in a Rat Model of Pressure-Induced Retinal Ischemia - Jing-bo Li; Zhi-gang Lu; Li Xu; Qi Wang; Zu-hai Zhang; Jia-hua Fang (Cell Biochemistry and Biophysics, 2014)

Synthesis, antibacterial activity, antibacterial mechanism and food applications of ZnO nanoparticles: a review - Lu-E Shi; Zhen-Hua Li; Wei Zheng; Yi-Fan Zhao; Yong-Fang Jin; Zhen-Xing Tang (Food Additives & Contaminants: Part A, 2014)

Activation of mammalian target of rapamycin contributes to pain nociception induced in rats by BmK I, a sodium channel-specific modulator - Feng Jiang; Li-Ming Hua; Yun-Lu Jiao; Pin Ye; Jin Fu; Zhi-Jun Cheng; Gang Ding; Yong-Hua Ji (Neuroscience Bulletin, 2014)

Downregulation of miR-133 via MAPK/ERK signaling pathway involved in nicotine-induced cardiomyocyte apoptosis - Lu Wang; Xuelian Li; Yuhong Zhou; Hui Shi; Chaoqian Xu; Hua He; Shuxuan Wang; Xuehui Xiong; Yong Zhang; Zhimin Du; Ruixue Zhang; Yanjie Lu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Meta-analysis of the association of glutathione S-transferase T1 null/presence gene polymorphism with the risk of gastric carcinoma - Yuan-Biao Meng; Xiao-Yong Cai; Wen-Qi Lu; Li-Hua Yang; Ting-Qing Gan; Gregor P. C. Drummen (Molecular Biology Reports, 2014)

Giant plagioclase growth during storage of basaltic magma in Emeishan Large Igneous Province, SW China - Li-Lu Cheng; Zong-Feng Yang; Ling Zeng; Yu Wang; Zhao-Hua Luo (Contributions to Mineralogy and Petrology, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

A new indole alkaloidal glucoside from the aerial parts of Clematis terniflora DC. - Wen-Ting Li; Bing-Xian Yang; Wei Zhu; Ming-Hua Gong; Xiang-Dong Xu; Xiang-Hong Lu; Lian-Li Sun; Jing-Kui Tian; Lin Zhang (Natural Product Research, 2013)

Cloning and expression characterization of the chicken Piwil1 gene - Rong Chen; Guobin Chang; Aiqin Dai; Teng Ma; Fei Zhai; Mingxiu Xia; Lu Liu; Jianchao Li; Dengke Hua; Guohong Chen (Molecular Biology Reports, 2013)

Discovery of indeno[1,2- $$c$$ c ]quinoline derivatives as dual topoisomerases I/II inhibitors: Part 3 - Chih-Hua Tseng; Cherng-Chyi Tzeng; Chiao-Li Yang; Pei-Jung Lu; Yu-Peng Liu; Hui-Ling Chen; Chien-Yu Chen; Chia-Ning Yang; Yeh-Long Chen (Molecular Diversity, 2013)

Saccharopolyspora cavernae sp. nov., a novel actinomycete isolated from the Swallow Cave in Yunnan, south-west China - Juan Cheng; Yong-Guang Zhang; Wei Chen; Li Li; Dao-Feng Zhang; Hong-Fei Wang; Xin-Hua Lu; Yan-Qing Duan; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Association between SNPs in microRNA-machinery genes and tuberculosis susceptibility in Chinese Tibetan population - Xingbo Song; Siyue Li; MeiLang QuCuo; Yi Zhou; Xin Hu; Juan Zhou; Xiaojun Lu; Jun Wang; Wei Hua; Yuanxin Ye; Binwu Ying; Lanlan Wang (Molecular Biology Reports, 2013)

Association between CYP1A1 polymorphisms and esophageal cancer: a meta-analysis - Fang-Fang Shen; Fu-You Zhou; Qi-Si Xue; Ying Pan; Lu Zheng; Hua Zhang; Li-Dong Wang; Hou-Feng Zheng (Molecular Biology Reports, 2013)

Experimental study on dynamic properties and constitutive model of polypropylene fibre concrete under high-strain rates - Hua Zhang; Yuwei Gao; Fei Li; Feng Lu; Hao Sun (European Journal of Environmental and Civil Engineering, 2013)

A chloroplast membrane protein LTO1/AtVKOR involving in redox regulation and ROS homeostasis - Ying Lu; Hua-Rong Wang; Han Li; Hao-Ran Cui; Yue-Guang Feng; Xiao-Yun Wang (Plant Cell Reports, 2013)

Development and evaluation of multi-genotype varieties of rice derived from MAGIC lines - Xiao-Fang Li; Zhi-Xia Liu; Dong-Bo Lu; Yan-Zhuo Liu; Xing-Xue Mao; Zhi-Xin Li; Hua-Jun Li (Euphytica, 2013)

Microlunatus cavernae sp. nov., a novel actinobacterium isolated from Alu ancient cave, Yunnan, south-west China - Juan Cheng; Wei Chen; Bing Huo-Zhang; Salam Nimaichand; En-Min Zhou; Xin-Hua Lu; Hans-Peter Klenk; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Lack of association between SLCO1B1 polymorphism and the lipid-lowering effects of atorvastatin and simvastatin in Chinese individuals - Qiang Fu; Yan-Peng Li; Yuan Gao; Song-Hua Yang; Pei-Qi Lu; Min Jia; Li-Rong Zhang (European Journal of Clinical Pharmacology, 2013)

Halalkalicoccus paucihalophilus sp. nov., a halophilic archaeon from Lop Nur region in Xinjiang, northwest of China - Bing-Bing Liu; Shu-Kun Tang; Yong-Guang Zhang; Xin-Hua Lu; Li Li; Juan Cheng; Yuan-Ming Zhang; Li-Li Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Enhancing production of a 24-membered ring macrolide compound by a marine bacterium using response surface methodology - Hua Chen; Mian-bin Wu; Zheng-jie Chen; Ming-lu Wang; Jian-ping Lin; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Characterizing the interactions between polycyclic aromatic hydrocarbons and fulvic acids in water - Rui Lu; Guo-Ping Sheng; Yi Liang; Wei-Hua Li; Zhong-Hua Tong; Wei Chen; Han-Qing Yu (Environmental Science and Pollution Research, 2013)

Genetic diversity of Bartonella quintana in macaques suggests zoonotic origin of trench fever - Hao Li; Jie‐Ying Bai; Li‐Yuan Wang; Lin Zeng; Yan‐Sheng Shi; Zheng‐Liang Qiu; Hua‐Hu Ye; Xiao‐Fei Zhang; Qing‐Bin Lu; Michael Kosoy; Wei Liu; Wu‐Chun Cao (Molecular Ecology, 2013)
Bartonella quintana is a bacterium that causes a broad spectrum of diseases in humans including trench fever. Humans were previously considered to be the primary, if not the only, reservoir hosts for B. quintana . To identify the animal reservoir and extend our understanding of the ecological and evolutionary history of B. quintana , we examined blood samples from macaques and performed multilocus sequence typing ( MLST ) analysis. We demonstrated the prevalence of B. quintana infection was common in macaques from main primate centres in mainland C hina. Overall, 18.0% (59/328) of rhesus macaques and 12.7% (39/308) of cynomolgus macaques were found to be infected with B. quintana by blood culture and/or polymerase chain reaction. The infection was more frequently identified in juvenile and young monkeys compared with adult animals. In contrast with the relatively low level of sequence divergence of B. quintana reported in humans, our investigation revealed much higher genetic diversity in nonhuman primates. We identified 44 new nucleotide variable sites and 14 novel sequence types (STs) among the B. quintana isolates by MLST analysis. Some STs were found only in cynomolgus macaques, while some others were detected only in rhesus macaques, suggesting evidence of host‐cospeciation, which were further confirmed by phylogenetic analysis and Splits decomposition analysis. Our findings suggest that trench fever may primarily be a zoonotic disease with macaques as the natural hosts.

Regulation of Neural Stem Cell Differentiation by Transcription Factors HNF4-1 and MAZ-1 - Jiao Wang; Hua Cheng; Xiao Li; Wei Lu; Kai Wang; Tieqiao Wen (Molecular Neurobiology, 2013)

Landscape pattern evolution processes of alpine wetlands and their driving factors in the Zoige Plateau of China - Jun-hong Bai; Qiong-qiong Lu; Jun-jing Wang; Qing-qing Zhao; Hua Ouyang; Wei Deng; Ai-nong Li (Journal of Mountain Science, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Autophagy appears during the development of the mouse lower first molar - Jing-wen Yang; Ling-xin Zhu; Guo-hua Yuan; Yang-xi Chen; Li Zhang; Lu Zhang; Zhi Chen (Histochemistry and Cell Biology, 2013)

Aggravated inflammation and increased expression of cysteinyl leukotriene receptors in the brain after focal cerebral ischemia in AQP4-deficient mice - Wen-Zhen Shi; Chun-Zhen Zhao; Bing Zhao; Qiao-Juan Shi; Li-Hui Zhang; Yan-Fang Wang; San-Hua Fang; Yun-Bi Lu; Wei-Ping Zhang; Er-Qing Wei (Neuroscience Bulletin, 2012)

The role of leptin in lipid metabolism in fatty degenerated hepatocytes of the grass carp Ctenopharyngodon idellus - Rong-Hua Lu; Xu-Fang Liang; Min Wang; Yi Zhou; Xiao-Li Bai; Yan He (Fish Physiology and Biochemistry, 2012)

Sequence and phylogenetic analysis of H7N3 avian influenza viruses isolated from poultry in China in 2011 - Wu Hai-bo; Lu Ru-feng; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Xu Li-hua; Wu Nan-ping; Guo Chao-tan (Archives of Virology, 2012)

Screening for significant atherosclerotic renal artery stenosis with a regression model in patients undergoing transradial coronary angiography/intervention - Li-jin Pu; Ying Shen; Rui-yan Zhang; Qi Zhang; Lin Lu; Feng-hua Ding; Jian Hu; Zheng-kun Yang; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2012)

Juglanthraquinone C, a novel natural compound derived from Juglans mandshurica Maxim, induces S phase arrest and apoptosis in HepG2 cells - Yao Yao; Yu-Wei Zhang; Lu-Guo Sun; Biao Liu; Yong-Li Bao; Hua Lin; Yu Zhang; Li-Hua Zheng; Ying Sun; Chun-Lei Yu; Yin Wu; Guan-Nan Wang; et al. (Apoptosis, 2012)

Increased expression of calcium-sensing receptors in atherosclerosis confers hypersensitivity to acute myocardial infarction in rats - Jin Guo; Hong-zhu Li; Lu-chuan Wang; Wei-hua Zhang; Guang-wei Li; Wen-jing Xing; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2012)

Sphingosine 1-phosphate acts as an activator for the porcine Gpr3 of constitutively active G protein-coupled receptors - Bao-le Zhang; Ye Li; Jian-hua Ding; Fu-lu Dong; Yan-jun Hou; Bao-chun Jiang; Fang-xiong Shi; Yin-xue Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Differential effects of paraoxonase 1 (PON1) polymorphisms on cancer risk: evidence from 25 published studies - Dai-Hua Fang; Cong-Hai Fan; Qiang Ji; Bo-Xiang Qi; Juan Li; Lu Wang (Molecular Biology Reports, 2012)

Genetic characterization of subtype H1 avian influenza viruses isolated from live poultry markets in Zhejiang Province, China, in 2011 - Hai-bo Wu; Chao-tan Guo; Ru-feng Lu; Li-hua Xu; En-kang Wo; Jin-biao You; Yi-ting Wang; Qiao-gang Wang; Nan-ping Wu (Virus Genes, 2012)

Characterization of a highly pathogenic H5N1 avian influenza virus isolated from ducks in Eastern China in 2011 - Wu Hai-bo; Guo Chao-tan; Lu Ru-feng; Xu Li-hua; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Wu Nan-ping (Archives of Virology, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Pathology of urethral fibromuscular system related to parturition-induced stress urinary incontinence and TGF-β1/Smad pathway - Guang-Yong Li; Wan-Shou Cui; Feng Zhou; Zhe-Zhu Gao; Hua Xin; Tao Liu; Wei-Ren Li; Yan-Qing Gong; Guang-Yi Bai; Ying-Lu Guo; Zhong-Cheng Xin (Molecular and Cellular Biochemistry, 2012)

The Group III Two-Component Histidine Kinase AlHK1 is Involved in Fungicides Resistance, Osmosensitivity, Spore Production and Impacts Negatively Pathogenicity in Alternaria longipes - Yi Yong Luo; Jin Kui Yang; Ming Liang Zhu; Chen Jian Liu; Hai Yan Li; Ze Bao Lu; Wen Zheng Pan; Zhong Hua Zhang; Wei Bi; Ke Qin Zhang (Current Microbiology, 2012)

Simulation of direct radiative forcing of aerosols and their effects on East Asian climate using an interactive AGCM-aerosol coupled system - Hua Zhang; Zhili Wang; Zaizhi Wang; Qianxia Liu; Sunling Gong; Xiaoye Zhang; Zhongping Shen; Peng Lu; Xiaodong Wei; Huizheng Che; Laurent Li (Climate Dynamics, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Glutamate carboxypeptidase II gene polymorphisms and neural tube defects in a high-risk Chinese population - Hua Xie; Jin Guo; Jianhua Wang; Fang Wang; Huizhi Zhao; Chi Liu; Li Wang; Xiaolin Lu; Lihua Wu; Yihua Bao; Jizhen Zou; Ting Zhang; et al. (Metabolic Brain Disease, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Quantitative structure-activity relationships of antimicrobial fatty acids and derivatives against Staphylococcus aureus - Hui Zhang; Lu Zhang; Li-juan Peng; Xiao-wu Dong; Di Wu; Vivian Chi-Hua Wu; Feng-qin Feng (Journal of Zhejiang University-SCIENCE B, 2012)

Clinical Study of Autologous Cytokine-Induced Killer Cells for the Treatment of Elderly Patients with Diffuse Large B-Cell Lymphoma - Xue-chun Lu; Bo Yang; Rui-li Yu; Xiao-hua Chi; Shuai Tuo; Chao-wei Tuo; Hong-li Zhu; Yao Wang; Chao-guang Jiang; Xiao-bing Fu; Yang Yang; Yang Liu; et al. (Cell Biochemistry and Biophysics, 2012)

Erratum to: Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Changes of Iron Stores and Duodenal Transepithelial Iron Transfer During Regular Exercise in Rats - Li-Long Che; De-Sheng Xiao; Hua-Xi Xu; Liwei Lu (Biological Trace Element Research, 2011)

Association of a LSP1 gene rs3817198T>C polymorphism with breast cancer risk: evidence from 33,920 cases and 35,671 controls - Min-Bin Chen; Chen Li; Wen-Xiang Shen; Yu-Jiang Guo; Wei Shen; Pei-Hua Lu (Molecular Biology Reports, 2011)

The characterization of two novel IRF-3 transcripts starting from intron 2 of the wild type of IRF-3 - Wei Ren; Hua-Guo Xu; Chao Lu; Rui Jin; Li Zou; Yi Wang; Guo-Ping Zhou (Molecular Biology Reports, 2011)

Identification and expression analysis of two growth hormone receptors in zanzibar tilapia (Oreochromis hornorum) - Feng-Ying Gao; Mai-Xin Lu; Xing Ye; Zhang-Han Huang; Huan Wang; Hua-Ping Zhu; Li-Ping Yang (Fish Physiology and Biochemistry, 2011)

Physiological significance of P2X receptor-mediated vasoconstriction in five different types of arteries in rats - Lu Li; Zhen-Hua Jia; Chao Chen; Cong Wei; Jian-Ke Han; Yi-Ling Wu; Lei-Ming Ren (Purinergic Signalling, 2011)

Effects of palmitic acid on lipid metabolism homeostasis and apoptosis in goose primary hepatocytes - Zhixiong Pan; Jiwen Wang; Hui Tang; Liang Li; Jia Lv; Lu Xia; Chunchun Han; Feng Xu; Hua He; Hengyong Xu; Bo Kang (Molecular and Cellular Biochemistry, 2011)

Analysis of correlation between blood biochemical indicators and bone mineral density of post-menopausal women - Shun-zhi Liu; Li-fang Tian; Peng Xu; Gui-hua Zhuang; Fang Zheng; Juan Tian; Qi-Lan Ning; Bo-Feng Zhu; She-Min Lu; Hong Yan (Molecular Biology Reports, 2011)

An ordered EST catalogue and gene expression profiles of cassava (Manihot esculenta) at key growth stages - You-Zhi Li; Ying-Hua Pan; Chang-Bin Sun; Hai-Tao Dong; Xing-Lu Luo; Zhi-Qiang Wang; Ji-Liang Tang; Baoshan Chen (Plant Molecular Biology, 2010)

Structural basis for the decrease in the outward potassium channel current induced by lanthanum - Li Hong Wang; Na Jiang; Bo Zhao; Xiao Dong Li; Tian Hong Lu; Xiao Lan Ding; Xiao Hua Huang (JBIC Journal of Biological Inorganic Chemistry, 2010)

Post-conditioning protects cardiomyocytes from apoptosis via PKCε-interacting with calcium-sensing receptors to inhibit endo(sarco)plasmic reticulum–mitochondria crosstalk - Shiyun Dong; Zongyan Teng; Fang-hao Lu; Ya-jun Zhao; Hulun Li; Huan Ren; He Chen; Zhen-wei Pan; Yan-jie Lv; Bao-feng Yang; Ye Tian; Chang-qing Xu; et al. (Molecular and Cellular Biochemistry, 2010)

Computed tomography angiography-guided percutaneous coronary intervention in chronic total occlusion - Ping Li; Lu-yue Gai; Xia Yang; Zhi-jun Sun; Qin-hua Jin (Journal of Zhejiang University-SCIENCE B, 2010)

Chromosomal localization of rDNA genes and genomic organization of 5S rDNA in Oreochromis mossambicus, O. urolepis hornorum and their hybrid - Hua Ping Zhu; Mai Xin Lu; Feng Ying Gao; Zhang Han Huang; Li Ping Yang; Jian Fang Gui (Journal of Genetics, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Brief report: a new profile of terminal N-acetyllactosamines glycans on pig red blood cells and different expression of α-galactose on Sika deer red blood cells and nucleated cells - Yingxia Tan; Feng Gong; Subo Li; Shouping Ji; Yanping Lu; Hongwei Gao; Hua Xu; Yangpei Zhang (Glycoconjugate Journal, 2010)

Effects of sevoflurane preconditioning and postconditioning on rat myocardial stunning in ischemic reperfusion injury - An-lu Dai; Li-hua Fan; Feng-jiang Zhang; Mei-juan Yang; Jing Yu; Jun-kuan Wang; Tao Fang; Gang Chen; Li-na Yu; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

Phosphoproteomic identification and phylogenetic analysis of ribosomal P-proteins in Populus dormant terminal buds - Chang-Cai Liu; Tian-Cong Lu; Hua-Hua Li; Hong-Xia Wang; Gui-Feng Liu; Ling Ma; Chuan-Ping Yang; Bai-Chen Wang (Planta, 2010)

A structurally novel salt-regulated promoter of duplicated carbonic anhydrase gene 1 from Dunaliella salina - Jie Li; Yumin Lu; Lexun Xue; Hua Xie (Molecular Biology Reports, 2010)

Analysis of two sequence variants in peroxisome proliferator activated receptor gamma gene in Tajik population at high altitudes and Han population at low altitudes in China - Xiao-Ling Liu; Feng-Lin Zhang; Zhi-Yong Zhou; Hua-Lu Zhao; Guo-Min Shen; Wu-Yun Baohan; Zi-Yuan Duan; Wei Li; Jun-Wu Zhang (Molecular Biology Reports, 2010)

Characterization and structural analysis of the coat protein from Chinese isolates of Cymbidium mosaic virus - Yun-Chao Liu; Lu-Bin Li; Yun-Liang Li; Qing-Hu Ma; Zhen-Hua Peng (Journal of Plant Diseases and Protection, 2009)

Correlation Analysis Between Bone Mineral Density and Serum Element Contents of Postmenopausal Women in Xi’an Urban Area - Shun-Zhi Liu; Hong Yan; Peng Xu; Jian-Ping Li; Gui-Hua Zhuang; Bo-Feng Zhu; She-Min Lu (Biological Trace Element Research, 2009)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Inhibition of lung metastasis in mice by intravascular injection of dendritic cells and natural killer cells - Hui-fang Lv; Feng Cui; Chang-hua Yu; Li-li Deng; Jing-jing Ji; Dan Lu; Yu Yang; Wen-xiu Wang; Yu-qing Xu (Biotechnology Letters, 2009)

Characterization of ATPase activity of class II chaperonin from the hyperthermophilic archaeon Pyrococcus furiosus - Hua-you Chen; Xiao-li Tan; Jian Lu; Chun-xia Zhang; Yi Zhang; Sheng-li Yang (Biotechnology Letters, 2009)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)

Analysis of rice genes induced by striped stemborer (Chilo suppressalis) attack identified a promoter fragment highly specifically responsive to insect feeding - Hongxia Hua; Qing Lu; Meng Cai; Caiguo Xu; Dao-Xiu Zhou; Xianghua Li; Qifa Zhang (Plant Molecular Biology, 2007)

Cloning and heterologous expression of nitrate reductase genes from Dunaliella salina - Hua Xie; Peirong Xu; Yanlong Jia; Jie Li; Yumin Lu; Lexun Xue (Journal of Applied Phycology, 2007)

A follow-up study of mortality among the arseniasis patients exposed to indoor combustion of high arsenic coal in Southwest Guizhou Autonomous Prefecture, China - Ji-gang Chen; Yu-gang Chen; Yun-shu Zhou; Guo-fang Lin; Xiu-jie Li; Chao-gang Jia; Wei-chao Guo; Hui Du; Hong-chao Lu; Hong Meng; Xin-jiang Zhang; Klaus Golka; et al. (International Archives of Occupational and Environmental Health, 2007)

Comparative analysis of telomeric restriction fragment lengths in different tissues of Ginkgo biloba trees of different age - Di Liu; Nan Qiao; Han Song; Xin Hua; Juan Du; Hai Lu; Fenglan Li (Journal of Plant Research, 2007)

China Subregional Avian Endemism and Biodiversity Conservation - Fu-Min Lei; Guo-An Wei; Hong-Feng Zhao; Zuo-Hua Yin; Jian-Li Lu (Biodiversity and Conservation, 2007)

Zinc adsorption and desorption characteristics in root cell wall involving zinc hyperaccumulation in Sedum alfredii Hance - Ting-qiang Li; Xiao-e Yang; Fan-hua Meng; Ling-li Lu (Journal of Zhejiang University-SCIENCE B, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Surface pollen in the east of Qaidam Basin - Hui Chen; Dongsheng Zhao; Xinmiao Lu; Yuecong Li; Qinghai Xu; Shuangcheng Li; Hua Ouyang (Journal of Geographical Sciences, 2006)

Soil microbial biomass as affected by non-flooded plastic mulching cultivation in rice - Yong-Shan Li; Liang-Huan Wu; Xing-Hua Lu; Li-Mei Zhao; Qiao-Lan Fan; Fu-Suo Zhang (Biology and Fertility of Soils, 2006)

Identification of differentially expressed genes in seeds of two near-isogenic Brassica napus lines with different oil content - Rong-Jun Li; Han-Zhong Wang; Han Mao; Ying-Tang Lu; Wei Hua (Planta, 2006)

Molecular analysis of early rice stamen development using organ-specific gene expression profiling - Xiao-Chun Lu; Hua-Qin Gong; Mo-Li Huang; Su-Lan Bai; Yang-Bo He; Xizeng Mao; Zhi Geng; Song-Gang Li; Liping Wei; Jie-Shuai Yuwen; Zhi-Hong Xu; Shu-Nong Bai (Plant Molecular Biology, 2006)

Functional analysis of helicase and three tandem HRDC domains of RecQ in Deinococcus radiodurans - Li-fen Huang; Xiao-ting Hua; Hui-ming LU; Guan-jun Gao; Bing Tian; Bing-hui Shen; Yue-jin Hua (Journal of Zhejiang University-SCIENCE B, 2006)

In situ and in vitro colonization of Cathaya argyrophylla (Pinaceae) by ectomycorrhizal fungi - Lu-Min Vaario; Shu-Tang Xing; Zong-Qiang Xie; Zhi-Ming Lun; Xue Sun; Yu Hua Li (Mycorrhiza, 2006)

Association tests of interleukin-6 (IL-6) and type II tumor necrosis factor receptor (TNFR2) genes with bone mineral density in Caucasians using a re-sampling approach - Peng Xiao; Peng-Yuan Liu; Yan Lu; Yan-Fang Guo; Dong-Hai Xiong; Li-Hua Li; Robert R. Recker; Hong-Wen Deng (Human Genetics, 2005)

Study on beijing’s emerging mobile communication industrial cluster and its policy implications - Tie-shan Sun; Guo-ping Li; Ming-hua Lu (Chinese Geographical Science, 2003)

Conservation on diversity and distribution patterns of endemic birds in China - Fu-Min Lei; Yan-Hua Qu; Jian-Li Lu; Yao Liu; Zuo-Hua Yin (Biodiversity and Conservation, 2003)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)

A polymorphism in the promoter region of catalase is associated with blood pressure levels - Zhengwen Jiang; Joshua M. Akey; Jinxiu Shi; Momiao Xiong; Ying Wang; Yayun Shen; Xiaoyun Xu; Hua Chen; Hong Wu; Junhua Xiao; Daru Lu; Wei Huang; et al. (Human Genetics, 2001)

Ground water hydrochemical characteristics: seawater intruded area in eastern and southern coast of Laizhou Bay - Zhang Zu-lu; Jiang Lu-guang; Yang Li-yuan; Qi Yong-hua (Journal of Geographical Sciences, 2001)